Lightweight real-time detection of sweet potato virus disease by a hybrid CNN–Transformer network - Ru Han; Lei Shu; Grzegorz Cielniak; Yan Zhu; Xing Yang; Fan Yang; Kai Huang (Computers and Electronics in Agriculture, 2026)

Divergent controls on nitrogen and phosphorus export regimes across Chinese catchments - Xu Yang; Haojie Han; Xing Yan; Yuting Xie; Yanyu Ren; Yuhang Zhang; Daming Yang; Dongli She; Xuan Huang; Yongqiu Xia (Water Research, 2026)

Alox12 mediates the temporal shift of arsenite-induced ferroptosis in zebrafish embryonic fibroblast ZF4 cells - Yu Wang; Xu Han; Zizheng Wang; Yushan Song; Yiqiang Zhang; Mingwei Xing; Hongjing Zhao (Toxicology, 2026)

A novel Pb(Ⅱ) − styrene phosphonic acid complex collector for ilmenite flotation: breaking the recovery bottleneck and revealing the selective adsorption mechanism - Zhiyuan Chen; Shuixiang Wang; Hongyang Xie; Zhao Wei; Pan Chen; Jihua Zhai; Haisheng Han; Wei Sun; Yaowen Xing; Xiahui Gui (Minerals Engineering, 2026)

Cadmium-associated cognitive impairment in adults: Proteomics-guided blood-based risk stratification with external validation and rat multimodal corroboration - Hao Gao; Hui Liu; Sheng Wan; Zhaokui Dan; Jianjun Xiong; Zelong Xing; Yinghui Yin; Feng Han; Yong Yang; Maoqin Tian; Qiwen Chen; Zhijian Hu; et al. (Environmental Pollution, 2026)

Microplastics stimulating polycyclic aromatic hydrocarbon biodegradation via cometabolism in historically coking-contaminated soil: Superior performance of biodegradable microplastics - Guixiang Zhang; Hongyu Zhang; Fengsong Zhang; Lanfang Han; Ke Sun; Hao Wu; Chen Liang; Dandan Liu; Long Ping; Baoshan Xing (Environmental Pollution, 2026)

Molecular bridging stabilizes halide perovskites for durable photocatalytic H2 production in pure water - Xiwen Ma; Na Han; Wanying Cheng; Guiqiang Diao; Ming Sun; Shaomin Peng; Guichuan Xing; Lin Yu (Chemical Engineering Journal, 2026)

Interconnected microporous carbon enabling boosted electrode-scale kinetics in dense supercapacitor electrodes - Qiqi Li; Su Zhang; Yutong Li; Junwei Han; Zhiyuan Li; Wei Xing; Han Hu; Luxiang Wang; Nannan Guo; Ning Cao (Chemical Engineering Journal, 2026)

Mild amorphization and structural reconstruction enable non-destructive recycling of continuous fiber-reinforced PAEK composites - Zhongxin Dong; Yanchao Yang; Dianfu Ren; Yanwei Xiao; Di Wu; Liangliang Pei; Yunhe Xing; Han Feng; Shengdao Wang; Guibin Wang (Chemical Engineering Journal, 2026)

Genomic and biosynthetic landscape of high-temperature Daqu microbiome - Mingyue Cheng; Xing Qin; Ying Han; Fanggen Tan; Menglin She; Xue Zhu; Lin Yuan; Mengjing Teng; Xiyang Ou; Sha Luo; Ping Xiang; Liangqiang Chen; et al. (Bioresource Technology, 2026)

Unraveling the short- and long-term effects of lignocellulosic pretreatment derivatives on the anaerobic co-digestion of corn straw and food waste: Digester performance, microbial community, and metabolic mechanisms - Sifan Cao; Yong-Chen Han; Xiaochang C. Wang; Rong Chen; Bao-Shan Xing (Bioresource Technology, 2026)

New thread-winged lacewings from the mid-Cretaceous Kachin amber highlight the early diversification of Nemopteridae (Insecta: Neuroptera) - Yu-Han Yan; Yu-He Gao; Fang-Yuan Xia; Xing-Yue Liu (Cretaceous Research, 2026)

Clinical outcomes of patients with brain metastases from primary esophageal cancer - Bianca Nolde-Lopez; Christina K. Cramer; Scott Isom; Anthony Naquin; Caio M.S.P. Rocha Lima; Ravi K. Paluri; Jimmy Ruiz; Fei Xing; Christopher T. Whitlow; Stephen B. Tatter; Adrian W. Laxton; Jaclyn J. White; et al. (Next Research, 2026)

Enhanced biodegradation of pharmaceutical wastewater via electron transfer mediated by electric field from cation-π driven on catalyst surface - Congjian Wei; Tong Ren; Xueci Xing; Chun Hu; Han Zhang (Journal of Water Process Engineering, 2026)

Modeling of hydrological performance degradation in permeable pavement systems induced by their spatiotemporal clogging evolution - Zihao Liu; Qiongfang Li; Yiqun Sun; Zhengmo Zhou; Yao Du; Shuhong Xu; Xingye Han; Xing Huang; Junliang Jin (Journal of Hydrology, 2026)

Green recovery and regeneration of ultrafine silver powder from end-of-life photovoltaic modules via ethylene glycol–citric acid/H2O2 system - Yuyang Han; Feihong Guo; Xing Chen; Xue Lan; Xiaoxiang Jiang (Journal of Environmental Chemical Engineering, 2026)

Zr-modified NiAl layered double hydroxide for efficient adsorptive removal of reactive Black 5: From synthesis optimization to interfacial adsorption mechanisms - Huaqing Zhang; Yixin Xing; Mingyu Han; Zhengxu Kang; Bowen Wang; Xiaoyi Shen; Jianzhong Li; Yuchun Zhai (Journal of Environmental Chemical Engineering, 2026)

Straw decomposition slightly affects soil Cd availability and bacterial communities: Insights from batch adsorption and Cd speciation - Xingbin Zhang; Chengxi Zhou; Shitong Ding; Yihao Wang; Zhongyi Cheng; Hui Han; Xing Xia; Jianjun Yang; Xiangwei Wu (Journal of Environmental Chemical Engineering, 2026)

Dynamic flavor perception in sturgeon caviar during oral processing revealed by volatile release, neural responses, and phospholipid changes - Guixin Han; Ke Li; Jinlin Wang; Peng Xu; Tianhong Liu; Ruichang Gao; Lianfa Gong; Xing Zhao; Xinxing Xu; Yuanhui Zhao (Food Chemistry, 2026)

N-3 PUFA deposition and esterification patterns drive aroma profile remodeling in the longissimus dorsi of pigs fed flaxseed oil - Yingsen Liu; Longzhu Zhou; Luxi Lin; Shijie Wang; Yiyu Yin; Haoyang Han; Huihui Tian; Miaomiao Dong; Pingyang Li; Youyou Yang; Xiaohui Feng; Weihai Xing; et al. (Food Chemistry, 2026)

Charge–viscosity coupling–regulated interaction mechanism of polysaccharides and intestinal mucin - Yangyang Zhang; Lina Yang; Yaqin Zong; Siying Xing; Shengnan Wang; Lu Han; He Liu (Food Bioscience, 2026)

Novel temperature-tolerant Schiff base derivative as high-efficiency inhibitor for acid corrosion of N80 steel - Li-Mao Chen; Shuang-Jian Li; Ru-Han Li; Bo-Kai Liao; Xing-Peng Guo; Long-Fei Song (Chemical Engineering Journal, 2026)

Multi-site Ag-π conductive gel for ultrasensitive digital acousto-optic sensor - Jintao Tian; Yihao He; Hao-Ran Yang; Xing Han; Xiao-Wen Sun; Hong Yao; Tai-Bao Wei; Jin-Fa Chen; Bingbing Shi; Qi Lin (Chemical Engineering Journal, 2026)

Engineered TGF-β-enriched exosomes delivered by dissolving microneedles for androgenetic alopecia therapy - Yu-Qing Ni; Yi-Fan Ji; Bo Huang; Si-Jia Tang; Zi-Han Fang; Li-Bin Wang; Yuan Zhang; Xing Li (Chemical Engineering Journal, 2026)

Janus dual-nitride heterostructure on nanoporous metal for highly selective urea oxidation-assisted hydrogen production - Zhi-Lan Zhou; Jin-Peng Li; Ying Wang; Rui-Qi Yao; Xin-Ying Sun; Shu-Pei Zeng; Yun-Fei Chang; Gao-Feng Han; Tong-Hui Wang; Zi Wen; Hang Shi; Xing-You Lang; et al. (Chemical Engineering Journal, 2026)

Unveiling dynamic membrane functions in a high-rate anaerobic mesophilic co-digestion system treating cow manure and food waste: Performance, digestate characteristics, and microbial community - Hao-Cheng Zhang; Liguo Wan; Yule Han; Xiaochang C. Wang; Rong Chen; Yu-You Li; Bao-Shan Xing (Bioresource Technology, 2026)

Semiconducting polymer-based ratiometric fluorescent nanoprobe for highly accurate imaging of H2S in inflammatory and tumor cells - Chen Han; Xing Wang; Yating He; Rong Wang; Hong-Min Meng; Lin Zhang; Zhaohui Li (Analytica Chimica Acta, 2026)

Rapid assessment method for lateral bearing capacity of row piles in levee-breach closure based on an improved p-y curve - Shu-Han Chen; Xing-Huai Huang; Yu Fang; Zhao-Dong Xu; Sheng-Yu Chang (Ocean Engineering, 2026)

Rare earth elements as emerging contaminants: Multi-source release, geochemical tracing, and implications for environmental monitoring and management - Yong-He Han; Ming-Zhu Zou; Dong-Xing Guan; Yi-Xi Li; Ping Xiang; Yong Zhang; Hong Zhang; Zhibiao Chen (Journal of Environmental Management, 2026)

Molecular authentication of Polyporus umbellatus and its commercial products using a nucleotide signature - Junrong Wang; Yongmei Xing; Huilin Yuan; Yiyun Fan; Jianping Han; Xiaohui Pang (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

Bioinspired artificial lipase with engineered hydrophilic microenvironment for oriented substrate binding and structured lipids preparation - Han Liu; Keyu Xing; Shaoyi Yu; Jia Tu; Yanna Jiao; Liguang Xu; Wei Chen; Pei Jia; Zhou Xu (Food Research International, 2026)

Constructing deep traps and high barriers via interfacial covalent cross-linking in NiS@POSS@CQDs/PEI composites for high-temperature energy storage - Rujian Zhao; Qixiong Zhang; Qinyun Yu; Xing Wu; Jiujun Zhu; Renlu Han; Yafei Hou; Zhongbin Pan; Jing Cuan; Weiping Li (Chemical Engineering Journal, 2026)

Carbon radical-promoted NH bond breaking for biomass-derived amino acids to nitriles on low-coordinated Ni centers - Huiwen Zhang; Xia Zhang; Yue Ma; Yingnan Zhao; Rui-Qi Yao; Xinying Sun; Tonghui Wang; Beibei Xiao; Gao-Feng Han; Xing-You Lang; Qing Jiang (Chemical Engineering Journal, 2026)

Gradient polypyrrole-coated CS/PVA/β-CD/Fe3O4 NPs magnetic aerogels for efficient solar interfacial evaporation - Chen Yang; Qing Han; Zheng Jiang; Yuyuan Tian; Ruyue Liu; Fuxin Zhao; Wilberforce Agbley; Xuechun Wang; Yan Dou; Jianyu Xing (Chemical Engineering Journal, 2026)

Dual-clay composite electrolyte with rigid-flexible interlocked architecture for safe lithium metal batteries - Zhangkuo Han; Shusen Zhou; Di Jiang; Jiahan Zheng; Huiying Hao; Jie Xing; Jingjing Dong; Hao Liu; Libing Liao (Chemical Engineering Journal, 2026)

Preparation of gelatin based wood adhesive with “cascading triggering - synergistic enhancement” (CTSE) mechanism - Yuanyuan Qiang; Zhentao Wei; Xuechuan Wang; Lei Yang; Lei Han; Bin He; Xing Zhu (Chemical Engineering Journal, 2026)

Facile fabrication of high-performance hollow fiber-supported porous organic cage membranes via Zn2+-bridging for advanced helium separation - Tianliang Han; Qi Wu; Pengfei Xing; Hongying Mo; Baoru Yu; Zhenyuan Li; Can Wang; Lili Gong; Shuangjiang Luo (Chemical Engineering Journal, 2026)

Photochemically corrected machine learning framework for real-time VOCs source apportionment in support of air quality management - Yu Han; Xing Peng; Yi Hong; Jiang-Yao Tan; Jiang Wu; Li He; Xiao-Feng Huang; Guang-He Yu; Ke Du (Atmospheric Environment, 2026)

METTL18-catalyzed histidine methylation of YTHDF2 promotes mRNA stability - Wen-Lan Yang; Meng-Xia Liu; Yue Han; Xing-Xing Li; Ye Gu; Xinyuan Tian; Mengqian Mu; Xiaolin Zhang; Yanzhe Wang; Xinyu Li; Yu-Sheng Chen; Chun-Chun Gao; et al. (Science China Life Sciences, 2026)

SCAD-DTA: spherical concept alignment with dynamic multi-modal fusion for drug–target affinity prediction - Zhensong Wang; Weiliang Han; Ge Kong; Yuan Zhang; Jiajie Xing; Juan Wang (Molecular Diversity, 2026)

Synthesis and antifungal activity evaluation of flavonol derivatives containing an imidazolidinone moiety - Qingxue Hu; Xiaoting Geng; Xiaoyan Pan; Dan Shen; Han Yang; Fang Tian; Mingman Sun; Lang Xing; Ying Yang; Wei Xue (Molecular Diversity, 2026)

Lactobacillus Plantarum R-Fermented Phellodendron Amurense Extract Protects Against Pseudorabies Virus by Regulating Oxidative Stress and Inflammation in Vitro and in Vivo - Mengyao Zhao; Feifan Wu; Zenghao Xu; Xing Han; Sai Mao; Hongying Zhang; Yina Zhang; Mingfan Yang (Probiotics and Antimicrobial Proteins, 2026)

Prioritizing riparian scale landscape management is a spatially efficient strategy for controlling river water quality in China - Haojie Han; Xing Yan; Xuran Li; Xu Yang; Xiaohan Li; Zelin Huang; Xiaoyuan Yan; Yongqiu Xia (Water Research, 2026)

Welfare spillovers from inter-city carbon transfers in China’s metropolitan areas - Xinyu Han; Yuxin Wang; Zeyu Xing (Sustainable Cities and Society, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Novel insights into the flotation enhancement of fine cassiterite via hydrophobic solid microbubbles: experimental and interfacial interaction force aspects - Zhiguo Han; Shimei Li; Jiushuai Deng; Jianying Deng; Dingquan Xing; Chang Liu; Zhongyi Bai (Process Safety and Environmental Protection, 2026)

Environmental context and human presence at the Shaojiagouwan site, Salawusu River basin - Jiequn Hua; Fuyou Chen; Hao Long; Shuangquan Zhang; Tingting Chen; Yinghua Wang; Mingchao Shan; Han Yang; Shengrui Li; Jiacheng Ma; Jian Wang; Guanhan Chen; et al. (Quaternary Science Reviews, 2026)

Toddacoumalins A-J, ten undescribed coumarins from the roots of Toddalia asiatica - Feng Wu; Han Yao; Xin-Rui Liao; Nan An; Xing-Shu Li; Wen-Hao Hu; Albert S.C. Chan; Hou-Jin Li; Wen-Jian Lan (Phytochemistry, 2026)

Source apportionment and spatial drivers of soil microplastics across land-use types revealed by APCS-MLR and Geodetector - Tongtong Meng; Mingya Wang; Qiao Han; Mingfei Xing; Fengcheng Jiang; Chuanbing Zhang; Mingshi Wang (Journal of Hazardous Materials, 2026)

Health risk of PM2.5-bound heavy metals in a megacity in South China: Comparison between before and after the outbreak of COVID-19 - Runhua Wang; Xing Peng; Kejin Tang; Yu Han; Jiangyao Tan; Ning Feng; Shaoxia Wang; Liwu Zeng; Xiaofeng Huang; Lingyan He; Sihua Lu; Min Hu (Journal of Environmental Sciences, 2026)

Assessing additive interactions of heat wave, fine particulate matter, and ozone on cardiovascular mortality in a typical cold region of China: A time-stratified case-crossover study - Jinghao Wan; Mingzhao She; Hanhan Wang; Lixin Zheng; Xinyue Yu; Yuqian Song; Zhongran Wang; Min Li; Xu Han; Haibo Zhou; Zhifeng Xing; Xiao Bai; et al. (International Journal of Hygiene and Environmental Health, 2026)

Application of optimized hydrothermal, ozone and superalkali pretreatment techniques for qualitative biogas production from corn straw: A comparative assessment - Sifan Cao; Yong-Chen Han; Huqe Farhana; Xiaochang C. Wang; Rong Chen; Yu-You Li; Bao-Shan Xing (Fuel, 2026)

Unveiling the flavor and microbial dynamics: a comprehensive analysis of key flavor compounds and core microorganisms in industrial-scale naturally fermented Jianshui pickle - Wenwen Zhang; Wenwen Li; Yu Qin; Xing Han; Dengjie Yao; Muxi Yang; Lirong Li; Rui Huang (Food Chemistry, 2026)

Medium-entropy ceramics surfaces with organic tethers: A route to rapid densification and improvement anti-ablation performance for C/SiBCN-(Hf1/2Zr1/3Ti1/6) C composites - Yijun Zhang; Shengman Yan; Jingjun Xu; Xing Chen; Han Yan; Yu Liu; Yiduan Zhang; Weijian Han; Zhongwei Zhang (Chemical Engineering Journal, 2026)

MXene-enhanced self-healing nanocomposite hydrogels with multiple-dynamic-bond crosslinking for motion sensing and information transmission - Ze-Hua Hou; Huan-Jie Che; Zi-Han Jiang; Xing Wu; Jin-Ping Yuan; Jing Li; Jian-Bo Qu (Chemical Engineering Journal, 2026)

17β-estradiol reshapes the reproductive dose–response to polystyrene nanoplastics in the rotifer Brachionus calyciflorus - Qi-bin Zhu; Yi-fan Feng; Yi-fu Xing; Yu Zhang; Jiang-hua Yang; Cui Han; Xiao-jie Liu; Jia-xin Yang (Aquatic Toxicology, 2026)

Unveiling the enigma of anxiety disorders and depression: from pathogenesis to treatment - Han-Qing Pan; Tian Xia; Yu-Ya-Nan Zhang; Hui-Jie Zhang; Meng-Jie Xu; Jing Guo; Yan Liu; Xue-Ying Bai; Qian Liu; Wei-Zhu Liu; Wen-Hua Zhang; Qi-Gang Zhou; et al. (Science China Life Sciences, 2026)

Stable leaf pH of grassland community under nitrogen inputs ensured by contrasting intra- and inter-specific variations - Xiao-Hua Yang; Cong Ding; Xiao-Sa Liang; Yuan-Xiu Wu; Xiao-Ru Zhang; Xiao-Jing Zhang; Liang-Chao Jiang; Xing-Guo Han; Xiao-Tao Lü (Plant and Soil, 2026)

Exploring the complex relationship between vestibular symptoms and migraine: a resting‑state functional MRI study - Lin Han; Xing Xiong; Jiajie Lu; Kai Zhang; Jun Ke; Hongru Zhao (Brain Imaging and Behavior, 2026)

Acute Stress Drives Adaptive Anxiety via Excitatory-Inhibitory Imbalance in the Prefrontal-Amygdala Circuit in Male Mice - Jia-Xin Zou; En Cao; Zhi-Hao Wang; Rui Han; Xing-Yan Lu; Cheng-Yuan Huang; Xia Qin; Wei-Zhu Liu; Wen-Hua Zhang; Bing-Xing Pan (Neuroscience Bulletin, 2026)

BRSK2 accumulation mediated by TRIM28 accelerates hepatocellular carcinoma progression via activating the PI3K/AKT/mTOR signaling pathway - Shengjin Han; Tan Liang; Cui Yang; Yunlong Xing; Jianzhong Ma; Zhengwu Zhou; Zixiang Chen; Yijun Zhao; Jiangming Chen; Fubao Liu (Molecular and Cellular Biochemistry, 2026)

Integrated hydrochemical assessment and health risk evaluation of coastal groundwater under seawater intrusion and anthropogenic influence in Weihai, North China - Linxian Huang; Kai Hu; Zhong Han; Xiaonong Hu; Liting Xing; Hui Liu; Hao Liang; Henghua Zhu (Environment, Development and Sustainability, 2026)

Coupled Aero-Hydro-Elastic Response Analysis of 16 MW Semi-Submersible and TLP Floating Wind Turbines - Kangzhe Li; Jinghong Shang; Liang Liu; Xuliang Han; Xing Zheng; Guangyuan Cheng (Journal of Marine Science and Engineering, 2026)
This study investigates the dynamic performance characteristics of 16 MW-class floating wind turbines supported by semi-submersible and tension leg platform (TLP) concepts, with the aim of providing guidance for platform selection. High-fidelity coupled aero-hydro-servo-elastic models were developed in OpenFAST for both floating platform configurations. Dynamic simulations were carried out under operational conditions for five wind–wave inflow directions with aligned environmental loading. The responses of the floating systems were comprehensively evaluated in terms of platform six-degree-of-freedom motions, tower structural behavior, blade aeroelastic loads, and aerodynamic performance. The results show that the TLP configuration provides enhanced hydrodynamic stability, reduced platform motions, and improved aerodynamic efficiency compared with the semi-submersible platform. In contrast, the semi-submersible configuration exhibits lower aeroelastic loading levels. Furthermore, platform-induced hydrodynamic excitations significantly amplify the elastic responses of both the tower and blades, leading to noticeable variations in aerodynamic performance. These findings provide useful insights into the design and selection of next-generation large-scale floating wind turbine platforms.

Chemical composition of the endogenous fungus Fusarium sp. L-3 derived from Chinese Qinan agarwood - Ming-Li Han; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Jiao-Cen Guo; Hao-Fu Dai; Na Xiao; You-Xing Zhao (Natural Product Research, 2026)

Exogenous phytohormones as protective agents against high light-induced bleaching in Betaphycus gelatinae - Zexu Liu; Haolong Zheng; Xiangyu Wu; Shouguo Yang; Han Yang; Yifang Zhao; Yixuan Xing; Xianming Tang; Zhifeng Gu; Yaohua Shi; Feng Yu (Journal of Applied Phycology, 2026)

Coupling microbial electrosynthesis and chain elongation for simultaneous biomethane upgrading and carboxylate recovery: A tunable carbon valorization strategy - Kai-Kai Wu; Shu-tong Wu; Chuan Chen; Zi-Han Wang; Ya-Ru Wang; Li Zhao; Juan Tong; Fei Shen; De-Feng Xing; Nan-Qi Ren; Lei Zhao (Water Research, 2026)

Temporal trajectory and determinants of permanent gully erosion in the grassland: A long-term analysis spanning 1973–2020 - Zhicai Xiao; Mingming Guo; Xin Liu; Zhuoxin Chen; Xingyi Zhang; Jinzhong Xu; Shaoliang Zhang; Jielin Liu; Xing Han; Ruifeng Xie (Soil and Tillage Research, 2026)

Parameter calibration of a particle discrete element model for amphibious screw-propelled vehicle in sandy loamy soil road - Jiayi Wang; Xing Han; Ruihan Wang; Anliang Yu; Juan Zhou (Journal of Terramechanics, 2026)

A newly merging approach of multiple precipitation products by combining time-varying quadruple collocation and random forest spatial interpolation - Shuhong Xu; Qiongfang Li; Yiqun Sun; Zhengmo Zhou; Chuanhao Wu; Xiaoqiang Yang; Xingye Han; Xing Huang; Junliang Jin (Journal of Hydrology, 2026)

Functional characterization of a previously unknown gene governing metamorphosis in Bombyx mori - Tao Lu; Zhiping Xing; Hui Dong; Yuping Deng; Zhipeng Li; Han Gao; Xiaojing Liu; Bo Hu; Anjiang Tan (Insect Biochemistry and Molecular Biology, 2026)

Market mechanism design and trading decision model incorporating renewable energy alliances for the future electricity capacity market of China - Ying-zhu Han; Xing-ping Zhang; Li Liu; Jia-lin Li; Qin-liang Tan; Yuan-fei Li; Yi Du (Energy Policy, 2026)

A bilayer nanofiber textile integrating radiative cooling, phase-change buffering, and anisotropic heat spreading for adaptive personal thermal management - Guang-peng Luo; Jin Wang; Yu-tong Wu; Chang-hui Ma; Xing-xiang Zhang; Na Han (Chemical Engineering Journal, 2026)

Micro-scale redox heterogeneity governs chromium mobility and reoxidation in flooded industrial soils with contrasting properties - Danxing Yang; Hao Zhang; Wen Fang; Haiyi Chen; Haitao Sun; Xing Liu; Chao Han; Jun Luo (Chemical Engineering Journal, 2026)

Pilot-scale treatment of wool scouring wastewater in two-stage anoxic/oxic moving bed biofilm reactor: Performance and nitrogen removal mechanism - Xing Fan; Xueqing Shi; Jiahua Wu; Wenxuan Qiu; Xifeng Zhao; Jiazhong Zhou; Wenjie Han; Hongrui Lu; Ling Wang; Xuejun Bi (Bioresource Technology, 2026)

Long-Term Multi-Parameter Monitoring of Subsurface Fluids: Advances, Applications, and Future Prospects - Sihang Han; Yifei Xing; Guangzheng Jiang; Chuanzhi Liao; Shu Hu; Zhenyu Li; Bohan Zeng (Water Resources Management, 2026)

Impact of polystyrene nanoplastics on soil microbial biomass - Chunyang Li; Heping Shang; Zeyu Cai; Weili Jia; Yini Cao; Xiupei Zhou; Jie Zhang; Sixiang Zhuang; Ziqin Lin; Anqi Liang; Lanfang Han; Jason C. White; et al. (Environmental Chemistry Letters, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

Polystyrene nanoplastics disrupt iron homeostasis by promoting FPN1 ubiquitination in GC-2spd(ts) cells - Xinru Cui; Yitong Shang; Liyang Ding; Zhen Zhang; Yu Deng; Tengjiao He; Bo Xu; Xufeng Fu; Xing Du; Hang Han (Toxicology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Effects and mechanisms of a novel multi-target regulator on serum uric acid reduction and renal injury improvement in rats with hyperuricemia and renal damage - Zhihua Xing; Yue Xu; Wen Jiang; Zhiyuan Xu; Guanghuan Shen; Na Ling; Mingyu Gao; Weina Han; Yingjie Liu; Linlin Cui (PharmaNutrition, 2026)

Research on the excitation force and cavitation performance of a pump-jet propulsor in ice blockage flow - Qiaogao Huang; Sijie Zheng; Han Li; Jing Liu; Xing He; Xinming Li; Bo Lu; Xihui Wang; Li Zhou (Ocean Engineering, 2026)

Palaeopolyploidy promoted ancient adaptation of Tibetan sclerophyllous oaks to aridity and cold triggered by mountain uplift - Jin-Jin Hu; Wen-Guang Sun; Jia Liu; Robert A. Spicer; Zhuo Zhou; Yong-Jiang Huang; Zhi-Min Li; Tao Su; Ting-Shen Han; He Tang; Lin-Bo Jia; Yun-Heng Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Ce-Fe-MI/CA composite catalyst for catalytic ozonation: Synergistic adsorption-activation via Ce/Fe sites & oxygen vacancies and application in air flotation-catalytic ozonation coupling process for pharmaceutical wastewater - Lin Yue; Shiqi Xing; Xiaoyun Han; Wang Liang; Yanfang Liu; Xinyang Liang; Yonghui Han (Journal of Environmental Chemical Engineering, 2026)

Biochar nanoparticles modulate root-associated microbial interactions under polycyclic aromatic hydrocarbon stress - Yu Shen; Hao Su; Dongru Wang; Hui Huang; Jiangang Han; Hui Li; Melanie Kah; Xinhua Zhan; Baoshan Xing (Journal of Environmental Management, 2026)

Experimental study of an R515B/CO2 cascade refrigeration system for commercial applications - Bingdong Wang; Yaoxiang Han; Lixin Liu; Yanpeng Li; Chuang Wang; Ziwen Xing (International Journal of Refrigeration, 2026)

Efficient hydrolysis of glycosides by Pichia kudriavzevii with high-activity β-glucosidase: a critical role in enhancing terpene aroma in beer - Lin Yuan; Xiaoping Hou; Yang He; Xiujuan Wan; Jiaxin Han; Wenqi Xu; Shuo Yu; Shuang Bi; Lijuan Ma; Lei Xing (Food Chemistry, 2026)

A dual-functional fluorescent sensor based on a single soybean-derived carbon dots for discrimination and quantification of tetracyclines in food - Xin Lin; Jiaqi Wang; Meiqi Xia; Shuang Li; Yixin Xu; Jingyi Sun; Han Leng; Tianqun Song; Yanzhi Xing; Mei Yang (Food Chemistry, 2026)

A review of computational approaches for metagenomics by long-read sequencing - Baichen Le; Longhao Jia; Tianxiang Pang; Shuwen Han; Yiqian Duan; Xing-Ming Zhao (Science China Life Sciences, 2026)

Does the heat tolerance induced by Sargassum horneri extract in Pyropia yezoensis sporophytes transfer to gametophytes? - Ho-Hyeon Lee; Jae Woo Jung; Ji-Sook Park; Qikun Xing; Young-Seok Han; Jang Kyun Kim (Journal of Applied Phycology, 2026)

Sediment transport characteristics in a highly erosive catchment based on flood events in the northern earth-rocky mountainous areas, China - Jianqiao Han; Yuanhao Liu; Hongting Gao; Lijuan Shen; Xianshuang Xing; Yuan Yuan (Frontiers of Earth Science, 2026)

A developed cascade DNA recycling amplification integrating with microchip electrophoresis for ultrasensitive detection of Cronobacter sakazakii - Shuang Tang; Xing Geng; Jianan Lv; Mengmeng Han; Sijin Li; Fan Zhang; Qingjiang Wang (Analytica Chimica Acta, 2026)

Enhancing solar-to-chemical conversion by CdSe-cyanobacteria biohybrids - Xiaofei Wu; Fangshu Xing; Yue Qiao; Guodong Luan; Jian Liu; Weihua Wang; Zuozhen Han; Xuefeng Lu (Algal Research, 2026)

Prevalence and Molecular Characterization of Entamoeba spp. in Pigs in Shanxi Province, North China - Ze-Dong Zhang; Han-Dan Xiao; Dong-Yang Wang; Zi-Rui Wang; Xun-Zhi Liu; Nan Su; Xing-Quan Zhu; Qing Liu; Wen-Wei Gao (Acta Parasitologica, 2026)

Description of the second scale‐developed and eyed Sinocyclocheilus (Cypriniformes: Cyprinidae) species from South Guizhou, China, with evolutionary implications - Zhi‐Xuan Zeng; Xing‐Wei Cai; Jia‐Jun Zhou; Wei‐Tao Chen; Wei‐Han Shao (Journal of Fish Biology, 2026)
The genus Sinocyclocheilus represents the world's most diverse cavefish radiation, typically exhibiting troglomorphic traits such as scale regression and eye degeneration. Notably, Sinocyclocheilus macrolepis from a tributary of the Long‐Jiang of the Pearl River retains fully developed scales despite inhabiting epigean streams, a rare trait among its cave‐adapted congeners. The Sinocyclocheilus specimens collected from a tributary of the Hongshui‐He of the Pearl River in South Guizhou exhibit overall similarities to S. macrolepis with fully developed scales and normal eyes. Phylogenetic analyses using mitochondrial Cyt b and ND4 genes reveal that these specimens represent a novel species, sister to S. macrolepis but with significant genetic divergence, and closely related to Sinocyclocheilus ronganensis . This new species was designated as Sinocyclocheilus pingchowensis in this study. Morphologically, S. pingchowensis differs from S. macrolepis in lateral‐line scale counts, head width, gill‐opening position and pelvic‐fin ray counts. S. pingchowensis along with S. macrolepis and S. ronganensis are herein defined as the S. macrolepis group based on the shared synapomorphies and phylogenetic affinities. The phylogenetic tree suggests that the retention of scales in the species pair of S. pingchowensis and S. macrolepis represents a rare case of evolutionary reversal from cave‐adapted degeneration. This phenotypic re‐emergence correlates with their re‐colonization of surface water, likely reflecting a synergistic adaptation to both photic exposure and occupation of the niche of mid‐upper water strata, coinciding with relaxed selection on cave‐associated trade‐offs. The divergence of S. pingchowensis from its sister species was likely triggered by the river capture event between the two rivers.

Three‑Dimensional Brittle–Ductile Strength Criterion Based on Parameterization Method - Jiacun Liu; Gang Han; Yawu Shao; Ying Xu; Xing Li; Kaiwen Xia (Rock Mechanics and Rock Engineering, 2026)

Scour-Protection Strategies for Offshore Wind Farms: A Life Cycle Assessment of Operation and Maintenance Impacts - Yingyue Xing; Chanjuan Han (Journal of Marine Science and Engineering, 2026)
The operation and maintenance (O and M) phase of offshore wind farms is often simplified in life cycle assessments (LCA), especially with respect to scour-related activities. This study develops a refined O and M–LCA model that explicitly includes scour monitoring, repair, and protection measures, and applies it to a 202 MW offshore wind farm in China. The analysis focuses on the environmental burdens of scour-related O and M activities under predefined engineering scenarios, rather than on the prediction of structural fatigue life or reliability-based intervention timing. Two representative scour-protection strategies were compared: rock dumping (S1) and cement-stabilized soil (S2). The results show that scour protection can substantially increase the environmental burdens of the O and M phase. Relative to the baseline O and M carbon intensity of 4.36 kg CO2-eq/MWh, S1 causes only a slight increase in global warming potential but greatly increases air pollution- and resource-related impacts because of large-scale rock extraction and transport. In contrast, S2 reduces mineral resource scarcity from 2.14 to 0.042 kg Cu-eq/MWh, corresponding to a 98% reduction compared with S1, but raises the global warming potential to 9.94 kg CO2-eq/MWh, mainly because of cement production and offshore treatment. Sensitivity analysis shows that S1 is more affected by hydrodynamic-driven intervention frequency in air pollution-related categories, whereas S2 is more sensitive to seabed conditions and stabilization efficiency in terms of GWP. A site-specific screening framework is proposed by integrating geotechnical and hydrodynamic constraints, regional environmental concerns, and targeted mitigation options. The results provide O and M-stage environmental evidence for the site-specific screening of scour-protection strategies and for improving the environmental performance of offshore wind O and M.

Research progress on the regulatory mechanisms of the PSY promoter - Bing-Bing He; Xing-Wen Zhou; Jing-Jing Li; Jie Sun; Yi-Qing Xie; Guo-Yong Han; Jia-Shi Lu (Transgenic Research, 2026)

Corrigendum to “Acanthoic acid protectsagainst ethanol-induced liver injury: Possible role of AMPK activation and IRAK4 inhibition” [Toxicol. Lett. 281 (2017) 127–138] - You-Li Yao; Xin Han; Jian Song; Jing Zhang; Ya-Mei Li; Li-Hua Lian; Yan-Ling Wu; Ji-Xing Nan (Toxicology Letters, 2026)

Development characteristic of permanent gully morphology at the small watershed scale and its relations with driving factors along the Mollisols Belt of Northeast China - Xiaohui Lian; Ningning Xiao; Mingming Guo; Xingyi Zhang; Xin Liu; Jinzhong Xu; Shengmin Zhang; Xing Han (Soil and Tillage Research, 2026)

Research on thrust fluctuation and flow field characteristics of pump-jet propulsor in XLUUV's hull wake - Bo Lu; Qiaogao Huang; Han Li; Wei Qiang; Xing He; Xinming Li; Sijie Zheng; Xihui Wang (Ocean Engineering, 2026)

Sustainable alternative to biochar: Effects of oxychar on soil carbon sequestration pathway and microbial communities - Cheng Ji; Chenchen Zhao; Shutao Wang; Qinggang Meng; Huiwei Zhao; Yifan Li; Duo Li; Mingzhen Xing; Shiming Su; Bing Han; Wei Liu (Journal of Environmental Sciences, 2026)

Distinct cytotoxicity of water disinfection byproducts in human uroepithelium and Chinese hamster ovary cells - Jiaojiao Xie; Jian Han; Yanming Liu; Birget Moe; Qiming Shen; Tongtong Xiang; Chun-Gang Yuan; Xing-Fang Li (Journal of Environmental Sciences, 2026)

Monte Carlo simulation-based characteristics of indoor radon concentrations and exploratory probabilistic risk analysis in university buildings - Yuefei Ma; Mingya Wang; Decheng Qin; Xuechun Zhang; Chunhui Zhang; Qiao Han; Fengcheng Jiang; Mingfei Xing; Xiaoming Guo; Chuanbing Zhang; Pinghua Huang; Mingshi Wang (Journal of Environmental Radioactivity, 2026)

Tailoring pore architecture in hard carbons: Clarifying the distinct sodium storage roles of closed pores and ultra-micropores - Wei-wei Kang; Hai-tao Zeng; Guang-xu Huang; Jian-bo Jia; Qiang Li; Han Hu; Bing Xu; Wei-jie Guo; Rui Hao; Bao-lin Xing; Chuan-xiang Zhang (Chemical Engineering Journal, 2026)

BTEXS metabolites and lung dysfunction in petrochemical workers: Dose-response relationships and the mediation of oxidative stress - Dongsheng Wang; Rui Ma; Minghui Xiao; Zhaorui Zhang; Han Yang; Yanrong Lv; Shaorui Yu; Xiumei Xing; Shanfeng Dang; Qifei Deng; Xiaoyu Mao; Qiansheng Hu; et al. (Atmospheric Pollution Research, 2026)

Isolation of Rhizospheric Fungi from Crocus sativus L. Rhizosphere and their Effects on Host-Growth Promotion - Jing-Chao Xu; Xing-Guang Xie; Xin-Zhu Yu; Zi-hao Zhu; Xue-Wen Bi; Kun-miao Feng; Ying-jie Lu; Khalid Rahman; Bo Zhu; Lu-ping Qin; Zhen-zhen Zhang; Ting Han (Current Microbiology, 2026)

Applied research on predicting strong earthquake risk areas in western Yunnan based on Curie-point depth and seismogenic characteristics - Xing Ju; Hua Guo; Zhi-tao Shao; Song Han; Meng-chu Xiao; Jin-peng Huang (Applied Geophysics, 2026)

Study on S-wave Velocity Structure and Seismogenic Structure in the Source Region of the 1976 M6.2 Horinger Earthquake - Dong-yang Pei; Xiao-ming Han; Juan Li; Fan Zhang; Li-feng Chen; Shu-bo Wang; Wei Guo; Xin Wang; Tie-suo Zhao; Xing Zhao; Jin-zhe Bao (Applied Geophysics, 2026)

Effects of Offshore Wind Farm-Associated Electromagnetic Fields on the Physiology and Behavior of Sebastes schlegelii - Tingting Wen; Hongwu Cui; Zhengguo Cui; Xinxing Zhang; Qi Zhang; Juanjuan Sui; Xixi Han; Huanhuan Jiang; Congcong Xing; Mian Xie; Yanrong Zhou; Weihan Yin; et al. (Fishes, 2026)
To evaluate the potential biological effects of electromagnetic fields from offshore wind farms on Sebastes schlegelii, a laboratory-controlled chronic exposure experiment was conducted using a magnet-based static magnetic field system. Each group contained 60 fish distributed across four replicate tanks, with 15 fish per tank, and the fish were continuously exposed for 20 d under controlled water-quality conditions. Daily video monitoring of collective shoaling behavior was combined with multi-tissue physiological and biochemical analyses. Electromagnetic field exposure increased the swimming speed, burst frequency, activity ratio, spatial coverage, occupancy entropy, and polarization, while reducing the nearest neighbor distance, group radius, and group area. At the physiological level, cortisol increased mainly in the liver and brain, ACTH showed tissue-dependent modulation, SOD remained relatively stable, and glutathione increased in multiple tissues, especially in the liver, gut, and brain. Correlation analysis indicated a close coupling between behavioral reorganization and endocrine–redox regulation, suggesting that chronic EMF exposure shifted Sebastes schlegelii into a stress-associated but functionally coordinated collective state.

Stereogenic P(V) platform construction via streamlined installation - Jing-Ming Zhang; Shi-Feng Tao; Xing-Kai Zhao; Han Yang; Gong Xu; Zhi-Tao He (Science Bulletin, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

An assessment of model parameters for offshore torpedo anchors - Jinbo Chen; Zhuo Wang; Chao Tang; Zhaolong Han; Xing Tao; Yunliang Shao; Xiaoni Wu (Ocean Engineering, 2026)

Boron-doped diamond electrodes for environmental applications: From structure-property relationships to electrochemical remediation and sensing - Liwei Chen; Yurong Guo; Yanrong Chen; Yan Zhang; Mingming Gao; Yingying Jing; Yen Leng Pak; Xing Gao; Suqin Han; Lan Bao; Jibin Song (Journal of Environmental Chemical Engineering, 2026)

Insight into the mechanism of doxycycline promoting N2O emissions during swine manure composting - Chengyu Ma; Yunfeng Qian; Bingbing Xing; Han Xiao; Hao Zhu; Shanshuai Chen; Wei Gao; Xin Jin; Huanyu Bao; Yunze Ruan (Journal of Environmental Chemical Engineering, 2026)

Alterations in soil pH drive the impact of global change on glomalin-related soil protein: a global meta-analysis - Jia Zeng; Xing Wang; Zhengchen Wang; Fang Chen; Jingbo Fang; Hongxia Wang; Chengjie Ren; Gaihe Yang; Zekun Zhong; Yiqi Luo; Thomas Ward Crowther; Xinhui Han (Journal of Environmental Management, 2026)

Pathway toward carbon neutrality of cement industry: A comprehensive analysis based on microdata - Mengling Zhang; Baokun Li; Hairui Yang; Man Zhang; Dongfang Li; Xing Zhu; Runsheng Lin; Yongkang Han; Aoyang Zhang (Fuel, 2026)

Deciphering the mechanisms underlying cadmium tolerance in the endophytic fungus Trichoderma atroviride D16 - Xue-Wen Bi; Xing-Guang Xie; Wen-Jing Zhang; Rui-Di Zhang; Khalid Rahman; Xin-Zhu Yu; Cun-Yu Fan; Shu-Lang Ding; Yu-Qing Peng; Ting Han (Fungal Biology, 2026)

Integrated analysis of time-driven sensory deterioration and microbial dynamics in not-from-concentrate (NFC) pitaya juice during storage - Bing Xia; Lingfang Shi; Susu Han; Jianling Kang; Zongren Zhao; Weizhao Li; Fuguo Xing (Food Chemistry, 2026)

Leveraging deep learning and spectral information for enhanced variety identification of safflower seeds - Hao Huang; Wen-Xia Li; Chao-Chuan Jia; Hui Yan; Shan-Yong Yi; Lei-Lei Gao; Cun-Wu Chen; Bang-Xing Han; Fang Wang (Food Chemistry, 2026)

HFPO-TA induces cardiac developmental damage in zebrafish by disrupting mitochondrial dynamics through FABP3 - Xing Liu; Mingzhu Xia; Xinyi Wu; Ruobing Chen; Yuting Peng; Yi Fan; Junjie Han; Yichun Zhao (Environmental Research, 2026)

Automated identification of single- and multi-mode vortex induced vibrations: Algorithm and application to a cable stayed bridge - Min He; Peng Liang; Zhi-han Zhou; Yu-hao Pan; Xing-shun Lu; Wei-song Luo (Engineering Structures, 2026)

Research progress and future prospects of cellulose-based composite gas separation membranes from a green sustainability perspective - Han Pei; Jinghui Zhou; Hongge Jia; Chengbao Geng; Mingyu Zhang; Yanqing Qu; Shuangping Xu; Xiaozhou Zhang; Xing Wang; Jingyu Xu (Carbohydrate Polymers, 2026)

Sources of PM2.5 pollution in Kui-Du region on the northern slope of Tianshan Mountains: Insights from chemical and optical characterization - Yueyi Yang; Jun Li; Yi Han; Chunxiao Qiu; Ruizhi Zhou; Yunyan Zhao; Zhaoyi Xing; Caiqing Yan (Science China Earth Sciences, 2026)

Controlled irrigation combined with powdered straw return enhance rice yield while mitigating greenhouse gas emissions - Jinhua Zhang; Yugeng Guo; Bingxiao Liu; Xiaohui Xu; Zexun Liu; Han Han; Xiangping Guo; Xing Yang; Wenye Zhang (Plant and Soil, 2026)

Research progress on the structure of photosynthetic reaction centers–mobile electron carrier supercomplexes - Jiasheng Jiang; Jie Wang; Xing Han; Xiaochun Qin; Shishang Dong (Photosynthesis Research, 2026)

Irrigation and straw particle size jointly drive soil bacterial community assembly to regulate nutrient cycling in paddy fields - Jinhua Zhang; Han Han; Bingxiao Liu; Xiangping Guo; Xing Yang; Wenye Zhang (Applied Soil Ecology, 2026)

A multilevel regression model to explain disparities in residential cooling infrastructure across heat-threatened regions - Yang Yang; Haoying Han; Shuyang Li; Jiayi Fu; Xing Su; Chao Fan (Applied Geography, 2026)

Moisture-Proof Herbal Extract Pellets Prepared via Asymmetric Liquid Layering Technology Combined with Mesoporous Silica and Magnesium Stearate - Shilin Ma; Yupeng Feng; Panao Yuan; Yunlong Xu; Ping Shao; Lifeng Lin; Zimin Wang; Ling Han; Xing Tang (AAPS PharmSciTech, 2026)

Comparative insights into denitrification performance and microbial adaptation of heterotrophic, autotrophic, and mixotrophic systems under florfenicol stress for recirculating mariculture wastewater treatment - Feng You; Shaofei Yang; Yunzhu Ding; Jinfeng Han; Dongxu Xing; Chunji Jin; Yangguo Zhao; Mengchun Gao; Liang Guo (Water Research, 2026)

Assessment of gully erosion susceptibility in Northeast China's black soil region using new stacking model with multiple machine learning algorithms - Zhang Minghao; Qin Wei; Wang Xiangdong; Yin Zhe; Xu Xiaohong; Zhou Liheng; Han Xing (Soil and Tillage Research, 2026)

Corrigendum to “Aridity shapes distinct biogeographic and assembly patterns of forest soil bacterial and fungal communities at the regional scale” [Sci. Total Environ., 948, (2024), 174812] - Xing Wang; Jia Zeng; Fang Chen; Zhengchen Wang; Hanyu Liu; Qi Zhang; Weichao Liu; Chengjie Ren; Gaihe Yang; Zekun Zhong; Xinhui Han (Science of The Total Environment, 2026)

Spray-dried soy protein/tamarind seed polysaccharide/tea polyphenol ternary complexes with enzymatic and natural crosslinking enhance probiotic viability - Jialei Sun; Jiayu Wang; Haiyue Niu; Yue Zhou; Xing Li; Xue Han (Food Chemistry, 2026)

Plant and microbial interactions under different planting patterns regulate nitrogen removal in constructed wetlands - Feng-Cong Jia; Yue Zhang; Yu Han; Xing-Peng Wang; Yu-Hui Yang; Wei-Jie Wang (Bioresource Technology, 2026)

The orbital dynamics modeling and simulation of asteroid probe based on variational integrators - Zhen-Zhen Han; Shi-Xing Liu; Yong-Xin Guo (Advances in Space Research, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Design of an AUV Visual Docking Localization Simulation Platform Based on Webots - Runfa Xing; Lichuan Zhang; Guangyao Han; Lu Liu (Journal of Marine Science and Engineering, 2026)
To meet the design and evaluation requirements of underwater vision-based docking localization, a Webots-based simulation platform for Autonomous Underwater Vehicle (AUV) visual docking localization was designed and implemented to address the high cost of real sea trials, uncontrollable operating conditions, and the difficulty of systematically covering extreme scenarios. An end-to-end simulation of the docking localization pipeline was provided. Visual components—including fiducial markers, underwater illumination and imaging, and occlusion—were modeled in relatively fine detail, while non-vision-dominant factors such as propulsion and hydrodynamics were treated with approximate models to balance visual realism and simulation efficiency. The platform supported multiple types of visual markers, parameterized configuration of underwater lighting and turbidity, and the generation of diverse occlusion scenarios, enabling unified integration and benchmarking of docking localization algorithms. The results showed that the platform offered tunable scene parameters, repeatable conditions, and broad algorithm compatibility, and it effectively revealed performance differences across algorithms for complex combinations of illumination, turbidity, and occlusion. These capabilities reduced the risk and cost of real underwater docking experiments and supported faster iterative improvement of vision-based localization methods.

A spatio-temporal attention enhanced CNN method for marker localization in AUV docking - Runfa Xing; Lichuan Zhang; Bing Huang; Guangyao Han; Lu Liu (Frontiers in Marine Science, 2026)
Underwater docking of autonomous underwater vehicles (AUVs) was typically dependent on the complete visual detection of markers. When markers were only partially visible due to occlusion or departure from the field of view, conventional localization methods based on complete features were rendered ineffective, resulting in the interruption of docking operations. To address this limitation, an enhanced orientation-aware method based on a spatiotemporal attention convolutional neural network (CNN) was proposed in this study. The core of this method was a dual-path feature fusion architecture: discriminative features of visible marker segments were extracted from single frames by the spatial path, while the temporal path was employed to aggregate features across consecutive frames, thereby compensating for the insufficiency of single-frame information. These two pathways were adaptively fused through a spatiotemporal attention module, which was designed to dynamically focus on the most informative cues. Consequently, robust qualitative judgment of the marker’s relative orientation was achieved. Experimental validation conducted in underwater environments demonstrated that stable orientation awareness was maintained by the proposed method even under conditions where the marker was severely off-center or largely obscured. This approach was shown to significantly extend the initial capture range for AUV docking guidance, and the robustness and operational continuity of the system under extreme visual conditions were effectively enhanced.

The novel PFOS substitute OBS induces visual developmental toxicity in zebrafish embryos via ferroptosis - Xing Liu; Xinyi Wu; Mingzhu Xia; Yi Fan; Yichun Zhao; Junjie Han; Ruobing Chen; Yuting Peng; Man Qu (Toxicology Letters, 2026)

A mixed mushroom poisoning in humans associated with the ingestion of Collybiopsis orientisubnuda - Xiu-Juan Li; Chang Xu; Wen-Hao Zhang; Jing Ma; Han-Chi Lei; Jia Li; Yu-Xian Gao; Xing Xia; Ping Wei; Yi Liu; Li-Ping Tang (Toxicon, 2026)

Controllable deterministic quantum teleportation of multiple sideband qumodes - Na Wang; Meihong Wang; Chun Ma; Xuefan Xing; Dongmei Han; Xiaolong Su (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

A global meta-analysis of N2O emission-yield trade-offs in wheat, rice and maize systems under different agricultural management - Jia Zeng; Yu Li; Xing Wang; Qi Zhang; Ying Lu; Jingjing Wang; Yang Guo; Hongxia Wang; Gang Yang; Chengjie Ren; Gaihe Yang; Xinhui Han (Resources, Conservation and Recycling, 2026)

A Pb(II)–oleate complex collector for highly selective flotation of ilmenite from titanaugite - Zhiyuan Chen; Zhao Wei; Haisheng Han; Wei Sun; Yaowen Xing; Xiahui Gui (Minerals Engineering, 2026)

Agglomeration of coal gangue particles in an ultra-supercritical CFB boiler: microstructure, thermodynamic modeling, mechanisms and prevention methods - Xiuting Yang; Junjie Li; Seokgi Ahn; Yongkang Han; Lin Pu; Chung-Hwan Jeon; Hua Wang; Xing Zhu; Tao Zhu; Dongfang Li (Fuel, 2026)

Corrigendum to “Aldehyde metabolism in Maotai-flavor baijiu: insights from integrated metagenomic and metaproteomic analyses” [Food Res. Int. 221(Part 3) (2025) 117518] - Chao Li; Fan Yang; Ying Han; Chong Yang; Xing Qin; Huizhen Zheng; Liangqiang Chen; Jianjun Lu; Cuiying Zhang; Fuping Lu; Li Wang (Food Research International, 2026)

Prenatal organophosphate esters exposure impacts placental structure and inflammatory markers in a trimester-specific manner - Yuan Liu; Ping Lv; Xing Wang; Mengqian Zhang; Yifan Wang; Sheng Wang; Mengjuan Lu; Han Li; Hong Gan; Juan Tong; Hui Gao; Fangbiao Tao (Environmental Research, 2026)

Halophytes reclamation soil through improving soil structures, decreasing salinity and enhancing SOC storage in coastal saline land - Huanyu Chen; Sunan He; Ziyan Xue; Xiao Zhang; Kai Yu; Kai Wang; Angyan Ren; Jianjun Han; Xiaohui Zhao; Xiaomei Zhu; Chong Liu; Lizhou Hong; et al. (Ecological Engineering, 2026)

Zero-solvent-emission rapid synthesis of aerogel beads: A food-colorant adsorbent with biocompatibility and facile separation - Boxuan Peng; Jiahui Li; Tong Wu; Shiyi Wang; Fangzheng Zhao; Chunyue Zhao; Qingyun Liu; Enchang Liu; Huizhen Han; Siyuan Yu; Jinfeng Xing (Chemical Engineering Journal, 2026)

Biomimetic knitted fabric with hierarchical gradient for high-efficiency personal thermal–moisture management - Zhijia Dong; Luyi Han; Xing Feng; Honglian Cong; Yousong Xue; Pibo Ma (Chemical Engineering Journal, 2026)

Dual improvement in thermal stability and flame retardancy of addition-cure liquid silicone rubber mediated by oxygen vacancy-rich fillers - Yue Xing; Yao Li; Hailan Kang; Feng Yang; Long Li; Wenchi Han; Genshi Liu; Qinghong Fang (Chemical Engineering Journal, 2026)

Fe-Mn modified activated carbon three-dimensional electrodes enhance electron transfer in bacterial-algal systems for mariculture wastewater treatment and microalgal product recovery - Feng You; Jinfeng Han; Dongxu Xing; Chunji Jin; Yangguo Zhao; Liang Guo (Bioresource Technology, 2026)

Manganese cycle-mediated synchronous bacteria-algae/anammox coupled denitrification system under low-temperature conditions: Performance and mechanisms - Peng-fei Yu; Dian-lin Jiang; Ding Wang; Xing-guan Ma; Jun-Li; Li-yao Han; Ao Wang; Yu-bo Fu; Xing Jin (Bioresource Technology, 2026)

Chemical characteristics and source apportionment of free amino acids in the Qinling forest atmosphere of central China - Xin Zhang; Rui Wang; Jianjun Li; Shuyan Xing; Lijuan Li; Yue Lin; Junji Cao; Yuemei Han (Atmospheric Environment, 2026)

Discrimination of seismic event near the North Korean nuclear test site (January-March 2022) using multi-station P/S spectral ratios - Bo-Han Wang; Lian-Feng Zhao; Xiao-Bi Xie; Xi He; Yong Zhao; Zhen-Xing Yao (Journal of Seismology, 2026)

Adaptive gaining-sharing knowledge region coverage planning for multi-stratospheric airships in complex environments - Xing-han Liu; Ming Zhu; Yi-fei Zhang; Tian Chen (Advances in Space Research, 2026)

Experimental Study on Mechanism of Using Complex Nanofluid Dispersions to Enhance Oil Recovery in Tight Offshore Reservoirs - Zhisheng Xing; Xingyuan Liang; Guoqing Han; Fujian Zhou; Kai Yang; Shuping Chang (Journal of Marine Science and Engineering, 2026)
Horizontal wells combined with multi-stage fracturing are key techniques for extracting tight oil formation. However, due to the ultra-low permeability and porosity of reservoirs, energy depletion occurs rapidly, necessitating external supplements to sustain production. During the hydraulic fracturing process, large volumes of fracturing fluid are injected into reservoirs, increasing its pressure to a certain extent. However, due to the oil-wet nature of the formation, the fracturing fluid cannot penetrate the rock, failing to enhance oil recovery during the shut-in period. Surfactant-based nanofluids have been introduced as fracturing fluid additives to reverse rock wettability, thereby boosting imbibition-driven recovery. Although the imbibition has been studied to inspire the tight oil recovery, few studies have demonstrated the imbibition in enhanced fossil hydrogen energy, which further promotes the imbibition recovery. In this paper, complex nanofluid dispersions (CND) have been proved to enhance the tight reservoir pressure. Through contact angle and imbibition experiments, it is shown that CND can transform oil-wet rock to water-wet, reduce the adhesion of oil, and improve the ultimate oil recovery through the imbibition effect. Then, core flow testing experiments were conducted to show CND can decrease the flow resistance and improve the swept area of the injected fluid. In the end, pressure transmission tests were conducted to show CND can enhance the formation energy and production after fracturing. Results demonstrate that CND enables the fracturing fluid to travel further away from the hydraulic fractures, thus decreasing the depletion of tight formation pressure and maintaining a higher oil production rate. Results help optimize the design of the hydraulic fracturing of tight offshore reservoirs.

Logbook fish yield data improving species distribution model forecasting for purse seine fishery in the Western and Central Pacific Ocean - Tung-Yao Hsu; Jen-Han Yang; Xing-Han Wu; Yi Chang (International Journal of Remote Sensing, 2026)

Few-shot natural frequency prediction of Camellia oleifera for vibration harvesting enabled by synthetic data generation - Feng Liu; Dongying Mo; Han Fu; Shaozheng Yu; Xuan Chu; Nan She; Xing Xu; Weizu Wang; Jieli Duan (Computers and Electronics in Agriculture, 2026)

DEM-MBD-based study on mechanism of tamping-induced ballast breakage and tamping tine optimization in ballasted track beds - Yang Xu; Hongyang Han; Yike Yang; Luzhuang Li; Xing Ling; Luchao Qie; Chaozhi Ma (Transportation Geotechnics, 2026)

Nomilin ameliorates perfluorooctanoic acid (PFOA)-induced impairment of zebrafish (Danio rerio) ocular development and visual function through PIK3CA activation - Xing Liu; Mingzhu Xia; Xinyi Wu; Ruobing Chen; Yuting Peng; Yi Fan; Junjie Han; Yichun Zhao; Man Qu (Toxicology and Applied Pharmacology, 2026)

Comparative study of bow form resistance performance in open water, pack ice, and level ice for Arctic shipping - Biye Yang; Borui Yang; Zhe Sun; Xu Han; Guiyong Zhang; Song Liu; Hao Xing (Ocean Engineering, 2026)

Temperature shapes the biogeography of rdhA and reductive dehalogenators in sediment across northwestern Pacific marginal seas - Yangru Xu; Yingchun Han; Xiyang Dong; Yanlei Feng; Fabai Wu; Fengmin Xing; Junyu He; Matthew J. Rogers; Xiwu Luan; Rulong Liu; Jianzhong He; Hongyue Dang; et al. (Journal of Hazardous Materials, 2026)

Hydrothermal carbonization of sewage sludge: Effects of hydrothermal temperature and time on biochar properties and migration and transformation of heavy metals - Siyao Hou; Han Wang; Jiameng Sun; Jing Liu; Manxu Bai; Wanli Zhang; Wanli Xing; Rundong Li (International Biodeterioration & Biodegradation, 2026)

Limited association of m6A RNA modification with post-transcriptional regulation during honeybee caste differentiation - Chen Yang; Yu Zhu He; Yu Xiang Wang; Xing Chao Yan; Xu Han; Zhi Jiang Zeng; Xu Jiang He (Insect Biochemistry and Molecular Biology, 2026)

Deciphering the butylated hydroxytoluene dissolution behavior in solid-liquid systems through coupled experimental and molecular dynamic simulation approaches - Xing Wu; Xiaowei Cheng; Shiyu Sun; Jixu Ni; Yuan Han; Mengwen Qu; Baoshu Liu; Hua Sun (Food Chemistry, 2026)

Tannic acid-mediated oxygen vacancies in broccoli-like CeO2@Carbon for enhanced photocatalytic peroxymonosulfate activation toward tetracycline degradation - Huage Lin; Xinrui Han; Yihan Tang; Jiaxiang Zong; Guangyu Wu; Weinan Xing (Environmental Research, 2026)

Bamboo-architecture-inspired aluminum-coordinated hydrogel flexible sensors for smart home systems - Xiaoyu Guan; Xing Li; Liuping Jin; Sai Zheng; Luying Zhang; Dongping Li; Qingxin Han; Xuechuan Wang; Taotao Qiang (Chemical Engineering Journal, 2026)

Fabrication of Prussian blue mixed matrix membranes based on the synchronous growth for water treatment - Xiaotong Lu; Xing Gao; Xiaojiao Hou; Bingbing Chen; Peining Han; Tieqiang Wang; Fanbao Meng; Yu Fu (Chemical Engineering Journal, 2026)

Sr2Sb2O7: A multifunctional oxide platform for cyan-compensated healthy lighting and near-infrared applications - Changle Luo; Yanbing Han; Qingqing Mo; Xiaoyang Xing; Shiyu Zhu; Han Gao; Jinghuo Chen; Zhuangzhuang Ma; Mochen Jia; Linyuan Lian; Jibin Zhang; Ying Liu; et al. (Chemical Engineering Journal, 2026)

Dual-crosslinked injectable polysaccharide-based hydrogel with synergistic photothermal-controlled release of black phosphorus-baicalein for accelerating wound healing - Huizhen Han; Zhen Wang; Tong Wu; Fangzheng Zhao; Shuaibing Huang; Boxuan Peng; Chunyue Zhao; Qiqi Han; Enchang Liu; Qingyun Liu; Jinfeng Xing (Carbohydrate Polymers, 2026)

Microbial-electrochemical driven simultaneous biogas upgrading and high-value medium-chain carboxylic acid production - Ya-Ru Wang; Chuan Chen; Shu-Tong Wu; Zi-Han Wang; Lei Zhao; Juan Tong; Kai-Kai Wu; De-Feng Xing; Ai-Jie Wang; Nan-Qi Ren (Bioresource Technology, 2026)

Nomilin mitigates OBS-induced developmental cardiotoxicity via the Nrf2 pathway - Xing Liu; Yi Fan; Ruobing Chen; Yuting Peng; Xinyi Wu; Mingzhu Xia; Yichun Zhao; Junjie Han; Man Qu (Aquatic Toxicology, 2026)

Reshaping the root-associated bacterial community for enhanced phosphorus deficiency tolerance in foxtail millet - Xiongwei Zhao; Mengqing Li; Yixuan Liang; Jie Zhang; Jian Cui; Chuang Ma; Yuanhuai Han; Yiwei Jiang; Yanhua Cao; Guofang Xing (Plant and Soil, 2026)

Mechanisms and Therapeutic Potential of Targeting Mitophagy in Neurodegenerative Diseases - Ya-Ning Wang; Xing Wang; Qin Huang; Yun Yang; Tao Wang; Xin-Hui Qu; Xiao-Jian Han (Molecular Neurobiology, 2026)

Presence of Astrocytic S1R/5-HT1A Heterocomplex in the mPFC: A Putative Link to S1R Activation Mediated Faster Antidepressant-Like Effects - Peng Ren; Jing-Ya Wang; Meng-Jie Xu; Han Ni; Shuang Zhang; Chen-Xing Yue; De-Yi Yang; Yun-Feng Li (Molecular Neurobiology, 2026)

Shifts in epidemic patterns and age dynamics of RSV, IFV, and SARS-CoV-2 in Chinese children following COVID-19 non-pharmaceutical intervention relaxation, 2017 − 2024 - Yiguo Zhou; Jian-Bo Xia; Meimei Luo; Wan-Xue Zhang; Shan-Shan Zhang; Le Ao; Han Yang; Qin-Yi Ma; Juan Du; Yu-Ting Wang; Ninghua Huang; Xing-Wen Hu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Mineralization Mechanism of Cobalt in the Dahongshan Copper-Iron-Cobalt Polymetallic Deposit in Yunnan, China - Xuhao Kang; Runsheng Han; Yanwei Zhao; Dong Zhao; Hongsheng Gong; Liuqing Meng; Xing Mao; Long Sun; Yinkang Zhou (Acta Geochimica, 2025)

Development and Application of a Polar Ice-Based Ecological Observation Buoy - Xing Han; Guoxuan Liu; Liwei Kou; Yinke Dou (Journal of Marine Science and Engineering, 2025)
Addressing the current situation where in situ observations in the Arctic primarily target physical and a few biogeochemical parameters, leaving a gap in systematic direct observation of biological populations beneath sea ice, this study developed a polar ice-based ecological observation buoy system. Building upon conventional meteorological and oceanographic hydrographic sensors, this system innovatively integrates an underwater imaging module and key technologies such as machine learning-based automatic fish target recognition and reliable dual-channel satellite data transmission in polar environments. Its successful deployment during the 2025 15th Chinese National Arctic Research Expedition verified the system’s stability. During the initial one-month operation period (designed for a monitoring cycle of not less than one year), the data return rates for conventional and image data reached 100% and 96.8%, respectively, achieving quasi-real-time continuous observation of physical and ecological parameters at the air–sea interface in the Arctic Ocean, and it is capable of acquiring not only physical parameters but also visual observations of under-ice fauna. The system successfully acquired and transmitted images containing suspected biological targets and reference objects, providing the first in situ, image-based biological observation dataset for the central Arctic Ocean. This work establishes a new methodological capability for direct ecological monitoring, offering essential equipment support for quantifying biological presence, studying population dynamics, and informing evidence-based polar ecosystem governance.

Taxonomy and phylogeny of Erysiphe species on Liquidambar formosana (Hamamelidaceae) - Jing Feng; Shuang-Bao Wang; Shu-Yan Liu; Michael Bradshaw; Uwe Braun; Shou-Rong Yu; Guan-Xiu Guan; Dan-Ni Jin; Zhao-Yang Zhang; Han-Xing Gao (New Zealand Journal of Botany, 2025)

Toxicity and sublethal effects of thiamethoxam on life-history traits, feeding behavior, and detoxifying metabolism of Aulacorthum solani - Tianyu Xing; Jiahui Lei; Xue Han; Jiayi Wang; Xiaoyun Wang; Changchun Dai; Jian Liu; Zhenqi Tian (Crop Protection, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Ship trajectory prediction under multi-ship coupling effect based on a generative adversarial network - Xiao Li; Zhaokun Wei; Qiang Zhang; Lei Xing; Zhifeng Han; Ge Gao (Ocean Engineering, 2025)

The application of bionic vortex generator on the duct of a pump-jet propulsor and mechanism for its flow control - Sijie Zheng; Xing He; Qiaogao Huang; Han Li; Xinming Li; Bo Lu; Li Zhou (Ocean Engineering, 2025)

Redox-regulated plastoglobule ABC1K1–ABC1K3 kinase complex controls plastoquinone mobilization for chloroplast photosynthetic adaptation to red light - Mei Yang; Hao Huang; Chao Xu; Xue Han; Guochen Qin; Le Chang; Fang Lin; Xuncheng Wang; Hang He; Xing Wang Deng (Molecular Plant, 2025)

Enhancing runoff prediction accuracy of deep learning model using baseflow separation method and timestamp information - Chen Jin; Qin Xu; Xing Chen; Jing Cai; Han Meng (Journal of Hydrology, 2025)

A three-dimensional Copula-based standardized temperature precipitation evapotranspiration water storage index for comprehensive drought monitoring - Xing Huang; Qiongfang Li; Chuanhao Wu; Junliang Jin; Shuhong Xu; Xingye Han; Peng Shi; Qihui Chen; Yiqun Sun (Journal of Hydrology, 2025)

Deciphering the acute toxicity mechanisms of PFAS in algae: A molecular descriptor and binding energy hierarchy perspective - Yanting Li; Lin Zhao; Lu Wang; Han Zhang; Guodong Xing; Jinrui Yuan; Yongkui Yang; Peizhe Sun (Journal of Hazardous Materials, 2025)

Interfacial charge modulation in CuFe2O4/MXene composites: Enhancing persulfate activation and efficient degradation of chloroquine phosphate - Yeqiong Huang; Zhi Song; Boxia Liu; Lin Wang; Xiayan Zhang; Jialu Liu; Dongxu Han; Chuhan Xing; Jing Zhang (Journal of Environmental Chemical Engineering, 2025)

Fertilization managements mitigate microbial carbon and nitrogen limitations while preserving soil organic carbon in croplands compared to grasslands: A meta-analysis - Xing Liu; Mengjie Han; Mengmeng Zhang; Chenran Wu; Zhuo Wang; Yulan Zhang; Zhenhua Chen (Journal of Environmental Management, 2025)

Study on flow field evolution and dispersion patterns of leakage in sour gas gathering pipelines under controlled hydrogen sulfide concentrations - Zhuosong Zhao; Guangyuan Weng; Zhaoyang Han; Chezhan Li; Xiyu Zhu; Xing Wang (Journal of Environmental Chemical Engineering, 2025)

A novel lead ion–octyl hydroxamic acid complex collector for enhanced ilmenite flotation: From crystal structure to surface-specific adsorption - Zhao Wei; Zhiyuan Chen; Haisheng Han; Wei Sun; Yaowen Xing; Xiahui Gui (Journal of Environmental Chemical Engineering, 2025)

Bioremediation of cadmium-phoxim co-contamination by an autochthonous pollutant-resistant consortium enhances Ligusticum Chuanxiong Hort. resistance - Jianpeng Li; Minghui Wu; Han Wu; Qin Han; Yongxiang Gao; Maoxiang Tang; Can Wang; Fangfang Yan; Bin Li; Xing Li; Zhongping Qiu (Journal of Environmental Sciences, 2025)

Synergistic pathways to promote nature-based Solutions: How policy and peer collaboration shape herder decisions on artificial pasture cultivation in Qinghai, China - Dayuan Xing; Liqun Shao; Xiangwei Zhang; Haibin Chen; Han Zhang (Journal of Arid Environments, 2025)

System design, control strategy development and performance comparison analysis for a novel air-liquid hybrid data center cooling system based on cold plates - Shengli Qu; Chuang Wang; Yishuang Liu; Yiwei Feng; Yaoxiang Han; Ziwen Xing (International Journal of Refrigeration, 2025)

A three-dimensional fractional elastoplastic constitutive model for rocks within ductile domain - Jiacun Liu; Junjie Xiao; Ying Xu; Xing Li; Kaiwen Xia; Gang Han (Geomechanics for Energy and the Environment, 2025)

Aldehyde metabolism in Maotai-flavor Baijiu: insights from integrated metagenomic and metaproteomic analyses - Chao Li; Fan Yang; Ying Han; Chong Yang; Xing Qin; Huizhen Zheng; Liangqiang Chen; Jianjun Lu; Cuiying Zhang; Fuping Lu; Li Wang (Food Research International, 2025)

Combining untargeted metabolomics and chemometrics to reveal the metabolic profiles of jujube-hawthorn fermented beverages at different fermentation stages - Zhibin Xing; Tarun Belwal; Hao Huang; Xiang Li; Liangxia Han; Yahui Yin; Chunhui Shan; Xizhe Fu; Yinglin Du (Food Chemistry, 2025)

Abundant and rare microbial subcommunities exhibit different adaptive strategies to temperature stress in Daqu fermentation - Xing Qin; Qingqing Cao; Mengjing Teng; Ying Han; Fan Yang; Ping Xiang; Huabin Tu (Food Bioscience, 2025)

CHI–GSE–Nano-ZnO coating delays grape postharvest deterioration by inhibiting excess ROS via MYB714-pSTS484-mediated resveratrol biosynthesis - Yun-Lu Song; Jia-Lin Xing; Charles Ampomah-Dwamena; Shuai-Hui Ma; Mao-Song Pei; Han-Li Liu; Rui-Ping Feng; Yong-Ke Wu; Tong-Lu Wei; Hai-Nan Liu; Da-Long Guo (Food Bioscience, 2025)

Linking sedimentary PAH occurrence forms to precision lake pollution management: Multidimensional insights via three component analysis - Xiaoshui Li; Chijun Zhou; Erxuan Han; Ziyang Ye; Weijie Liu; Xinli Xing; Shihua Qi (Environmental Research, 2025)

Molecular characteristics of brown carbon aerosols over a forest atmosphere in the Qinling region of central China - Xin Zhang; Shuyan Xing; Jianjun Li; Rui Wang; Lijuan Li; Yue Lin; Junji Cao; Yuemei Han (Environmental Pollution, 2025)

Three-dimensional elastoplastic constitutive modeling of green sandstone within ductile domain - Jiacun Liu; Lei Zhu; Han Gao; Jie Feng; Xing Li; Kaiwen Xia (Computers and Geotechnics, 2025)

Overcoming uranium re-dissociation in microbial electrolysis cells: Hydrogen-bond mediated reduction mechanisms in sulfate-reducing bacteria systems - Leyi Chen; Yuchen Yang; Kengqiang Zhong; Xing Lu; Haowen He; Xing Chen; Luoyi Han; Chengjun Guo; Meng Li; Lei Huang; Jia Yan; Diyun Chen; et al. (Chemical Engineering Journal, 2025)

Multi-side-port nanotube array based on pillar[5]arene-Ag(I) self-assembly for efficient and recyclable separation of trace pyridine - Hao-Ran Yang; Jintao Tian; Xing Han; Tai-Bao Wei; Hong Yao; Bingbing Shi; Jin-Fa Chen; Qi Lin (Chemical Engineering Journal, 2025)

Generation of reactive nitrogen species for ultrasound-catalyzed tumor treatment through cascade reaction by self-supplied H2O2 nano-reactor - Hao Wu; Zhiping Zhang; Zhao Wang; Lei Yu; Quanxiang Han; Yurong Guo; Mingming Gao; Yingying Jing; Liwei Chen; Xing Gao; Yen Leng Pak; Jibin Song (Chemical Engineering Journal, 2025)

SHAP explainable PSO-CNN-BiLSTM for 6-hour prediction analysis of urban PM2.5 and O3 concentrations - Kun Lei; Mingya Wang; Mingshi Wang; QingWei Liu; Fan Zhang; MingFei Xing; Wei Wu; Fengcheng Jiang; Xiaoming Guo; Qiao Han; Fayang Guo; Huiyun Pan; et al. (Atmospheric Pollution Research, 2025)

Coal Gasification Slag Derivatives Loaded with High Activity Ni Enhanced Superoxide Radical to Produce Efficient Degradation of Chloroquine Phosphate - Zhi Song; Yeqiong Huang; Boxia Liu; Xiayan Zhang; Jialu Liu; Cheng Li; Dongxu Han; Chuhan Xing (Water, Air, & Soil Pollution, 2025)

Hippocampal Extracellular Matrix Protein Laminin β1 Regulates Neuropathic Pain and Pain-Related Cognitive Impairment - Ying-Chun Li; Pei-Yang Liu; Hai-Tao Li; Shuai Wang; Yun-Xin Shi; Zhen-Zhen Li; Wen-Guang Chu; Xia Li; Wan-Neng Liu; Xing-Xing Zheng; Fei Wang; Wen-Juan Han; et al. (Neuroscience Bulletin, 2025)

Mitochondrial function in intestinal ischemia-reperfusion injury: mechanisms and therapeutic perspectives - Xuena Han; Zekun Lang; Xinghua Lv; Yang Xing; Min Hou; Zhiguo Tan; Yan Zhang; Yufang Leng (Molecular Biology Reports, 2025)

The crucial role of immune factors in susceptibility to SARS-CoV-2 infection and severity of COVID-19 - Xing-Hao Yu; Rong-Rong Cao; Yi-Qun Yang; Han-Wen Cao; Fei-Yan Deng; Shu-Feng Lei (Molecular Genetics and Genomics, 2025)

Differential Effects of Nitrogen Chemical Forms on Soil Bacterial Communities and Ecosystem Multifunctionality in a Temperate Meadow Steppe - Jian‐Guo Ma; He‐Yong Liu; Jordi Sardans; Raúl Ochoa‐Hueso; Guo‐Jiao Yang; Étienne Yergeau; Josep Peñuelas; Xiao‐Tao Lü; Zheng‐Wen Wang; Xing‐Guo Han; Xiao‐Bo Wang (Global Change Biology, 2025)
Understanding the impact of nitrogen (N) enrichment on soil microbial community and its associations with ecosystem functionality is crucial, given rising global atmospheric N deposition and even greater agricultural inputs. Most previous studies simulating N deposition used single N species, yet the specific effects of different N forms are not fully understood. This limitation hinders our capacity to link changes in soil microbial communities with ecosystem multifunctionality and to assess the impact of atmospheric N deposition on ecosystem services. To bridge this knowledge gap, our study, conducted from 2016 to 2018 in a typical temperate grassland in Inner Mongolia, China, evaluated the differential effects of the addition of four N forms—ammonium bicarbonate (AC), ammonium nitrate (AN), ammonium sulfate (AS), and urea (UR)—on soil bacterial community structure and function, taxonomic interactions, and ecosystem multifunctionality. These forms were applied at five levels (0, 2, 10, 20, and 50 g N m −2 year −1 ) with five replicates as part of a long‐term experiment. Our findings reveal that N forms in combination with increased N loading differentially influence bacterial community structure and functional characteristics, and co‐occurrence networks, alongside ecosystem multifunctionality. Notably, AN/AS significantly reduced bacterial taxonomic and functional diversity and network complexity, unlike AC, which showed minimal changes. The alteration in bacterial community structure and function under AN/AS was more significantly linked to changes in ecosystem multifunctionality than those under AC/UR, with AC having minimal connections. Additionally, keystone taxa responded differently to N levels and showed varied correlations with ecosystem multifunctionality. These results underscore the distinct effects of different N forms on soil bacterial communities and their cascading influence on ecosystem multifunctionality, emphasizing the need for management practices targeted to the specific chemical species of N deposition and fertilization.

Appraisal and strategic allocation of industrial water use efficiency in henan province: balancing economic and ecological environmental objectives - Ken Sun; Xiaotong Xing; Weisheng Xie; Zhenzhen Yang; Jingmin Han; Yuanbiao Wangas; Jiacheng Liu; Enhui Shi; Jiabin Chen (Environment, Development and Sustainability, 2025)

Preparation of Nitrogen-Doped Fluorescent Carbon Quantum Dots and Detection Study of Tetracycline - Li Han; Hui Wang; Jiajia Ye; Fengcui Shi; Wen He; Xing Gao; Yan Gao; Chaoyue Shan; Haidi Cheng (Journal of Fluorescence, 2025)

Phylogenetic analysis and morphological evidence reveal a new genus Motuoorchis in subtribe Goodyerinae (Orchidaceae) - Yue Liu; Mei Sun; Chen Xing Li; Xiang Feng Han; Zhen Liu; Huai Zhen Tian (Plant Biosystems, 2025)

Bromate-reducing capability of nitrate/nitrite-dependent methane driven membrane biofilm reactors - Zi-Han Wang; Chuan Chen; Kai-Yin Ye; Si-Mai Peng; Jing-Yan Tan; Zhong-Fang Sun; Kai-Kai Wu; Wei Wang; De-Feng Xing; Ai-Jie Wang; Nan-Qi Ren; Lei Zhao (Water Research, 2025)

Machine learning reveals heavy metal migration pathways in Asia's largest Pb-Zn smelting region: Soil pollution simulation in Jiyuan - Shaobo Sui; Mingshi Wang; Wanqi Ma; Mingya Wang; Jing Wang; Kewu Liu; Fengcheng Jiang; Xiaoming Guo; Mingfei Xing; Qiao Han; Baoxian Jia; Huiyun Pan (Process Safety and Environmental Protection, 2025)

Preparation and characterization of PAPP@MF microcapsules for enhancing the safety of PVDF - Long-Tai Qi; Lei Ma; Zhi-Xiang Xing; Ye-Cheng Liu; Wan-Zheng Lu; Han Han; Tian-Yu Zhou; Yao Wu (Journal of Fluorine Chemistry, 2025)

Combined impact of land-use/land-cover and soil property changes on soil erosion in the Yellow River Basin - Yang-Yang Wang; Xin-Xiao Yu; Deng-xing Fan; Guo-Dong Jia; Jian-Zhi Niu; Yong-Han Feng; Yu-Kun Wang (Journal of Environmental Management, 2025)

Research on intelligent diagnosis of freeze-thaw damage of concrete based on improved YOLO v8s-Segformer integrated model - Daming Luo; Jie Han; Tianze Wang; Guohua Xing; Ditao Niu (Engineering Structures, 2025)

Feasibility of one-step nanofiltration driven by ultra-low pressure (LPOSNF) for algae-laden brackish water treatment: insights from the relationship between algal physiological state and membrane fouling development - Dachao Lin; Zhongjian Zhuang; Hualong Zhao; Yi Wu; Xiaobin Ma; Zhihong Wang; Han Zhang; Lifan Liu; Xing Du (Chemical Engineering Journal, 2025)

F, O-co-regulated Ni-Co-S mesoporous heterostructured electrodes for supercapacitor applications - Xuzhao Han; Baojing Luo; Hailin Zhang; Yue Xing; Qin He; Yu Gu; Gaihua Li; Shuang Liu (Chemical Engineering Journal, 2025)

Vacancy occupation-phase transformation synergistic regulation toward high-performance lithium-sulfur batteries - Dezhi Yan; Shichao Zhang; Fangchao Han; Xianggang Guan; Shuai Yin; Puheng Yang; Xingjiang Liu; Qianfan Zhang; Yalan Xing (Chemical Engineering Journal, 2025)

“Subject-object” multi-scale regulated aluminum coordination hydrogel self-powered sensors for percussion instruments application - Xiaoyu Guan; Yanxia Zhu; Xing Li; Sai Zheng; Dongping Li; Qingxin Han; Xuechuan Wang (Chemical Engineering Journal, 2025)

The recovery mechanism of granular sludge fragmentation and re-granulation caused by long-term high-concentration organic matter erosion in the SAD process: performance, sludge evolution, and metagenomic sequencing - Peng-fei Yu; Ding Wang; Yu-bo Fu; Xing-guan Ma; Hao Zheng; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Xing Jin (Bioresource Technology, 2025)

Sustained PM2.5 decline in Shenzhen confronts emerging challenges: Strengthening regional governance and secondary aerosol mitigation - Kejin Tang; Xing Peng; Lingyan He; Yu Han; Yuqi Liu; Sizhe Liu; Tingting Yao; Xiaofeng Huang (Atmospheric Environment, 2025)

Dynamic landscape and regulation of m5C methylation in human tissues - Ke An; Ruijuan Liu; Han Yang; Luyao Feng; Xinhan Zhang; Xuran Zhang; Mingyang Hou; Jingyao Wei; Xiao Han; Boyang Shi; Huan Yao; Xing Chen; et al. (Science China Life Sciences, 2025)

4-Hydroxychalcone alleviated Angiotensin II-induced atrial fibrillation via immunoproteasome-IKK-NF-κB signaling pathway modulation - Yun-Long Zhang; Ze-Yan Xu; Yan Sun; Qian-Qiu Zhu; Sheng-Xing Tang; Qing-Hua Zhong; Xiao Han (Journal of Molecular Medicine, 2025)

Correlation between intestinal microbiota composition and growth performance in largemouth bass (Micropterus salmoides) - Dong dong Yu; You xing Xu; Xing han He; Xian ke Zhou; Dong chun Li; Shun Yang; Hui Fei (Aquaculture International, 2025)

Comparative transcriptomic analysis of gill tissues in largemouth bass (Micropterus salmoides) under low-temperature stress - Zhi-Guang Hou; Meng-Chao Xing; Li-Han Zhang; Yi-Huan Xu; Xin Zhao; Xiao-Wei Gao; Chun-Long Zhao; Cheng-Bin Wu (Aquaculture International, 2025)

Correction: Review on the Molecular Characterization of Atmospheric Organic Aerosols Using High-Resolution Orbitrap Mass Spectrometry: Techniques, Applications, and Perspectives - Yue Lin; Xin Zhang; Lijuan Li; Zhiyu Li; Rui Wang; Shuyan Xing; Yuemei Han (Aerosol Science and Engineering, 2025)

MnO2-Mediated Fluorescence Recovery for Selective Detection of Glutathione Using Orange-Emitting Carbon Quantum Dots - Yan Gao; Wen He; Hui Wang; Chaoyue Shan; Yuanyuan Du; Xing Gao; Li Han; Ruixin Zhang (Journal of Fluorescence, 2025)

Three-Dimensional Trajectory Tracking for Underactuated Quadrotor-like Autonomous Underwater Vehicles Subject to Input Saturation - Chunchun Cheng; Xing Han; Pengfei Xu; Yi Huang; Liwei Kou; Yang Ou (Journal of Marine Science and Engineering, 2025)
This paper focuses on the design of a three-dimensional trajectory tracking controller for underactuated quadrotor-like autonomous underwater vehicles (QAUVs) subject to actuator saturation. A hand position method with a signum function is proposed to handle the under-actuation of QAUVs, while avoiding trajectory tracking in the opposite direction. The dynamic surface control (DSC) technique is integrated to eliminates the complexity explosion problem of standard backstepping. An auxiliary dynamic system is employed to handle input saturation. By using Lyapunov stability theory and phase plane analysis, it is proved that the proposed control law ensures that the QAUVs converge to the desired position with arbitrarily small errors, while guaranteeing the uniform ultimate boundedness of the whole closed-loop system. Comparative simulation results verify the effectiveness of the proposed control law.

Powerful Fenton-like reactions derived from montmorillonite modulated Co single atom: Key role of heterogeneous high-valent Co (IV)-oxo - Kexin Yin; Yufeng Tang; Zisen Li; Han Zhao; Xing Xu; Qian Li; Qinyan Yue; Yue Gao; Baoyu Gao (Water Research, 2025)

Authigenic CaCO3 precipitation contributes to the stabilization of algal-derived organic carbon in karst lake - Yingxun Du; Cheng Zhao; Xuexin Han; Shilin An; Zhendu Mao; Fan Xun; Ding He; Yongdong Zhang; Muhua Feng; Wenlei Luo; Qinglong L. Wu; Peng Xing (Water Research, 2025)

Influence of iron and manganese on nitrogen biotransformation in the vadose zone of red beds following landfill leachate leakage - Zi-Liang Zhao; Hao Zhu; Xu Chen; Shi-Jie Feng; Muhammad Salam; Shan He; Yu-Ping Du; Jiong-Kuang Chen; Zhi-Xing Lan; Yong-Jie Zhou; Zhi-Yong Han (Science of The Total Environment, 2025)

Enhancing spatiotemporal coverage of satellite-derived high-resolution NO2 data with a super-resolution model - Maolin Zhang; Siwei Li; Jia Xing; Ge Song; Shuangliang Li; Jiaxin Dong; Shuxin Zheng; Ge Han; Jie Yang (Remote Sensing of Environment, 2025)

The influence of water flow disturbance form on the granulation of algae sludge: Granulation property, treatment effect and algae biological structure - Peng-fei Yu; Ao Wang; Hai-wen Sun; Ding Wang; Xing-guan Ma; Yu-jia Wang; Bo-mei Hu; Li-yao Han; Yu-bo Fu; Dian-lin Jiang; Shi-gang Tu (Journal of Water Process Engineering, 2025)

Soil water infiltration under thickening unsaturated zone: patterns, mechanisms, and quantitative formula - Kuan Liu; Jiaqi Zhai; Yong Zhao; Qingming Wang; Hao Wang; Jipeng Cao; Xudong Li; Yuansheng Pei; Leilei Min; Lichuan Wang; Haodong Deng; Xing Li; et al. (Journal of Hydrology, 2025)

Biodegradable and non-biodegradable microplastics affect greenhouse gas emissions through chemical diversity and microbial biodiversity - Ying Guo; Yajuan Tang; Yi Xing; Chen Hong; Wei Su; Wei Wen; Haobo Ya; Jiayu Chen; Han Zhang; Duo Zhang; Wenxin Li; Yixiang Chen; et al. (Journal of Hazardous Materials, 2025)

Ceramsite catalyst derived from printed circuit board sludge for catalytic ozonation treatment of coking wastewater: Performance and mechanism - Fengcheng Jiang; Xiao Xu; Xixi Feng; Mingya Wang; Chuanbing Zhang; Yuxiang Mao; Mingfei Xing; Peng Li; Qiao Han; Huiyun Pan; Jie Wang; Mingshi Wang (Journal of Hazardous Materials, 2025)

NxO emission from a pure-MBBR system: Characteristics, influencing factors, bacterial community, and metabolism pathway - Xing Fan; Jianchang Wang; Xuyi Wang; Di Wu; Haicheng Liu; Xiaolin Zhou; Shujuan Huang; Jiazhong Zhou; Wenjie Han; Xiaoyu Liu; Tang Yang; Xuejun Bi (Journal of Environmental Chemical Engineering, 2025)

Recent advances in membrane and integrated processes for the removal of nanoplastics from water and wastewater - Xiangfeng Hong; Zixi Han; Jiajian Xing; Nan Xiao; Yuesong Ding; Gaoliang Wei; Xin Wang; Haiguang Zhang (Journal of Environmental Chemical Engineering, 2025)

Heavy metals and water-soluble inorganic ions in park dust of a Chinese megacity: Machine learning-driven source assignment and control prioritization - Mingya Wang; Wanqi Ma; Shaobo Sui; Mingshi Wang; Yidong Wang; Fengcheng Jiang; Xiaoming Guo; Mingfei Xing; Qiao Han; Baoxian Jia; Fayang Guo; Huiyun Pan (Journal of Environmental Chemical Engineering, 2025)

Discovery of dietary beneficial compounds for healthy aging: From worm to human - Xianjiang Ye; Hao Wang; Yuxuan Han; Xing Fu; Jiuliang Zhang; Tao Zhang (Food Research International, 2025)

Naked mole-rat-derived high molecular weight hyaluronic acid protects against DSS-induced intestinal inflammation - Shuyin Wu; Lei Xing; Xiaolong Wu; Run Quan; Keyi Du; Jianchun Han; Huili Tong; Shuai Shi (Food Bioscience, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

Microwave−assisted synthesis of NIR electrochemiluminescence Au nanoclusters with triethanolamine−Au nanoparticles/Co3O4/NiCo2O4 as co−reactant accelerator for miRNA−107 detection - Qiao Zhang; Lei Yu; Fangfang Liu; Jimei Song; Xing Gao; Yue Sun; Yuxiao Li; Yen Leng Pak; Quanxiang Han; Zhao Wang; Yan Huang; Jibin Song (Chemical Engineering Journal, 2025)

Interinterface electron-proton co-engineering: The dual regulation of surface charge and hydroxylation promotes the efficient activation and degradation of chloroquine phosphate by monopersulfate - Zhi Song; Yeqiong Huang; Boxia Liu; Hongqiao Jiao; Yulong Ma; Lin Wang; Xiayan Zhang; Jialu Liu; Dongxu Han; Chuhan Xing; Jing Zhang (Chemical Engineering Journal, 2025)

Erlotinib-functionalized dextran derivatives enable self-assembly of redox-responsive paclitaxel dimers for lung Cancer treatment after intratracheal delivery - Lan Wu; Yingchao Han; Yuzhu Liu; Yingkai Ning; Fangyan Zuo; Xinhe Wang; Xing Zhao; Yu Zhang; Hriday Bera; Dongmei Cun; Mingshi Yang (Carbohydrate Polymers, 2025)

Harnessing nanomaterial-driven electron transfer for enhanced uranium recovery and toxicity mitigation in bioelectrochemical systems - Meng Li; Leyi Chen; Kengqiang Zhong; Haowen He; Xing Chen; Xing Lu; Chengjun Guo; Luoyi Han; Ziyin Xia; Chenxi Li; Jingyi Wang; Wei Han; et al. (Bioresource Technology, 2025)

An Automatic Route Planning Method for Digital Transmission Lines Based on Remote Sensing Spatial Model of Ground Obstacles and Ant Colony Algorithm - Guoping Wan; Xiping Han; Xing Zhao; Meng Liu (Journal of the Indian Society of Remote Sensing, 2025)

Influence of herbal extract blend supplementation on growth performance, liver and intestinal health, intestinal transcriptome, and resistance to Aeromonas veronii in Micropterus salmoides with optimized feeding intervals - Zi ying Zeng; Dong dong Yu; Yi Ting Shen; Xing han He; Shun Yang; Hui Fei (Animal Feed Science and Technology, 2025)

Exploring the Muscle Quality of Olive Flounder ( Paralichthys olivaceus ) Under Pre-Slaughter Hypoxic Stress Using a UPLC-QTOF-MS Based Metabolomics Method - Shize Han; Guodao Li; Feng Liu; Shuang Xing; Tao Yin; Dongling Li; Tanye Xu (Journal of Aquatic Food Product Technology, 2025)

Reanalysis-data-based approach to generate urban local weather data to support building energy design in a tropical climate - Xing Zheng; Naika Meili; Shuyang Li; Huanhuan Wang; Lei Xu; Zhen Han; Martín Mosteiro-Romero; Yi Wu; Da Yan; Dengkai Chi; Guanli Feng; Rudi Stouffs (Sustainable Cities and Society, 2025)

Utilization of oxided tamarind polysaccharide gum as novel selective depressant in the flotation separation of copper-lead-zinc sulfide ore - Tichen Wang; Jiushuai Deng; Hao Zhang; Dingquan Xing; Zhiguo Han; Jie Sheng; Chul B. Park (Process Safety and Environmental Protection, 2025)

Surface functionalized polystyrene nanoplastics impair nutrient assimilation from corn kernels (Zea mays L.) in a simulated human digestive tract - Chunyang Li; Heping Shang; Xiaoyan Hu; Ian Eggleston; David Julian McClements; Bin Han; Jason C. White; Chuanxin Ma; Baoshan Xing (Journal of Hazardous Materials, 2025)

Characteristics of microplastic pollution in sediments and error analysis of ecological risk assessment in Qin River, China - Yu Guo; Mingya Wang; Mingshi Wang; Fengcheng Jiang; Xiaoming Guo; Mingfei Xing; Qiao Han; Baoxian Jia; Huiyun Pan; Mengwen Chen (Journal of Hazardous Materials, 2025)

Unraveling the distinct response patterns of abundant and rare fungi to vanadium at nationwide smelting sites - Han Zhang; Baogang Zhang; Jianping Lu; Wenyue Yan; Yang Tang; Bo Jiang; Yi Xing (Journal of Hazardous Materials, 2025)

Floatable Janus nanofiber membrane driven by photothermal bubbles: A novel platform for efficient photocatalytic water purification - Kelin Wang; Guobin Li; Xiaolong Bie; Jiaqi Yu; Xing Guo; Hanxue Jia; Pengxin Liu; Weimin Kang; Zhenbang Han; Yong Liu (Journal of Cleaner Production, 2025)

Oxidative modification and structural characterization of konjac gum and its effect on the flotation separation of chalcopyrite from galena - Tichen Wang; Jiushuai Deng; Dingquan Xing; Zhiguo Han; Yue Gao; Qizheng Qin; Hao Zhang; Hongxiang Xu; Chul B. Park (Journal of Cleaner Production, 2025)

Elucidating nitrate sources in a karst watershed: Integrating isotope techniques, hydrochemical methods, and Bayesian model - Zhen Fan; Chaopu Ti; Xing Yan; Jie Qiu; Haojie Han; Ruigang Wang; Yan Liu; Rulin Xu; Caiqiong Qi; Zhangmeng He; Xiaoyuan Yan; Yongqiu Xia (Journal of Environmental Management, 2025)

High- and low-quality litter are equally important to the improvement of grassland soil multifunctionality and quality - Liheng Xing; Yu Li; Jia Zeng; Jingbo Fang; Yanfeng Niu; Yang Guo; Linshan Yuan; Chengjie Ren; Gaihe Yang; Xinhui Han (Journal of Environmental Management, 2025)

The genesis of typical geothermal water in Shigatse based on hydrochemical characteristics and isotopes - Yadong Zheng; DaWa Nan; Zhao Liu; Ciren Pubu; Mengmeng Zhu; Haihua Zhao; Yifei Xing; Sihang Han; Qifeng Zeng; Linjie Zhang (Geothermics, 2025)

Phylogenetic distance drives rare cooperation in a competition-dominated cadmium stress environment - Fang Ma; Yi Jiang; Yanan Han; Yonghui Xing; Song Liu; Shuxin Tan; Qiaoyun Huang; Rasha M. El-Meihy; Wenli Chen (Environmental Research, 2025)

Enhanced mechanical properties and tunable degradation of shape memory polyurethanes through oligo(glycolic acid) chain extender design - Han Wu; Wenjie Pan; Xing He; Zhenbo Ning; Ni Jiang; Zhihua Gan (Chemical Engineering Journal, 2025)

Heteroatom- and bonded tailored Schottky barrier in Ti₃C₂ MXene/carbon nitride heterojunctions toward efficient photocatalysis - Weinan Xing; Huage Lin; Weifan Shao; Ning Jian; Teng Liu; Shanpeng Wen; Jiangang Han; Guangyu Wu (Chemical Engineering Journal, 2025)

Extracellular vesicles in antimicrobial therapy: Advances, challenges and perspectives - Rongjia Han; Weiwei Wang; Yaxin Zhou; Bing Li; Rongbin Hu; Jingru Zuo; Jiabao Xing; Hongxing Zhang; Huan Huang; Yubin Bai; Jiyu Zhang (Chemical Engineering Journal, 2025)

Formation of early continental crust by remelting of hydrothermally altered oceanic crust: Evidence from potassium and oxygen isotopes - Shao-Bing Zhang; Liang Zhang; Xing-Yu Yao; Zhen-Xin Li; Xiaoqiang Li; Guilin Han; Yong-Fei Zheng (Chemical Geology, 2025)

Microbial inoculation simultaneously promotes humification and the removal of antibiotic resistance genes during kitchen waste composting - Bingbing Xing; Hao Zhu; Han Xiao; Chengyu Ma; Weijie Zhou; Wei Gao; Qilin Zhu; Huanyu Bao; Yunze Ruan (Bioresource Technology Reports, 2025)

Rarer fungal taxa contribute to pathotrophic and deterministic assemblages in wild spotted seal faeces - Jiashen Tian; Zhichuang Lu; Zhen Wang; Jing Du; Yankuo Xing; Xianggang Gao; Zhongren Kong; Jiabo Han (Marine Biology, 2025)

Cucurbitacin B alleviates DSS-induced experimental colitis by targeting ZNF70 to suppress the NLRP3/STAT3 signaling axis - Shen Cao; Yuhan Wang; Yi Tai; Jing Han; Yanjin Zheng; Can Wang; Hong Xiang Zuo; Ming Yue Li; Yue Xing; Xuejun Jin; Juan Ma (Inflammopharmacology, 2025)

Divergent mechanisms of rhizosphere and non-rhizosphere soil organic carbon sequestration under precipitation variability: Evidence from microbial life-history strategies - Jia Zeng; Liheng Xing; Yu Li; Xing Wang; Qi Zhang; Hanyu Liu; Yingyi Liu; Yongzhong Feng; Xiaojiao Wang; Chengjie Ren; Gaihe Yang; Xinhui Han (Applied Soil Ecology, 2025)

Multi-Modal Time-Frequency Image Fusion for Weak Target Detection on Sea Surface - Han Wu; Hongyan Xing; Mengjie Li; Chenyu Hang (Journal of Marine Science and Engineering, 2025)
Aiming at the problem of harrowing target feature extraction for one-dimensional radar signals in the strong sea clutter background, this paper proposes a weak target detection method based on the combination of multi-modal time-frequency map fusion and deep learning in the sea clutter background. The one-dimensional signal is converted into three gray-scale maps with complementary characteristics by three signal processing methods: normalized continuous wavelet transform, Normalized Smooth Pseudo Wigner-Ville Distribution, and recurrence plot; the resulting two-dimensional grayscale maps are adaptively mapped to the R, G, and B channels through an adaptive weighting matrix for feature fusion, ultimately generating a fused color image. Subsequently, an improved multi-modal EfficientNetV2s classification framework was constructed, wherein the decision threshold of the Softmax layer was optimized to achieve controllable false alarm rates for weak signal detection. Experiments are carried out on the IPIX dataset and the China Yantai dataset, and the proposed method achieves certain improvement in detection performance compared with existing detection methods.

Nitrite and sulfide stress induces hepatopancreatic oxidative stress, lipid metabolism disorders, ferroptosis and apoptosis in the Chinese mitten crab, Eriocheir sinensis - Yi-Fu Xing; Yi-Fan Feng; Jian Tian; Qi-Bin Zhu; Cui Han; Xiao-Jie Liu; Jiang-Hua Yang; Jia-Xin Yang (Aquaculture, 2025)

Selective electroreduction of carbon dioxide to ethylene over stable iodide-induced asymmetric copper sites within a metal-organic polyhedron - Yaguang Peng; Yinlin Chen; Zi Wang; Yaoyu Yin; Jiangnan Li; Huanyan Liu; Jiapeng Jiao; Wenling Zhao; Ran Duan; Pei Zhang; Jiahao Yang; Hengan Wang; et al. (Science Bulletin, 2025)

Study on the performance regulation mechanism of in-situ Bi doping on the degradation of tetracycline by Prussian blue analogue activated PMS catalytic system - Jing Zhang; Zhi Song; Boxia Liu; Dongxu Han; Xiayan Zhang; Jialu Liu; Yeqiong Huang; Chuhan Xing (Journal of Water Process Engineering, 2025)

Identification and functional characterization of a novel CaSrpA enzyme for selenite reduction and selenium nanoparticle formation - Xiaoxiao Hou; Jidong Gu; Jicong Chen; Habib Ullah; Tursunay Mamtimin; Xing Wang; Xiaoqin Li; Yuchao Jiang; Jingwen Fan; Huawen Han; Xiangkai Li (Journal of Hazardous Materials, 2025)

Sex-and stage-specific effect of prenatal exposure to organophosphate esters with children's physical growth patterns and adiposity rebound timing: Modification by breastfeeding - Xing Wang; Juan Tong; Han Li; Mengjuan Lu; Yuan Liu; Hong Gan; Yifan Wang; Menglong Geng; Xuejiao Qie; Xiulong Wu; Hui Gao; Beibei Zhu; et al. (Journal of Hazardous Materials, 2025)

Dynamic microbial community assembly and molecular ecological network responses in biological activated carbon filters: effects of algal organic matter exposure and empty bed contact time - Fei Han; Zhiwei Zhou; Chaoran Liu; Zedong Lu; Liping Tian; Xing Li (Environmental Research, 2025)

Bioinspired trilayer poly(ε-caprolactone) scaffolds with native-like structures and mechanical property for heart valve constructs - Zeping Zhang; Rizheng Han; Yueen Liu; Xinqi Yu; Guixue Wang; Yun Bai; Rui Yang; Tao Jin; Xing Zhang (Chemical Engineering Journal, 2025)

Analyzing Landscape Preference in Under-Bridge Spaces Based on Different Travel Modes: A Study on Urban Viaduct Landscapes in China - Xing Huang; Chenping Han; Liang Gao; Jingjing Zhao; Tangming Bu (International Journal of Environmental Research, 2025)

Calcium-O-Sr-Nd isotope evidence for the origin of REE-bearing carbonatite from metasomatized lithospheric mantle without recycled carbonate - Xing-Hui Li; Ming-Cai Xie; Kui-Feng Yang; Kan Li; Chun-Ming Han; Hai-Dong She; Gai-Zhong Liang; Xiao-Chun Li; Hong-Rui Fan (Contributions to Mineralogy and Petrology, 2025)

Efficient antibiotic tetracycline degradation and toxicity abatement via the perovskite-type CaFexNi1-xO3 assisted heterogeneous electro-Fenton system - Yuling Liang; Aochen Feng; Naif Abdullah Al-Dhabi; Jing Zhang; Wenle Xing; Tao Chen; Yuxuan Han; Guangming Zeng; Lin Tang; Wangwang Tang (Water Research, 2025)

Luteolin-7-O-glucuronide alleviates doxorubicin-induced cardiotoxicity by inhibiting PPAR-mediated ferroptosis - Lishuang Cui; Qing Xia; Yongcheng Wang; Cong Han; Xiaohan Zang; Lijuan Zhang; Jianguo Xing; Ruifang Zheng; Yun Zhang (Toxicology and Applied Pharmacology, 2025)

A heterogeneous sparsity knowledge guided evolutionary algorithm for sparse large-scale multiobjective optimization - Jing Jiang; Huoyuan Wang; Pingping Tong; Juanjuan Hong; Zhe Liu; Xing Zhuang; Benyue Su; Fei Han (Swarm and Evolutionary Computation, 2025)

Simultaneous high molecular weight PAHs degradation and chromate and arsenite detoxification by Altererythrobacter sp. H2 - Qun Han; Mei-Ling Yang; Ze-Shen Liu; Ying-Hao Zhao; Xue-Hui Liu; Guo-Min Ai; Wei-Hong Qin; Xing-Yu Liu; De-Feng Li (Journal of Hazardous Materials, 2025)

Structure-guided engineering of a Rieske-type aromatic dioxygenase for enhanced consumption of 3-phenylpropionic acid in Escherichia coli - Wenxue Jiang; Miao Wu; Zhou Gong; Linhua Han; Xiaoqi Cheng; Xiaoqin Tang; Xiaolong Yu; Xu Dong; Yibin Cheng; Lixin Ma; Qiong Xing (Journal of Hazardous Materials, 2025)

Constructing built-in electric fields in bimetallic selenide heterojunctions to bidirectional catalyze polysulfide conversion for flexible lithium-sulfur batteries - Fangchao Han; Shichao Zhang; Dezhi Yan; Yalan Xing; Jun Xia; Xianggang Guan; Qiang Lu; Puheng Yang; Xiaomeng Wu; Qianfan Zhang (Chemical Engineering Journal, 2025)

Corrigendum to “Neovascularization-directed bionic eye drops for noninvasive renovation of age-related macular degeneration” [Chem. Eng. J. 450 (2022) 138291] - Meixin Ran; Yaxin Deng; Jiaqi Yan; Anan Zhang; Ying Wei; Xiaowen Li; Haibing He; Jingxin Gou; Tian Yin; Xing Tang; Jun Kong; Han Zhang; et al. (Chemical Engineering Journal, 2025)

Trace element and sulfur isotope study of sulfide chimneys from the mafic-hosted Daxi Vent Field: Implications on the genesis of seafloor massive sulfide deposit at a segment end - Yejian Wang; Ming Yang; Xiqiu Han; Sven Petersen; Yiyang Cai; Xinkai Hu; Anxia Chen; Zhongyan Qiu; Xing Yu; Hang Hu; Matthias Frische; Honglin Li (Chemical Geology, 2025)

Ash thermomechanical properties and combustion characteristics during Co-combustion of anthracite and biomass for CFB combustors - Shangkun Quan; Yijie Zeng; Yukun Wu; Ryang-Gyoon Kim; Zhouhang Li; Yong Han; Junjie Li; Chung-hwan Jeon; Xing Zhu; Hua Wang; Dongfang Li (Biomass and Bioenergy, 2025)

Bacteria in the Phylum Bacillota Degrade Nicotine Through the Variant of Pyridine and Pyrrolidine Pathway - Xiu-Ming Liu; Xuan Hai; Cong-Jian Li; Yu-Fan Han; Xing Chen; Yu-Jin Fan; Jian Wu; En-Min Zhou; Yuan-Dong Li; Ling-Ling Yang; Yan-Qing Duan; Xiao-Yang Zhi (Current Microbiology, 2025)

Review on the Molecular Characterization of Atmospheric Organic Aerosols Using High-Resolution Orbitrap Mass Spectrometry: Techniques, Applications, and Perspectives - Yue Lin; Xin Zhang; Lijuan Li; Zhiyu Li; Rui Wang; Shuyan Xing; Yuemei Han (Aerosol Science and Engineering, 2025)

The mRNA vaccine expressing fused structural protein of PRRSV protects piglets against PRRSV challenge - Chunxiao Mou; Xing Zhao; Chen Zhuo; Qing He; Mengwei Xu; Kaichuang Shi; Tiyun Han; Shi Xu; Zhenhai Chen (Veterinary Microbiology, 2025)

The effect of algal organic matter on advanced drinking water treatment by biological activated carbon filters with different media types and reduced empty bed contact time - Fei Han; Xing Li; Liping Tian; Kehua Fang; Zedong Lu; Zhiwei Zhou (Journal of Water Process Engineering, 2025)

Quantile regression reveals phosphorous overwhelms nitrogen in controlling high chlorophyll-a concentration in freshwater lakes - Haojie Han; Xing Yan; Xiaohan Li; Xuemei Zhao; Jie Qiu; Zelin Huang; Xiaoyuan Yan; Yongqiu Xia (Journal of Hydrology, 2025)

Unexpected Sr enrichment in karst lacustrine sediments associated with warming and rapid socio-economic development - Xiang Gu; Peng Xing; Cheng Zhao; Xiaotong Han; Di Xu; Qinglong L. Wu; Fengchang Wu (Journal of Cleaner Production, 2025)

Prediction of enhanced coagulation with varied pre-oxidations for seasonal variations of cyanobacteria-dominated algae-laden water quality - Luming Ding; Zhiwei Zhou; Yanling Yang; Yuankun Liu; Fei Han; Wenqing Yu; Kaidi Xin; Chunqing Liu; Xing Li; Jiawei Ren (Journal of Environmental Management, 2025)

Coupling anaerobic digestion with ammonification for the treatment of hydrothermal carbonization liquid: An innovative approach - Ying Han; Yunxin Xing; Han Wang; Qun Yan (Journal of Environmental Chemical Engineering, 2025)

Effects of different cooking times on the sensory evaluation and flavor characteristics of soy sauce - Xing Gao; Xiaomo Han; Mingguang Yu; Yuan Tang; Huanlu Song; Qi Meng; Rifeng Chen; Jiang Yu; Ping Yang; Zhili Yu (International Journal of Gastronomy and Food Science, 2025)

Effect and mechanism of calcium ions on the astringency in green tea infusion and epigallocatechin gallate solution: An in vitro oral soft tribology study - Long-Jie Xu; Qing-Qing Cao; Si-Han Deng; Wen-Jiang Dong; Qian Zou; Yong-Quan Xu; Xing-Hui Li (Food Chemistry, 2025)

A deep learning-based study on visual quality assessment of commercial renovation of Chinese traditional building facades - Jingjing Zhao; Chenping Han; Yijing Wu; Changsheng Xu; Xing Huang; Xiwu Qi; Yangming Qi; Liang Gao (Environmental Impact Assessment Review, 2025)

Multifunctional and structural magnetic nanobranches for high-efficiency biological detection - Wenxu Hu; Yongliang Dong; Tianxin Ge; Si-Yang Liu; Jianhe Guo; Liqiu Wang; Changqing Yi; Xing Han; Zong Dai (Chemical Engineering Journal, 2025)

Rational metabolic engineering of Escherichia coli for the industrial-scale production of l-phenylalanine - Minliang Chen; Chao Han; Peng Zhou; Run Shi; Zhiwei Xing; Qianqian Chen; Gou-an Xie; Rufei Xie; Wei Tan; Hengyu Liang (Bioresource Technology, 2025)

Gold mineralization in the hydrothermal field at the termination of a detachment fault: A case study of the Tianxiu Vent Field - Ming Yang; Yejian Wang; Sven Petersen; Zhongyan Qiu; Honglin Li; Peng Zhou; Yiyang Cai; Xing Yu; Matthias Frische; Jiqiang Liu; Xiqiu Han (Mineralium Deposita, 2025)

Cottonseed protein concentrate as fish meal substitution in fish diet: a review - You Xing Xu; Zhi Li Ding; Xing Han He; Hui Fei (Fish Physiology and Biochemistry, 2025)

Identification of Age-Related Characteristic Genes Involved in Severe COVID-19 Infection Among Elderly Patients Using Machine Learning and Immune Cell Infiltration Analysis - Huan Li; Jin Zhao; Yan Xing; Jia Chen; Ziying Wen; Rui Ma; Fengxia Han; Boyong Huang; Hao Wang; Cui Li; Yang Chen; Xiaoxuan Ning (Biochemical Genetics, 2025)

Sources, transport and fate of polycyclic aromatic hydrocarbons (PAHs) in a typical river-estuary system in the North China: From a new perspective of PAHs loading - Ke Liu; Xiaomeng Wang; Haibo Zhang; Yawen Wei; Gang Zhao; Xing Liu; Hao Cui; Jianbo Han (Marine Pollution Bulletin, 2025)

Corrigendum to “African swine fever virus maintains de novo global cellular protein synthesis and inhibits stress granules formation via dephosphorylating eIF2α” [Vet. Microbiol. 290 (2024) 109988] - Han Gao; Xiaopeng Gao; Xing Liu; Yizhuo Luo; Jianhao Zhong; Jing Liu; Luling Yan; Heng Wang; Lang Gong; Guihong Zhang; Zezhong Zheng; Yankuo Sun (Veterinary Microbiology, 2025)

A study on the flow and noise of a pump-jet propulsors in the fully appended SUBOFF hull wake - Han Li; Xinming Li; Xing He; Bo Lu; Qiaogao Huang; Guang Pan; Pengcheng Ye (Ocean Engineering, 2025)

Intergenerational transfer of micro(nano)plastics in different organisms - Yanhui Dai; Rui Han; Zhiming Yao; Han Yan; Zhuomiao Liu; Xia Liu; Tongtao Yue; Jian Zhao; Zhenyu Wang; Baoshan Xing (Journal of Hazardous Materials, 2025)

Significant differences in optimal riparian buffer zone on water quality between different segments within the same river - Haojie Han; Xing Yan; Xiaohan Li; Zelin Huang; Xiaoyuan Yan; Yongqiu Xia (Journal of Environmental Management, 2025)

Regulation CN reduction of CO2 products selectivity by adjusting the number of V sites and mechanism exploration - Zhi Zhu; Xiaohan Xing; Qi Qi; Hongping Li; Donglai Han; Xianghai Song; Xu Tang; Yun Hau Ng; Pengwei Huo (Fuel, 2025)

Efficient encapsulation of organic phase change materials through Diels-Alder reaction and in situ assembly for excellent photothermal conversion and energy storage - Guangpeng Luo; Haihui Liu; Na Han; Xing-xiang Zhang (Chemical Engineering Journal, 2025)

Two-way coupled numerical simulation between outdoor thermal environment and PM2.5 in urban blocks - Meilin Wang; Hang Ma; Xing Zheng; Chun Han; Pengyuan Shen (Building and Environment, 2025)

Integrating spatial heterogeneity and speciation dynamics in source apportionment of toxic metal(loid)s at an abandoned hydrometallurgical zinc smelting site - Hengbo Liu; Xu Cao; Zhiyue Gao; Yi Wu; Yongfang Sa; Qinying Yao; Jianzhou Han; Jinyan Yang; Jiang Hou; Tao Xing (Environmental Geochemistry and Health, 2025)

Risks of respiratory and circulatory system diseases induced by exposure to PM2.5 in high humidity and low solar radiation environments: disease types, genes, and functions - Xiaomeng Li; Liru Zhang; Zhengliang Zhang; Xuan Li; Jingli Qian; Jiawei Zhou; Hanxiong Che; Yan Han; Xin Qi; Fumo Yang; Yu Huang; Chao Peng; et al. (Environmental Geochemistry and Health, 2025)

Spatial adaptations in hospitality amid COVID-19: A case study of Xiamen's B&B sector - Juan Lin; Han Li; Shuyu Xing; Weiye Xiao (Applied Geography, 2025)

Comprehensive wheat lodging detection under different UAV heights using machine/deep learning models - Jianing Long; Zhao Zhang; Qu Zhang; Xiaohui Zhao; C. Igathinathane; Jianfei Xing; Chayan Kumer Saha; Wenyi Sheng; Han Li; Man Zhang (Computers and Electronics in Agriculture, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Using waste to treat waste: Coupling of advanced reduction processes and anaerobic fermentation - Xing-Yuan Chen; Yun Niu; Lin Pan; Han-Lin Gu; Wei Gao; Zi-Yi Mu; Li-Li Hu; Wei Zhang (Journal of Water Process Engineering, 2025)

A novel gravity-driven fixed-bed ceramic membrane filtration (GDFBCM) with critical PAC-MnOx-ceramsite filters for simultaneously removing hazardous manganese and ammonia from groundwater - Dachao Lin; Zhitian Peng; Xiaopeng Zhang; Zhihong Wang; Yi Wu; Xiaobin Ma; Han Zhang; Wei Song; Lifan Liu; Jinxu Nie; Xing Du (Journal of Hazardous Materials, 2025)

The complex underlying surface underestimates the carbon sink capacity of reed salt marsh wetlands: A case study from the Liaohe River Estuary, China - Cheng Hao; Xing Qinghui; Chen Hong; Wang Ziyu; Han Jianbo; Ming Yue (Journal of Environmental Management, 2025)

High sediment load weakens the effects of nitrogen nutrients on zooplankton diversity in a continental-scale river - Gang Li; Baozhu Pan; Yue Chen; Xu Han; Xing Liu; Yitong Ding; Zijie Yang (Journal of Environmental Management, 2025)

Impact of algal organic matter on the performance and microbial community of biologically-active filtration systems - Zhiwei Zhou; Luming Ding; Xinwei Zuo; Fei Han; Xing Li; Jiawei Ren; Zedong Lu (Journal of Environmental Chemical Engineering, 2025)

Investigation on the synergistic effects and thermokinetic analyses during co-combustion of corn stalk and polyethylene plastic: Effect of heating rate and placement method - Mengjie Liu; Bin Han; Jin Bai; Jiayao Ru; Xuetao Wang; Lili Xing; Haojie Li; Siyu Lv; Aopeng Gao; Yiming Wang; Lingxue Kong; Zongqing Bai; et al. (Fuel, 2025)

Characterization of flavor profiles of wines produced with Coniella vitis-infected grapes by GC–MS, HPLC, and sensory analysis - Xing Han; Yanfeng Wei; Lifang Yuan; Xiangtian Yin; Yao Liu; Chundong Wang; Xilong Jiang; Tinggang Li; Qibao Liu (Food Chemistry, 2025)

Hierarchical dandelion-like superhydrophobic surfaces with excellent stability and photothermal performance for efficient anti-/deicing - Chengjin Zhang; Ke Pei; Jing Zhao; Yongshen Zhou; Shouzi Zhang; Xing Han; Zhiguang Guo (Chemical Engineering Journal, 2025)

Reprogramming miR-146b-snphb Signaling Activates Axonal Mitochondrial Transport in the Zebrafish M-cell and Facilitates Axon Regeneration After Injury - Xin-Liang Wang; Zong-Yi Wang; Xing-Han Chen; Yuan Cai; Bing Hu (Neuroscience Bulletin, 2025)

Microrna363-5p targets thrombospondin3 to regulate pathological cardiac remodeling - Yu-kun Ma; Xin-yi Han; Shu-huai Zan; Hui-ting Liu; Xue-yan Zhou; Dan-xue Zhao; Rui Xing; Peng Zhao (Molecular and Cellular Biochemistry, 2025)

Reversal of Extreme Drought-Induced Plant Nitrogen and Phosphorus Imbalances in Grassland - Xiao-Sa Liang; Zheng-Wen Wang; Wentao Luo; Lin Song; Wang Ma; Niwu Te; Qiang Yu; Xing-Guo Han; Xiao-Tao Lü (Ecosystems, 2025)

The different pathways of microbial regulation of organic carbon turnover in the topsoil and subsoil of coastal saline soil after long-term stubble return and subsoiling - Xunya Su; Le Zhang; Hao Meng; Jiaxue Zhao; Han Wang; Lunxiao Shang; Qiyuan Guo; Yupeng Xing; Xianliang Song; Xuezhen Sun; Xiaopei Zhang; Xiaoli Tian; et al. (Applied Soil Ecology, 2025)

Study on synergistic change strategies of leaf functional traits of common garden plants along the urban–rural gradient—Suzhou, China - Qilin Zhong; Hongyun Zhang; Xing Zhang; Fei Gao; Hui Han (Environmental Monitoring and Assessment, 2025)

Establishing electro-functionalized gravity-driven ceramic membrane filtration (EGDCM) for decentralized treatment of algae-laden brackish water: Comparison of in-situ electro-oxidation and ex-situ electro-coagulation - Dachao Lin; Xinxu Shen; Caiwei Tan; Han Zhang; Rui Chen; Xing Du; Heng Liang (Water Research, 2025)

NAT10 primes a post-transcriptional repertoire essential for the maintenance of spermatogonial homeostasis - Xiaoli Zhu; Caoling Xu; Xue Jiang; Jiaqi Zou; Wenqing Li; Xuemei Xing; Xiaoxiao Gao; Jiao Lei; Fei Meng; Xin Wang; Yuzhang Zhu; Yu Cheng; et al. (Science Bulletin, 2025)

Temperature-dependent pathways in carbon dioxide electroreduction - Shiqiang Liu; Yaoyu Yin; Jiahao Yang; Wenling Zhao; Meng Zhou; Huisheng Qin; Jiapeng Jiao; Yiyong Wang; Heng’an Wang; Xing Tong; Yi Xu; Xiaofu Sun; et al. (Science Bulletin, 2025)

Molecular identification of three cytochrome P450 genes and their potential roles in insecticides tolerance in Grapholita molesta (Busck) - Hui Han; Ming-Gao Li; Kai-Yang Xing; Qi Wang; Jun Hu; Zhi-Guo Zhao; Qin Yu; Rui-Yan Ma; Ling-Ling Gao; Yan-Qiong Guo (Pesticide Biochemistry and Physiology, 2025)

Targeted isolation of lignans and triterpenoids from kadsura coccinea by molecular networking and anti-RA-FLS activity - Shi-qi Liu; Qing-ling Xie; Ya-si Deng; Ling Liang; Han-wen Yuan; Bin Li; Huang-he Yu; Xing Tian; Yi-xing Qiu; Guy Paulin Kemayou Mouthe; Nuzhat Shehla; Ye Zhang; et al. (Phytochemistry, 2025)

Numerical analysis of the effect of a breaking-vortex baffle around appendage on the submarine flow field and flow noise - Xing He; Lei Wang; Qiaogao Huang; Han Li; Jing Liu (Ocean Engineering, 2025)

Ni-Co synergistic regulation of catalyst surface charge density for efficient DNA base degradation in water - Jialu Liu; Yeqiong Huang; Xinyi Song; Zhi Song; Xiayan Zhang; Dongxu Han; Chuhan Xing; Boxia Liu (Journal of Water Process Engineering, 2025)

Optimizing fertilization rate can maintain the greenhouse gas mitigation effect of no-tillage: A global-scale meta-analysis - Jia Zeng; Xing Wang; Yu Li; Liheng Xing; Xiangyang Li; Qi Zhang; Hanyu Liu; Yingyi Liu; Weichao Liu; Yongzhong Feng; Xiaojiao Wang; Chengjie Ren; et al. (Field Crops Research, 2025)

Microporous carbon derived from waste plastics for efficient adsorption of tetracycline: Adsorption mechanism and application potentials - Shiyu Bian; Zhuoyu Cai; Weinan Xing; Chunyu Zhao; Yuwei Pan; Jiangang Han; Guangyu Wu; Yudong Huang (Environmental Research, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Comprehensive analysis of spatiotemporal heterogeneity reveals the effects of physicochemical and biological factors on temperature rise during the Moutai-flavor Baijiu stacking fermentation process - Yuanbu Li; Xing Qin; Xianglian Zeng; Menglin She; Liangqiang Chen; Jianjun Lu; Ying Han; Fan Yang; Huabin Tu; Hai Du; Yan Xu (Chemical Engineering Journal, 2025)

P-d orbital hybridization and lattice strain induced by B,Co-co-doped Cu promote the electrocatalytic nitrate reduction to ammonia - Qianling Wei; Yuexuan He; Guopeng Ding; Jiuhui Han; Zixuan Feng; Xue Chen; Zhili Wang; Xing-You Lang; Qing Jiang (Chemical Engineering Journal, 2025)

Epidemiological investigation and analysis of human papillomavirus infection and cataract development - Jing-Xing Li; Shu-Bai Hsu; Yu-Han Huang; Fuu-Jen Tsai (VirusDisease, 2025)

A wild-allele GsPP2C-51-a1 enhances tolerance to drought stress in soybean and Arabidopsis - Cheng Liu; Xianlian Chen; Wei Han; Xiaoshuai Hao; Liang Qin; Wei Luo; Lizhi Zhao; Ning Li; Lei Sun; Jiaoping Zhang; Guangnan Xing; Jianbo He; et al. (Theoretical and Applied Genetics, 2025)

Synthesis and anti-inflammatory activity of chromone-sulfonamide derivatives as COXs/iNOS dual-target inhibitors - Meng Qin; Tao Xing; Mengdi Zhang; Jiatong Han; Shuyan Yu; Jianping Chen; Yuheng Ma (Medicinal Chemistry Research, 2025)

Procyanidins-Mediated Biological Denitrification Inhibition Reduces Fertilizer-Induced N2O Emissions in Acidic Tea Plantation Soils - Xing Han; Haiyang Yu; Miaoling Meng; Chaorong Ge; Ningguo Zheng; Huaiying Yao (Journal of Soil Science and Plant Nutrition, 2025)

Recursive data reconciliation with nonlinear characteristic constraints for typical heat exchangers in nuclear power plant - Tianyang Xing; Mudi Jiang; Xiaoliang Zhu; Bin Han; Jianqun Xu; Xinfei Yang; Mengmeng Ji (Annals of Nuclear Energy, 2025)

Dominant grasses buffer the fluctuation of plant productivity to long-term grazing pressure in a desert steppe grassland - Feng Zhang; Shaoyu Li; Jiahua Zheng; Bin Zhang; Jing Wang; Jirong Qiao; Jiaqing Xing; Zhongwu Wang; Zhiguo Li; Guodong Han; Mengli Zhao (Agricultural and Forest Meteorology, 2025)

Multiple Nutrient Additions Homogenize Multidimensional Plant Stoichiometry in a Meadow Steppe - Yang Peng; Jian‐Xia Yang; Eric W. Seabloom; Jordi Sardans; Josep Peñuelas; Hai‐Yang Zhang; Cun‐Zheng Wei; Xing‐Guo Han (Global Change Biology, 2025)
Human activities are altering terrestrial ecosystem biogeochemistry globally by augmenting the availability of multiple biologically essential nutrients, thereby potentially altering plant internal concentrations (i.e., stoichiometry) across a diverse array of elements. These shifts in plant nutrient concentrations may subsequently impact crucial ecosystem processes, including litter decomposition, herbivory by insects and large animals, and ecosystem productivity. However, most work on the alteration of plant stoichiometry has focused on a few macronutrients (e.g., nitrogen or phosphorus), despite the potential importance of many other elements. In this study, we conducted a comprehensive field experiment in the Inner Mongolia Steppe, manipulating eight distinct nutrients to examine their effects on both soil and plant tissue concentrations. Our findings reveal that adding most nutrients increased their corresponding available contents in the soil. In most cases, the addition of nutrients also increased their corresponding concentrations in plant tissues at both species and community levels. Besides, multiple nutrient additions had greater effects on soil available nutrient contents than on plant internal nutrient concentrations. Notably, the concurrent addition of multiple nutrients led to a significant homogenization of plant stoichiometry among different species within the same community. This homogenization might influence interspecific interactions and coexistence within grassland ecosystems. Our findings advanced our comprehension of how anthropogenic nutrient enrichment may simplify plant nutrient profiles, thereby influencing grassland biodiversity and ecosystem functionality.

Warming effects on pelagic carbon metabolism is related to substrate composition and bacterioplankton community history - Zhendu Mao; Yixuan Han; Fan Xun; Shilin An; Biao Li; Yujing Wang; He Chen; Qinglong L. Wu; Peng Xing (Water Research, 2025)

Deciphering the driving mechanism of microbial community for rapid stabilization and lignocellulose degradation during waste semi-aerobic bioreactor landfilling with multifunctional microbial inoculum - Minghui Wu; Yiqian Tao; Qilu Zeng; Zhengyong Pan; Han Zhang; Zhiyan Yin; Wenjian Li; Yanxin Liu; Xing Li; Zhongping Qiu (Waste Management, 2025)

A novel cross-priming amplification technique combined with lateral flow strips for rapid and visual detection of zoonotic Toxoplasma gondii - Yao Liang; Yuan-Hui He; Shu-Feng Yang; Shi-Chen Xie; Yi-Han Lv; Wei Cong; Hany M. Elsheikha; Xing-Quan Zhu (Veterinary Parasitology, 2025)

Cadmium induces spontaneous abortion by impairing endometrial stromal cell decidualization - Xue-Ke Zhang; Xuan Li; Xing-Xing Han; Dong-Ying Sun; Yu-Qin Wang; Zi-Zhuo Cao; Lu Liu; Zi-Han Meng; Guo-Jing Li; Yu-Jie Dong; Dan-Yang Li; Xiao-Qing Peng; et al. (Toxicology, 2025)

C-C motif chemokine ligand 5 contributes to radon exposure-induced lung injury by recruiting dendritic cells to activate effector T helper cells - Liping Ma; Yilong Wang; Junwang Guo; Xuewen Zhang; Shuang Xing; Benbo Liu; Guo Chen; Xu Wang; Jiyao Hu; Ge Li; Gencheng Han; Maoxiang Zhu (Toxicology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Magma evolution along detachment fault-affected ridge segments: Petrology and geochemistry of MORBs from the Tianxiu segment, Carlsberg Ridge - Hang Hu; Xing Yu; Xiqiu Han; Jiqiang Liu; Yejian Wang; Zhongyan Qiu; Tong Zong; Honglin Li; Xucheng Xu; Hu He (Lithos, 2025)

The influence of metal organic frameworks(MOFs) after tannic acid etching on the performance and structure of loose nanofiltration membranes for enhanced dyes/salts selective separation - Shenghui Liu; Alhassan Martha Ndago; Biqin Chen; Shangsong Han; Weibin Chen; Jinke Zhang; Xing Zheng (Journal of Water Process Engineering, 2025)

Attributes of karst lakes in sustaining net autotrophy and carbon sink effects - Yongqiang Han; Haibo He; Zaihua Liu; Chaowei Lai; Zhen Ma; Xing Liu; Dong Li; Mingyu Shao; Wenfang Cao; Hang Li; Pengyun Hao; Yuhao Zhao; et al. (Journal of Hydrology, 2025)

Enhanced biological pump and carbonate pump synergy: The primary pathway for phosphorus clearance in the century-long dynamics of a karst lake - Haibo He; Zaihua Liu; Jingan Chen; Dongli Li; Yuyouting Wang; Yongqiang Han; Xing Liu; Hailong Sun; Quan Chen; Wenfang Cao (Global and Planetary Change, 2025)

Evaluating hydraulic permeability of hydrate-bearing porous media based on broadband electrical parameters: A numerical study - Lanchang Xing; Shuo Wang; Xiaofei Wu; Liyun Lao; Seyed Milad Salehi; Wei Wei; Weifeng Han; Donghui Xing; Xinmin Ge (Gas Science and Engineering, 2025)

Engineering noble metal-free nickel catalysts for highly efficient liquid fuel production from waste polyolefins under mild conditions - Xinlei Han; Jiuxuan Zhang; Zhengyan Qu; Tuo Ji; Feng Zeng; Hong Jiang; Jun Huang; Zhenchen Tang; Weihong Xing; Rizhi Chen (Fuel, 2025)

Single-cell transcriptome sequencing analysis of physiological and immune profiling of crucian carp (Carassius auratus) gills - Zhi-Guang Hou; Meng-Chao Xing; Jia-Xing Luo; Yi-Huan Xu; Li-Han Zhang; Xiao-Wei Gao; Jiang-Jiang Wang; Fazhan Hanafiah; Waiho Khor; Xin Hao; Xin Zhao; Cheng-Bin Wu (Fish & Shellfish Immunology, 2025)

Achieving efficient multifunctional platform utilizing sugarcane for water-electricity cogeneration and dyes reduction - Haitao Li; Qifan Qian; Xuan Li; Hui Cheng; Bingquan Wu; Xing Yi Ling; Jie Han (Chemical Engineering Journal, 2025)

Flexible and free-standing porous electrode fabricated with sacrificial polymeric chaperone PAN/TPU binder and design of flexible energy storage device - Xianggang Guan; Zhe Zhang; Shichao Zhang; Ziwei Wei; Fangchao Han; Jingli Guan; Shuai Yin; Yalan Xing; Puheng Yang; Xiaomeng Wu (Chemical Engineering Journal, 2025)

Enhancement of the yield of poly (ethylene terephthalate) hydrolase production using cell membrane protection strategy - Xiao-Qian Chen; De-Ming Rao; Xing-Yu Zhou; Yang Li; Xiao-min Zhao; De-min Kong; Han Xu; Chu-Qi Feng; Lei Wang; Ling-Qia Su; Zheng-Fei Yan; Jing Wu (Bioresource Technology, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Deciphering the landscape and evolutionary trajectory of NLR immune receptors in Dioscorea alata - Yue Wang; Xing-Yu Feng; Wen-Qiang Wu; Ming-Han Li; Sai-Xi Li; Zhen Zeng; Zhu-Qing Shao; Yan-Mei Zhang (Plant Molecular Biology, 2025)

Characteristics of Tylvalosin Tartrate Enteric Amorphous Pellets Prepared by Liquid Layering - Haoran Wang; Lin Han; Han Zeng; Mengyao Yu; Tian Yin; Yu Zhang; Haibing He; Jingxin Gou; Xing Tang (Pharmaceutical Research, 2025)

Transcriptome Sequencing Reveals Effects of Artificial Feed Domestication on Intestinal Performance and Gene Expression of Carnivorous Mandarin Fish (Siniperca chuatsi) and Related Mechanisms - Jia-Xing Luo; Xiao-Tian Gao; Zhen Rong; Li-Han Zhang; Yan-Feng Sun; Zun-Li Qi; Qi Yu; Khor Waiho; Wei-Xu Zhao; Yi-Huan Xu; Chun-Long Zhao; Cheng-Bin Wu (Marine Biotechnology, 2025)

Long-term no-tillage enhanced soil multifunctionality and reduced microbial metabolic entropy - Hanyu Liu; Yueqi Liang; Jianjian Liu; Qi Zhang; Yingyi Liu; Jia Zeng; Xing Wang; Gaihe Yang; Chengjie Ren; Xinhui Han (Applied Soil Ecology, 2025)

Regulation of soil microbial nitrogen limitation by soybean rhizosphere diazotrophs under long-term no-till mulching - Jiajie Song; Shahzad Haider; Jianheng Song; Dingding Zhang; Sen Chang; Jinze Bai; Jiaqi Hao; Gaihe Yang; Guangxin Ren; Xinhui Han; Xiaojiao Wang; Chengjie Ren; et al. (Applied Soil Ecology, 2025)

Fabrication of Ag based Surface Enhanced Raman Scattering substrates with periodic mask arrays by electron beam deposition - Tian Xing; Jiawei Wang; Jiaqing Wei; Xingxing Du; Ruijin Hong; Chunxian Tao; Qi Wang; Hui Lin; Zhaoxia Han; Dawei Zhang (Analytica Chimica Acta, 2025)

Stronger Response of Plant N:P to Nitrogen Enrichment When Considering Roots - Yu Ning; Feike A. Dijkstra; Xiao‐Sa Liang; Xiao‐Jing Zhang; Guo‐Jiao Yang; Liang‐Chao Jiang; Xing‐Guo Han; Xiao‐Tao Lü (Global Change Biology, 2025)
Nitrogen (N) enrichment leads to an imbalance of N and phosphorus (P) in plants by enhancing plant N:P, with consequences for ecosystem processes and function. However, the evidence for a plant N–P imbalance is predominantly from studies on aboveground tissues. It remains unclear whether imbalanced aboveground responses would be paralleled by similar responses in roots, which contribute to nearly 70% of total biomass in grasslands globally. We measured community‐level N:P stoichiometry of both shoots and roots to 1 m depth across a wide‐ranging N addition gradient in a temperate steppe after 7–9 years of treatment. Both shoot N:P (SNP) and root N:P (RNP) showed nonlinear responses to increasing N addition rates, where N:P first increased and then saturated. RNP was significantly higher than SNP and saturated at higher N addition rates than SNP (39.0 vs. 16.8 g N m −2 yr. −1 ). Furthermore, the inter‐annual stability of RNP was higher than that of SNP. Consequently, N:P in whole plants was higher than that in shoots, indicating more severe N–P imbalance than based on shoot measurements only. Previous results from aboveground parts might have underestimated the enhancement of N enrichment on plant N:P. Our results imply that belowground food webs with roots as their food resource would be more severely suffering from N–P imbalance than aboveground food webs.

Preparation of Carbon Dots with High Fluorescence Quantum Yields and its Detection of Hg2+ in Simulated Wastewater - Hui Wang; Li Han; Yan Gao; Xing Gao; Wen He; Chaoyue Shan; Weixi Fan; Yingkai Guo; Meng Gao; Haidi Cheng (Journal of Fluorescence, 2025)

Nitrite and sulfide stress affects physiological and metabolic functions of gills in crab Eriocheir sinensis - Yi-fu Xing; Yi-fan Feng; Jian Tian; Yu Zhang; Cui Han; Xiao-jie Liu; Jia-xin Yang (Aquaculture, 2025)

Enhancing electrochemical reductive defluorination of PFASs using ZIF-67 modified cathode: Mechanistic insights and performance optimization - Xing Zhang; Han Wu; Yue Wang; Yafei Wang; Yangyang Deng; Yanping Zhu; Shengsen Zhang; Huub Rijnaarts; Harry Bruning; Junhao Qin; Qingqi Lin; Zhuobiao Ni; et al. (Water Research, 2025)

Epilimnetic oligotrophication increases contribution of oxic methane production to atmospheric methane flux from stratified lakes - Fan Xun; Muhua Feng; Cheng Zhao; Wenlei Luo; Xiaotong Han; Zhen Ci; Yifan Yin; Rong Wang; Qinglong L. Wu; Hans-Peter Grossart; Peng Xing (Water Research, 2025)

Divergent responses of soil glomalin and microbial necromass to precipitation reduction: New perspectives from soil aggregates and multi-trophic networks - Xing Wang; Fang Chen; Jia Zeng; Zhengchen Wang; Yongzhong Feng; Xiaojiao Wang; Chengjie Ren; Gaihe Yang; Zekun Zhong; Xinhui Han (Soil Biology and Biochemistry, 2025)

Entropy-TOPSIS-based quantitative evaluation of specific roles of the enhanced coagulation process in multi-objective sewage pre-concentration by microfiltration - Yukun Xing; Xiaoxiang Zhang; Simeng Han; Lanxin Ling; Xiyuan Feng; Xiaoyu Zhang; Zhaotong Liu; Zhengyu Jin (Journal of Water Process Engineering, 2025)

Cross-shore profile evolution induced by real emergent vegetation in a sandbar-lagoon coast: Laboratory experiments - Cuiping Kuang; Xin Cong; Lixin Gong; Jiantao Liu; Xuejian Han; Wei Xing (Geomorphology, 2025)

New application of a dye-decolorizing peroxidase immobilized on magnetic nanoparticles for efficient simultaneous degradation of two mycotoxins - Xinling Du; Mumin Zheng; Han Zhang; Yangyu Qiu; Fuchun Ji; Zishen Nie; Huidong Xu; Xiaoxuan Li; Shijia Wu; Zhouping Wang; Fuguo Xing; Yu Xia (Food Chemistry, 2025)

The role of data resolution in analyzing urban form and PM2.5 concentration - Ziwei Zhang; Han Zhang; Xing Meng; Yuxia Wang; Yuanzhi Yao; Xia Li (Computers, Environment and Urban Systems, 2025)

Silk fibroin for cosmetic dermatology - Songjie Li; Han Chen; Xin Dan; Yikun Ju; Tong Li; Bo Liu; Yang Li; Lanjie Lei; Xing Fan (Chemical Engineering Journal, 2025)

Visible light-powered photodynamic antibacterial chlorophyllin-derived metallochlorins - Yuling Xue; Kuoran Xing; Max Jing Rui Tham; Bang Lin Li; Narattam Sikdar; Lai Peng Leong; Ching Hua Lee; Justin Jang Hann Chu; Wee Han Ang; David Tai Leong (Chemical Engineering Journal, 2025)

Dynamics of zinc dendritic growth in aqueous zinc-based flow batteries: Insights from phase field-Lattice-Boltzmann simulations - Hanxu Jing; Hui Xing; Hailong Zhang; Xinlei Du; Min Wang; Yongsheng Han (Chemical Engineering Journal, 2025)

Accelerated surface brightening in China: The decisive role of reduced anthropogenic aerosol emissions - Qixiang Chen; Chunlin Huang; Zhaohui Ruan; Ming Xu; Hongxia Li; Xinlei Han; Shikui Dong; Xing Yang (Atmospheric Environment, 2025)

Single-cell omics: experimental workflow, data analyses and applications - Fengying Sun; Haoyan Li; Dongqing Sun; Shaliu Fu; Lei Gu; Xin Shao; Qinqin Wang; Xin Dong; Bin Duan; Feiyang Xing; Jun Wu; Minmin Xiao; et al. (Science China Life Sciences, 2025)

Characterization of the complete genome of a novel allexivirus infecting Sauropus androgynus in China - Li-Juan Zhu; Lan-Yi Su; Xing Chen; Shifang Pan; Fagang Xia; Yan-Hong Han; Zhongtian Xu; Qian Xu (Archives of Virology, 2025)

Methane emissions from the riverine sandy wetlands on the Mongolia Plateau - Ang Li; Zun-Lan Luo; Katerina Machacova; Song Zhao; Jin-Chao Feng; Xing-Guo Han; Zhi-Ping Wang (Environmental Monitoring and Assessment, 2024)

Organic fertilizer significantly mitigates N2O emissions while increase contributed of comammox Nitrospira in paddy soils - Han Sun; Youfa Li; Yating Xing; Dylan Bodington; Xing Huang; Chenxiao Ding; Tida Ge; Hongjie Di; Jianming Xu; Cécile Gubry-Rangin; Yong Li (Science of The Total Environment, 2024)

PM2.5-mediated cardiovascular disease in aging: Cardiometabolic risks, molecular mechanisms and potential interventions - Francis Chanda; Kai-xuan Lin; Abdallah Iddy Chaurembo; Jian-yuan Huang; Hui-juan Zhang; Wen-hui Deng; Yun-jing Xu; Yuan Li; Li-dan Fu; Hao-dong Cui; Chi Shu; Yang Chen; et al. (Science of The Total Environment, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

An improved process for the preparation of Si-Fe-Al-Ca alloy from coal gasification fine slag via three-phase plasma smelting - Yaoxuan Wang; Haiyu Li; Zhaoyang Zhang; Xiaolin Guo; Hongbing Du; Wang Han; Yanxin Zhuang; Pengfei Xing (Process Safety and Environmental Protection, 2024)

Overexpression of GmSRC2 confers resistance to Phytophthora sojae in soybean - Sushuang Deng; Yu Zhang; Xiaowan Fang; Han Gou; Ruidong Sun; Huidong Xuan; Haitang Wang; Jinming Zhao; Han Xing; Na Guo (Plant Science, 2024)

Structurally diverse ent-clerodanoids from the aerial parts of Isodon scoparius - Xue-Chun Jiang; Kun Hu; Xue Bai; Xing-Ren Li; Bing-Chao Yan; Su-Ping Chen; Xiao-Nian Li; Han-Dong Sun; Pema-Tenzin Puno (Phytochemistry, 2024)

Interplay between vanadium distribution and microbial community in soil-plant system - Han Zhang; Shu Cheng; Wenyue Yan; Qinghao Zhang; Bo Jiang; Yi Xing; Baogang Zhang (Journal of Hazardous Materials, 2024)

Alteration of soil microbiomes in an arsenic and antimony co-contamination zone after dam failure - Wen Tian; Yongbing Cai; Ruicheng Wang; Han Liu; Xing Xiang; Jianjun Chen; Xingjun Fan; Jianfei Wang; Yue Xie; Feiyue Li (Journal of Hazardous Materials, 2024)

The effect of polyvinyl chloride microplastics on soil properties, greenhouse gas emission, and element cycling-related genes: Roles of soil bacterial communities and correlation analysis - Duo Zhang; Yi Xing; Xin Wang; Wenxin Li; Ying Guo; Yajuan Tang; Han Zhang; Jiayu Chen; Bo Jiang (Journal of Hazardous Materials, 2024)

Gas-liquid interface properties of fluorocarbon and hydrocarbon surfactants and their mixed foams: Molecular dynamics simulations and experimental studies - Qingguo Wang; Xing Zhang; Weixiang Wang; Hongyang Zhao; Saihao Liu; Hetang Wang; Fangwei Han (Journal of Environmental Chemical Engineering, 2024)

Synergistic effects of carbon coating and Bi-bridge in S-scheme C@CuO/Bi/Bi2MoO6 nanocomposites for enhanced photoreduction of Cr(VI) - Luxin Zhang; Qunshuai Li; Xu Xing; Yunfeng Li; Bo Gao; Han Yu (Journal of Environmental Chemical Engineering, 2024)

Encapsulation of ferulic acid in potato protein-pectin nanocomplexes with improved stability and controlled release properties - Zenghong Xing; Wenxin Han; Taotao Dai; Deming Gong; Guowen Zhang (Food Bioscience, 2024)

Differences in the regulation of soil carbon pool quality and stability by leaf-litter and root-litter decomposition - Jia Zeng; Xiangyang Li; Junnan Jian; Liheng Xing; Yu Li; Xing Wang; Qi Zhang; Chengjie Ren; Gaihe Yang; Xinhui Han (Environmental Research, 2024)

Unveiling the adsorption behavior and mass transfer mechanism of Rb+ and Cs+ adsorption on FeMn-MOF - Yanping Wang; Xiushen Ye; Qiongyuan Zhang; Wenjie Han; Xing Liu; Huifang Zhang; Haining Liu; Zhijian Wu; Guosheng Shi (Chemical Engineering Journal, 2024)

The effect of COVID-19 epidemic and sandstorm on distribution of short-, medium-, and long-chain chlorinated paraffins in outdoor atmosphere of Xi'an, Northwest China - Xiuqun Liu; Xiaomei Huang; Han Song; Jingzhi Wang; Jiayu Li; Xi Li; Zhibao Dong; Li Xing; Junji Cao (Atmospheric Environment, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

Melatonin Ameliorates Abnormal Sleep-Wake Behavior via Facilitating Lipid Metabolism in a Zebrafish Model of Parkinson’s Disease - Meng-Zhu Pang; Han-Xing Li; Xue-Qin Dai; Xiao-Bo Wang; Jun-Yi Liu; Yun Shen; Xing Xu; Zhao-Min Zhong; Han Wang; Chun-Feng Liu; Fen Wang (Neuroscience Bulletin, 2024)

Mechanisms of intermittent theta-burst stimulation attenuating nerve injury after ischemic reperfusion in rats through endoplasmic reticulum stress and ferroptosis - Xin-Ya Shen; Xing-Yu Zhang; Ping-Ping Han; Yi-Ning Zhao; Guo-Hui Xu; Xia Bi (Molecular Biology Reports, 2024)
Background Repetitive transcranial magnetic stimulation (rTMS) exerts neuroprotective effects early in cerebral ischemia/reperfusion (I/R) injury. Intermittent theta-brust stimulation (iTBS), a more time-efficient modality of rTMS, improves the efficiency without at least decreasing the efficacy of the therapy. iTBS elevates cortical excitability, and in recent years it has become increasingly common to apply iTBS to patients in the early post-IS period. However, little is known about the neuroprotective mechanisms of iTBS. Endoplasmic reticulum stress (ERS), and ferroptosis have been shown to be involved in the development of I/R injury. We aimed to investigate the potential regulatory mechanisms by which iTBS attenuates neurological injury after I/R in rats. Methods Rats were randomly divided into three groups: sham-operated group, MCAO/R group, and MCAO/R + iTBS group, and were stimulated with iTBS 36 h after undergoing middle cerebral artery occlusion (MCAO) or sham-operated. The expression of ERS, ferroptosis, and apoptosis-related markers was subsequently detected by western blot assays. We also investigated the mechanism by which iTBS attenuates nerve injury after ischemic reperfusion in rats by using the modified Neurological Severity Score (mNSS) and the balance beam test to measure nerve function. Results iTBS performed early in I/R injury attenuated the levels of ERS, ferroptosis, and apoptosis, and improved neurological function, including mNSS and balance beam experiments. It is suggested that this mode of stimulation reduces the cost per treatment by several times without compromising the efficacy of the treatment and could be a practical and less costly intervention.

How functional traits of submerged macrophytes response to underwater light quality? - Xueyuan Gao; Han Liu; Guihua Liu; Wenmin Huang; Wei Xing (Hydrobiologia, 2024)

Influence of Selenium Supplementation on Mercury Levels in hair of Metropolitan Residents in China: Spatial Distribution, Impact Factors, and Antagonism - Geting Wang; Qianqian Hong; Jian Mei; Jinyi Chen; Wansheng Wu; Feng Han; Jingchen Xing; Shijian Yang (Exposure and Health, 2024)

Study on the thermo-hydraulic behaviors within a CiADS 61-pin wire-wrapped fuel assembly under porous blockage conditions based on LBEblockageFoam - Yun-Xiang Li; Run-Sheng Yang; Yue Li; Xing-Kang Su; Yi-Wen Han; Zi-Nan Huang; Lu Meng; Song Li; You-Peng Zhang; Lu Zhang; Wei Jiang (Annals of Nuclear Energy, 2024)

Well Logging Stratigraphic Correlation Algorithm Based on Semantic Segmentation - Cai-zhi Wang; Xing-yun Wei; Hai-xia Pan; Lin-feng Han; Hao Wang; Hong-qiang Wang; Han Zhao (Applied Geophysics, 2024)

Two novel Fe(III)-reducing bacteria, Geothrix campi sp. nov. and Geothrix mesophila sp. nov., isolated from paddy soils - Shuang Han; Shang Yang; Rong Tang; Cheng-Jie Xie; Xing Liu; Guo-Hong Liu; Shun-Gui Zhou (Antonie van Leeuwenhoek, 2024)

Litchi picking points localization in natural environment based on the Litchi-YOSO model and branch morphology reconstruction algorithm - Chenglin Wang; Qiyu Han; Tie Zhang; Chunjiang Li; Xing Sun (Computers and Electronics in Agriculture, 2024)

Mapping the heterogeneous removal landscape of wastewater virome in effluents of different advanced wastewater treatment systems of swine farm - Jiabao Xing; Han Gao; Guangyu Liu; Xinyu Cao; Jianhao Zhong; Sijia Xu; Yue Li; Yuwan Pang; Guihong Zhang; Yankuo Sun (Water Research, 2024)

Characteristics and regulatory mechanisms of net ecosystem CO2 exchange at the water-air interface in coastal aquaculture ponds - Ziyu Wang; Qinghui Xing; Hao Cheng; Yue Ming; Hong Chen; Xuemei Xu; Zhaowei Wang; Jianbo Han; Jinqiu Du (Science of The Total Environment, 2024)

Water temperature and salt ions respectively drive the community assembly of bacterial generalists and specialists in diverse plateau lakes - Xing Liu; Baozhu Pan; Lixin Wang; Yichi Zhang; Xiaohui Zhao; Xu Han; Xinyuan Liu; Jingxiang Hu (Science of The Total Environment, 2024)

Enhancing effect of conductive materials and rumen microorganisms on the anaerobic digestion performance of a real traditional Chinese medicine wastewater - Han Gao; Xiang-Lin Chang; Su Li; Rong Chen; Yu-You Li; Bao-Shan Xing (Journal of Water Process Engineering, 2024)

Differential spatial responses and assembly mechanisms of soil microbial communities across region-scale Taiga ecosystems - Zheng-Xiao Liu; Yue-Ming Lyu; Yang Liu; Yun-Qi Wang; Ming-Min Xiong; Yuan Tang; Xing-Yue Li; Han Sun; Ji-Liang Xu (Journal of Environmental Management, 2024)

Agglomeration-dispersion effects of coal fines to control the permeability of propping fractures: A visual experimental study - Zixiang Han; Shuaifeng Lyu; Ao Lu; Lichao Chen; Quanming Chen; Haichao Xing (Gas Science and Engineering, 2024)

From flavor to function: A review of fermented fruit drinks, their microbial profiles and health benefits - Yu-Han Yuan; Dong-Dong Mu; Li Guo; Xue-Feng Wu; Xiang-Song Chen; Xing-Jiang Li (Food Research International, 2024)

Polyoxometalates-based metal-organic frameworks with conjugated acid-base pairs for proton supercapacitors - Bao-Yue Zhang; Xue-Song Wu; Ning-Hao Wang; Xin-Long Wang; Xing-Qi Han; Zhong-Min Su (Chemical Engineering Journal, 2024)

Unique electron-feeding mechanism in CoN3O for enhanced acidic oxygen reduction - Wei Zhang; Guokang Han; Changpeng Liu; Xue Zhang; Wei Xing; Chunyu Du (Chemical Engineering Journal, 2024)

Regulation of N Zn O bonds via carbonized polymer dots in polyaniline composite cathode for high performance stable aqueous Zn-ion batteries - Bao-Hong Xu; Yi-Han Song; Guo-Duo Yang; Jia-Yu Zhang; Yu-Qi Liu; Jie-Qiong Liu; Qi-Meng Zhang; Xing-Long Wu; Ming-Xiao Deng; Hai-Zhu Sun (Chemical Engineering Journal, 2024)

Acacetin targets STING to alleviate the destabilization of the medial meniscus-induced osteoarthritis in mice - Dingjun Xu; Linjie Zhang; Chenyu Song; Dinglei Zhang; Chunlei Xing; Juan Lv; Huihui Bian; Minyu Zhu; Minxuan Han; Yongsheng Yu; Li Su (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Metal regeneration during an ex-situ disturbance experiment on deep-sea sediments from the polymetallic nodule area of western Pacific - Juan Yang; Zhaohui Xing; Baolin Liu; Dong Sun; Chunsheng Wang; Luwei Han; Jianxin Xia; Wenquan Zhang; Chengbing Song (Frontiers in Marine Science, 2024)
The ecological implications of deep-sea mining, particularly the considerable discharge of suspended sediments during operational processes, have attracted substantial concerns. In order to reveal the metal regeneration dynamics in the polymetallic nodule area of the western Pacific Ocean, ex-situ sediment disturbance experiments were conducted on a research vessel. After two levels of regulated stirring disturbance were exerted for half an hour, the concentrations of 12 dissolved metals and physicochemical parameters, including Eh and pH, were monitored continuously in the overlying water for three days. Porewater samples were also collected at the starting and ending time of each experiment to detect the change of dissolved metal profiles within the sediments. The findings revealed that the sediment disturbance led to fluctuations in the concentrations of metals in the overlying water, with manganese exhibiting the most pronounced change at a coefficient of 208%. The temporal patterns of dissolved metal concentrations demonstrated a coherent behavior among certain metals, such as Li, V, Co, Ni, Rb, Mo, and Cs, which displayed an overall increase, ultimately surpassing the initial concentrations in the overlying water. In line with this, the metal concentration profiles in the porewater were also elevated. Spearman correlation analysis confirmed the synchronized behavior of these metals. The results suggested that the metals mobility might be governed by physicochemical factors in the overlying water. Moreover, the sedimentary features, such as grain size composition, and the morphological state of metals in sediments played pivotal roles in the differential responses of metal groups to sediment disturbance across stations. Conversely, the disturbance intensity was found to have a relatively minor impact on the dissolved metal behavior. The findings from the ex-situ experiments provided critical insights for predicting metal regeneration related to deep-sea mining, which are expected to be validated through rigorous monitoring protocols during future in-situ mining trials.

Improved recovery of lithium from spent lithium-ion batteries by reduction roasting and NaHCO3 leaching - Wenke Liu; Qingwei Qin; Hailin Zhang; Wei Zhao; Xing Chen; Jiachun Xiong; Yunwu Han; Shili Zheng; Chunguang Zhang; Guangqiang Li; Ping Li (Waste Management, 2024)

Integrated transcriptomic and metabolomic analysis reveals the underlying mechanisms for male reproductive toxicity of polystyrene nanoplastics in mouse spermatocyte-derived GC-2spd(ts) cells - Hang Han; Zhen Zhang; Bo Xu; Liyang Ding; Hong Yang; Tiantian He; Xing Du; Xiuying Pei; Xufeng Fu (Toxicology in Vitro, 2024)

Aridity shapes distinct biogeographic and assembly patterns of forest soil bacterial and fungal communities at the regional scale - Xing Wang; Jia Zeng; Fang Chen; Zhengchen Wang; Hanyu Liu; Qi Zhang; Weichao Liu; Wenjie Wang; Yang Guo; Yanfeng Niu; Linshan Yuan; Chengjie Ren; et al. (Science of The Total Environment, 2024)

Identification of sanguinarine as a novel antagonist for perfluorooctanoate/perfluorooctane sulfonate-induced senescence of hepatocytes: An integrated computational and experimental analysis - Xue Zhang; Huan Gao; Xiaoyu Chen; Ziqi Liu; Han Wang; Mengxing Cui; Yajie Li; Yongjiang Yu; Shen Chen; Xiumei Xing; Liping Chen; Daochuan Li; et al. (Journal of Hazardous Materials, 2024)

Associations of prenatal exposure to individual and mixed organophosphate esters with ADHD symptom trajectories in preschool children: The modifying effects of maternal Vitamin D - Han Li; Juan Tong; Xing Wang; Mengjuan Lu; Fengyu Yang; Hui Gao; Hong Gan; Shuangqin Yan; Guopeng Gao; Kun Huang; Yunxia Cao; Fangbiao Tao (Journal of Hazardous Materials, 2024)

Catalytic performance and mechanism of Pt VW catalyst for selective catalytic oxidation of high-concentration NH3 - Xing Feng; Yu Gao; Zhitao Han (Journal of Environmental Chemical Engineering, 2024)

A facile electrospinning strategy to prepare cost-effective carbon fibers as a self-supporting anode for lithium-ion batteries - Xuefeng Han; Hui Guo; Baolin Xing; Hao Liang; Huihui Zeng; Weiwei Kang; Xiaoxiao Qu; Chuanxiang Zhang; Yijun Cao; Zhengfei Chen (Fuel, 2024)

Corrigendum to “In-situ electret scaffolds with controllable electric fields printed by MEW for bone tissue regeneration” [Chem. Eng. J. 496 (2024) 154330] - Xing Zhang; Zhiguang Qiao; Meifei Lian; Yu Han; Jieming Lin; Bin Yu; Linfa Peng; Huamiao Wang; Kerong Dai (Chemical Engineering Journal, 2024)

Conjugated acid-base pairs in Keggin-type polyoxometalate-based metal-organic frameworks enhance proton conduction - Ning-Hao Wang; Bao-Yue Zhang; Xue-Song Wu; Jia-Wei Wang; Xing-Qi Han; Jing Sun; Xin-Long Wang; Zhong-Min Su (Chemical Engineering Journal, 2024)

Fluorinated ionic liquid mediated nanostructure with enhanced conductivity and fluorine retention in Na3V2(PO4)2F3 cathode toward high-performance sodium-ion batteries - Yang Yan; Jun-Qing Xu; Jun-Ming Cao; Han-Wei Huang; Sen-Sen Xue; Guang-Lan Li; An-Min Liu; Cheng-Jie Li; Dongmei Dai; Bao Li; Xing-Long Wu (Chemical Engineering Journal, 2024)

Green wood bio-adhesives from cellulose-derived bamboo powder hydrochars - Yong-Xing Chen; Han-Song Zhu; Fan Gao; Huan-Ran Xiong; Huan Yang; Zhi-Xiang Xu; Pei-Gao Duan; Li-Jun Zheng; Sameh M. Osman; Rafael Luque (Chemical Engineering Journal, 2024)

Rapidly synthesizing magneto-thermal adjustable high entropy alloy nanoparticles on carbon fiber surface for enhancing electromagnetic wave absorption, thermal conductivity and interface compatibility of composites - Jinchuan Chen; Chuanqiang Sun; Zhe Han; Yujing Zhang; Feng Yang; Linlong Xing; Huajie Xu; Chuntai Liu; Changyu Shen (Chemical Engineering Journal, 2024)

Slot-structured catalytic membrane for sustained oily particulate matter removal with a low pressure drop - Jiesong Tan; Yiqing Zeng; Jiahao Chen; Yutang Kang; Jiangxiao Qiao; Feng Zhang; Feng Han; Zhaoxiang Zhong; Weihong Xing (Chemical Engineering Journal, 2024)

Integrating solar-driven biomass gasification and PV-electrolysis for sustainable fuel production: Thermodynamic performance, economic assessment, and CO2 emission analysis - Yu Xin; Wanlin Zhang; Fujie Chen; Xueli Xing; Dongjiang Han; Hui Hong (Chemical Engineering Journal, 2024)

Regulation of photosynthetic carbon fate by plant diversity and nutrients in abandoned farmland on the Loess Plateau - Hanyu Liu; Yaoyue Liang; Jingbo Fang; Yingyi Liu; Xing Wang; Qi Zhang; Weichao Liu; Gaihe Yang; Chengjie Ren; Xinhui Han (CATENA, 2024)

Petrogenesis of Neoarchean granitic gneisses from the Daqishan area of the Dabie orogen and implications for the early crustal evolution of the Northern Yangtze Craton - Lingyao Kong; Xiang Xing; Qingsen Han; Hua Luo; Pan Guo; Xin Deng; Jun Wan; Chao Chen; Chengxin Liu (International Geology Review, 2024)

Stereo visual-inertial localization algorithm for orchard robots based on point-line features - Xing Xu; Jinming Liang; Jianying Li; Guang Wu; Jieli Duan; Mohui Jin; Han Fu (Computers and Electronics in Agriculture, 2024)

Effects of carbon limitation and carbon fertilization on karst lake-reservoir productivity - Haibo He; Zaihua Liu; Dongli Li; Xing Liu; Yongqiang Han; Hailong Sun; Min Zhao; Mingyu Shao; Liangxing Shi; Pengyun Hao; Chaowei Lai (Water Research, 2024)

Quantifying the negative effects of dissolved organic carbon of maize straw-derived biochar on its carbon sequestration potential in a paddy soil - Lanfang Han; Beibei Liu; Yu Luo; Liying Chen; Chuanxin Ma; Chao Xu; Ke Sun; Baoshan Xing (Soil Biology and Biochemistry, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Highly active Ni atomic clusters loaded with coal gasification slag derivatives effectively remove tetracycline by activating persulfate to enhance electron transfer ability - Zhi Song; Xiayan Zhang; Boxia Liu; Jialu Liu; Yeqiong Huang; Dongxu Han; Chuhan Xing (Journal of Water Process Engineering, 2024)

Heterogenization of microplastic communities in lakes of the Qinghai-Tibetan Plateau driven by tourism and transport activities - Xu Han; Baozhu Pan; Dianbao Li; Xing Liu; Xinyuan Liu; Yiming Hou; Gang Li (Journal of Hazardous Materials, 2024)

Ecotoxicological assessment, oxidative response, and enzyme activity disorder of the rotifer Brachionus asplanchnoidis exposed to a toxic cocktail of spent lithium-ion battery leachate - Yi-fan Feng; Yu Zhang; Run-jia Yang; Si-qi Li; Xiao-jie Liu; Cui Han; Yi-fu Xing; Jia-xin Yang (Journal of Hazardous Materials, 2024)

Association between outdoor light at night exposure and executive function in Chinese children - Han-Yu Yang; Si-Han Wu; Shuo Zhang; Hong-Xing Zou; Le-Bing Wang; Li-Zi Lin; Zhao-Huan Gui; Xiao-Wen Zeng; Bo-Yi Yang; Ru-Qing Liu; Guang-Hui Dong; Li-Wen Hu (Environmental Research, 2024)

Na+ orientates Jahn-Teller effect to tune Li+ diffusion pathway and kinetics for Single-Crystal Ni-rich LiNixCoyMn1-x-yO2 cathode materials - Jiyuan Jian; Xing Xu; Xiaoyi Pan; Guokang Han; Rang Xiao; Ziwei Liu; Dandan Sun; Xin Zhang; Qingjie Zhou; He Zhu; Geping Yin; Hua Huo; et al. (Chemical Engineering Journal, 2024)

In-situ electret scaffolds with controllable electric fields printed by MEW for bone tissue regeneration - Xing Zhang; Zhiguang Qiao; Meifei Lian; Yu Han; Jieming Lin; Bin Yu; Linfa Peng; Huamiao Wang; Kerong Dai (Chemical Engineering Journal, 2024)

Boronate-modified electro-spun Fe doped carbon nanofibrous membrane for selective dye adsorption, catalytic degradation, and bacterial inhibition in treatment of water - De-yu Tang; Ling-ling Yan; Luo-lin Deng; Xing-han Wang; Ya-li Xiang; Qing-li Li; Juan Lin; Qing-han Zhou (Chemical Engineering Journal, 2024)

Construction of Covalent organic frameworks with bex topology for efficient photocatalytic hydrogen production - Lin Wang; Changzhi Han; Jingwen Pan; Shuo Li; Jia-Xing Jiang; Fengyun Guo; Shiyong Gao; Dongbo Wang; Yong Zhang (Chemical Engineering Journal, 2024)

Three new lanostane triterpenoids and two new amides from Alternaria sp. with NLRP3 inflammasome inhibitory activity - De-Wen Bi; Jian- Feng; Wen-Hui Pang; Peng-Yun Yang; Yao-Jun Xu; Muhammad Aurang Zeb; Meng-Ru Wang; Xing-Jie Zhang; Xiao-Li Li; Rui-Han Zhang; Wei-Guang Wang; Wei-Lie Xiao (Natural Product Research, 2024)

Urban HydroConnect: Harnessing SWMM for Dynamic Waterway Management Assessment - Xianqi Zhang; Peng Chen; Shengnan Dai; Yonghua Han; Xing Chang (Water Resources Management, 2024)

The p38/MAPK pathway as a therapeutic target to prevent therapeutic escape of breast cancer stem cells - Weixiao Yan; Xiaotong Wang; Wenjing Wang; Qi Guo; Na Huang; Hao Chen; Xing-Jie Liang; Yu Han; Dandan Liu; Jinchao Zhang (Science China Life Sciences, 2024)

Actn2 defects accelerates H9c2 hypertrophy via ERK phosphorylation under chronic stress - Kang Wang; Ye Wang; Hua Wan; Jie Wang; Li Hu; Shuainan Huang; Mingchen Sheng; Jiayi Wu; Xing Han; Youjia Yu; Peng Chen; Feng Chen (Genes & Genomics, 2024)

PET microplastics influenced microbial community and heavy metal speciation in heavy-metal contaminated soils - Yajuan Tang; Yi Xing; Xin Wang; Haobo Ya; Tian Zhang; Mingjie Lv; Jianchao Wang; Han Zhang; Wei Dai; Duo Zhang; Rui Zheng; Bo Jiang (Applied Soil Ecology, 2024)

Control of carbon dioxide exchange fluxes by rainfall and biological carbon pump in karst river–lake systems - Chaowei Lai; Zaihua Liu; Qingchun Yu; Hailong Sun; Fan Xia; Xuejun He; Zhen Ma; Yongqiang Han; Xing Liu; Pengyun Hao; Qian Bao; Mingyu Shao; et al. (Science of The Total Environment, 2024)

Chelation strategy induced blue-shift for efficient deep-blue perovskite light-emitting diodes - Yu Xia; Zhipeng Zhang; Yu-Hang Zhou; Yu-Han Li; Bin Wang; Kai-Li Wang; Chun-Hao Chen; Jing Chen; Ilhan Yavuz; Guichuan Xing; Zhao-Kui Wang (Science Bulletin, 2024)

Vegetation factors and atmospheric dryness regulate the dynamics of ecosystem water use efficiency in a temperate semiarid shrubland - Yanmei Mu; Xin Jia; Ziqi Ye; Xulin Guo; Shaorong Hao; Tianshan Zha; Yuqing Zhang; Cong Han; Shengjie Gao; Fei Xing; Shugao Qin; Peng Liu; et al. (Journal of Hydrology, 2024)

Versatile filter membrane for effective sampling and real-time quantitative detection of airborne pathogens - Saisai Yan; Qing Liu; Kunyue Xing; Zhanjie Liu; Han Guo; Wenhao Jiang; Xinyue Ma; Mingzhe Yan; Chao Wang; Xinlin Liu; Dongming Xing (Journal of Hazardous Materials, 2024)

Innovative lignin photocatalyst system motivated by intramolecular charge dynamics for H2O2 production - Xinyu Xiao; Honghan Wang; Xing Wang; Chao Liu; Ying Han; Shangru Zhai; Haishun Du (Chemical Engineering Journal, 2024)

Gravity Change Caused by Heavy Rainfall Detected by A gPhone Gravimeter in Zhengzhou, China - Lelin Xing; Yufei Han; Xiaowei Niu; Lei Bai (Journal of Earth Science, 2024)

Establishing a protected area network in Xinlong with other effective area‐based conservation measures - Xing Chen; Tengteng Tian; Han Pan; Yuyi Jin; Xiaodian Zhang; Biao Yang; Li Zhang (Conservation Biology, 2024)
Protected areas (PAs) are pivotal to biodiversity conservation, yet their efficacy is compromised by insufficient funding and management. So‐called other effective area‐based conservation measures (OECMs) present a paradigm shift and address PA limitations. Such measures can expand conservation areas, enhance connectivity, and improve the existing system. To assess the conservation status of biodiversity in Tibetan cultural areas in China, we investigated the spatial distribution of wildlife vulnerable to human disturbance (large‐ and medium‐sized mammals and terrestrial birds) in Xinlong, a traditional Tibetan cultural area. In particular, we compared a PA (Xionglongxi Nature Reserve) and OECMs targeting species conservation. We also investigated the relationship of wildlife with human temporal and spatial activities. The OECMs complemented areas not covered by PA, especially in rich understory biodiversity regions. More species in OECMs tolerated human presence than species in the PA. Existing biodiversity reserves failed to cover areas of high conservation value in Tibet and offered limited protection capacity. Expanding PAs and identifying OECMs improved Xinlong's system by covering most biodiversity hotspots. Building on the tradition of wildlife conservation in Tibet, harnessing OECMs may be an effective means of augmenting biodiversity conservation capacity. We recommend further evaluation of OECMs effectiveness and coverage in Tibetan area as a way to enhance the current PA system.

Upward soil arching effect under unloading: mechanism, theory and engineering application - Ren-Peng Chen; Han-Lin Wang; Xiang-Shen Fu; Fanyan Meng; Qi-Wei Liu; Xing-Tao Lin (Transportation Geotechnics, 2024)

Small water body significantly contributes to nitrous oxide emissions in China's aquaculture - Xing Yan; Haojie Han; Xiaohan Li; Xiangmin Rong; Longlong Xia; Xiaoyuan Yan; Yongqiu Xia (Journal of Environmental Management, 2024)

Nitrogen-doped carbon supported iron nanoparticles for mild catalytic hydrocracking of Xilinguole lignite - Zhi Yang; Fang-Jing Liu; Han-Bing Zhang; Yu-Lu Zhang; Yao Lu; Bo Meng; Shan-Shan Gao; Zai-Xing Huang; Guo-Jun Kang; Jing-Pei Cao; Xian-Yong Wei; Yun-Peng Zhao (Fuel, 2024)

Heterogenetic mechanism in high-temperature Daqu fermentation by traditional craft and mechanical craft: From microbial assembly patterns to metabolism phenotypes - Gailing Shi; Chao Fang; Shuang Xing; Ying Guo; Xin Li; Xiao Han; Liangcai Lin; Cuiying Zhang (Food Research International, 2024)

P-limitation regulates the accumulation of soil aggregates organic carbon during the restoration of Pinus tabuliformis forest - Xiangyang Li; Jia Zeng; Jianjian Liu; Qi Zhang; Yingyi Liu; Xing Wang; Hanyu Liu; Yongtao Zhao; Yunlong Zhang; Chengjie Ren; Gaihe Yang; Xinhui Han (Environmental Research, 2024)

Preparation of MOFs-based molecularity imprinted composite membrane biomimetically modified by PDA and its selective separation performance and mechanism - Yue Li; Jing Yan; Faguang Ma; Han Liu; Maobin Wei; Wendong Xing; Yilin Wu (Desalination, 2024)

From cell membrane to endoplasmic reticulum: Tunable lipid membrane imaging by regulating the lipophilicity and internalization of carbon dots - Yanzhi Xing; Jiaxin Li; Han Leng; Yanfeng Zhang; Shuang E; Jianhua Wang; Xuwei Chen (Chemical Engineering Journal, 2024)

Characteristics of rill development and dynamic mechanisms in intermittent field runoff scouring experiments - Tingting Tao; Lingyong Kong; Jie Zhang; Xing Wang; Wenhao Tan; Wei Han; Fulin Luo; Tao Feng; Xiaoyan Chen (CATENA, 2024)

Discovery and characterization of a new hydrothermal field at 2°N on the slow-spreading Carlsberg Ridge - Zhongyan Qiu; Yejian Wang; Xiqiu Han; Honglin Li; Xing Yu; Ruyong Cui; Mou Li; Xuegang Chen; Jiqiang Liu (Journal of Oceanology and Limnology, 2024)

Effect of rehabilitation exercise on locomotion performance of captive Bengal slow loris - Xing Bolin; Liao Linhong; Han Dongchen; Liu Jiayong; Zhao Kairui; Fan Yumai; Teng Ping; Zhang Yan; Huang Anqi; Zeng Changjun; Xie Meng; Ni Qingyong (Applied Animal Behaviour Science, 2024)

Sonar Fish School Detection and Counting Method Based on Improved YOLOv8 and BoT-SORT - Bowen Xing; Min Sun; Zhenchong Liu; Lianwu Guan; Jitao Han; Chuanxu Yan; Chuang Han (Journal of Marine Science and Engineering, 2024)
Fish object detection and counting in pelagic fisheries face many challenges in complex environments. Sonar imaging technology offers a solution because it generates high-resolution images underwater. In this paper, we propose a sonar-based fish object detection and counting method using an improved YOLOv8 combined with BoT-SORT to address issues such as missed detection, false detection, and low accuracy caused by complex factors such as equipment motion, light changes, and background noise in pelagic environments. The algorithm utilizes the techniques of lightweight upsampling operator CARAFE, generalized feature pyramid network GFPN, and partial convolution. It integrates with the BoT-SORT tracking algorithm to propose a new region detection method that detects and tracks the schools of fish, providing stable real-time fish counts in the designated area. The experimental results indicate that while focusing on maintaining a lightweight design, the improved algorithm achieved a 3.8% increase in recall and a 2.4% increase in mAP0.5 compared to the original algorithm. This significantly impacts scientific and rational fishery planning, marine resource protection, and improved productivity. At the same time, it provides important data support for marine ecological monitoring, environmental protection, and fishery management, contributing to sustainable fishery development and marine ecology preservation.

Investigation on tunnelling-induced soil pressure changes, a modified trapdoor test study - Yao Li; Xing Dong; Xuchao Du; Zhanglong Guo; Houxian Chen; Ruida Han (Tunnelling and Underground Space Technology, 2024)

In vivo study on osteogenic efficiency of nHA/ gel porous scaffold with nacre water-soluble matrix - SiRi-GuLeng Li; Zhu-Ling Guo; Si-Yu Tao; Tao Han; Jie Zhou; Wan-Yun Lin; Xiang Guo; Chu-Xing Li; Sunchuri Diwas; Xiao-Wen Hu (Tissue and Cell, 2024)

Adaptive knowledge transfer-based particle swarm optimization for constrained multitask optimization - Xing Bai; Ying Hou; Honggui Han (Swarm and Evolutionary Computation, 2024)

Air pollution mixture associated with oxidative stress exacerbation and symptoms deterioration in allergic rhinitis patients: Evidence from a panel study - Jinhui Li; Haisheng Wu; Weiwei Xing; Xin Li; Zheshen Han; Renyue Ji; Zhengyi Deng; Minji Jung; Shengzhi Sun; Benjamin I. Chung; Andres Cardenas; Marvin E. Langston (Science of The Total Environment, 2024)

Unintentional persistent organic pollutants in cremation process: Emissions, characteristics, and inventory - Rongrong Lei; Yunchen He; Wenbin Liu; Javid Hussain; Lijun Liu; Jinglei Han; Changliang Li; Yi Xing; Wei Su (Science of The Total Environment, 2024)

The trade-off effects of water flow velocity on denitrification rates in open channel waterways - Xiaohan Li; Xing Yan; Haojie Han; Gang Luo; Xiaoyuan Yan; Yongqiu Xia (Journal of Hydrology, 2024)

Large-scale soil application of hydrochar: Reducing its polycyclic aromatic hydrocarbon content and toxicity by heating - Hongyu Si; Rui Wang; Yuqing Zhao; Han Hao; Changkai Zhao; Sen Xing; Hewei Yu; Xiaohui Liang; JiKai Lu; Xiuxiu Chen; Bing Wang (Journal of Hazardous Materials, 2024)

Insights into the response of electroactive biofilm with petroleum hydrocarbons degradation ability to quorum sensing signals - Jianliang Xue; Han Ma; Xing Dong; Ke Shi; Xiaoyu Zhou; Yanlu Qiao; Yu Gao; Yang Liu; Yujie Feng; Qing Jiang (Journal of Hazardous Materials, 2024)

Interaction of acetamiprid, Varroa destructor, and Nosema ceranae in honey bees - Yuxin Kang; Tong Wu; Bo Han; Sa Yang; Xing Wang; Qiang Wang; Jing Gao; Pingli Dai (Journal of Hazardous Materials, 2024)

Enhancing the performance of triboelectric nanogenerator via chitosan films surface modification - Jin Han; Jiayao Li; Xing Zhang; Liwei Zhao; Chunchang Wang (Chemical Engineering Journal, 2024)

Promote the performance of carbon electrode based perovskite solar cells with Cu2GeS3 hole transporting layer - Nian Cheng; Weiwei Li; Han Pan; Dingshan Zheng; Wen-Xing Yang (Chemical Engineering Journal, 2024)

Microecology of aerobic denitrification system construction driven by cyclic stress of sulfamethoxazole - Xiao-Yan Fan; Zhong-Xing Zhang; Xing Li; Yuan-Kun Liu; Shen-Bin Cao; Wen-Nian Geng; Ya-Bao Wang; Xiao-Han Zhang (Bioresource Technology, 2024)

A compound enzyme as an additive to a continuous anaerobic dynamic membrane bioreactor for enhanced lignocellulose removal from codigestion: Performance, membrane characteristics and microorganisms - Bao-Shan Xing; Xiang-Lin Chang; Yi Zhang; Sifan Cao; Xi-Fang Tang; Yong-Chen Han; Yu-You Li; Xiaochang C. Wang; Rong Chen (Bioresource Technology, 2024)

Therapeutic effects and mechanisms of isoxanthohumol on DSS-induced colitis: regulating T cell development, restoring gut microbiota, and improving metabolic disorders - Ya-Na Yang; Bing Han; Mao-Qing Zhang; Na-Nan Chai; Feng-Lin Yu; Wen-Hui Qi; Meng-Yuan Tian; Dong-Zhi Sun; Ying Huang; Qing-Xin Song; Yan Li; Mao-Cui Zhu; et al. (Inflammopharmacology, 2024)

Mining, screening, and validation of cold-resistance molecular markers in Vitis vinifera L. - Zhi-Lei Wang; Xing Han; Wen-Long Ma; Guo-Qian Xu; Ting-Ting Xue (Euphytica, 2024)

Air permeability variation of compacted loess: effects of soil basic properties and dry-wet cycles - Shi-Feng Lu; Xiao-Pei Guo; Xing-Rui Wang; Zi-Jing Han; Ling Xu; Xiao-Lin Huang; Lu Zuo (Bulletin of Engineering Geology and the Environment, 2024)

Liver Iron Overload Drives COVID-19 Mortality: a Two-Sample Mendelian Randomization Study - Huimin Tian; Xiangjie Kong; Fulei Han; Fangjie Xing; Shuai Zhu; Tao Xu; Weijing Wang; Ning Song; Yili Wu (Biological Trace Element Research, 2024)

Impacts of Integrated Multi-Trophic Aquaculture on Phytoplankton in Sanggou Bay - Jichang Han; Xing Liu; Kehou Pan; Jiaojiao Liu; Yan Sun; Guiyong Jin; Yun Li; Yuhang Li (Journal of Ocean University of China, 2024)

The Sirtuin 5 Inhibitor MC3482 Ameliorates Microglia‑induced Neuroinflammation Following Ischaemic Stroke by Upregulating the Succinylation Level of Annexin-A1 - Qian Xia; Yongbo Yu; Gaofeng Zhan; Xue Zhang; Shuai Gao; Tangrui Han; Yilin Zhao; Xing Li; Yonghong Wang (Journal of Neuroimmune Pharmacology, 2024)

Correlation between acoustic velocity and physical parameters of sea floor sediments: a case study of the northern South China Sea - Hongmao Zhang; Lei Xing; Qingjie Zhou; Qianqian Li; Jiayi Han; Kai Liu (Frontiers in Marine Science, 2024)
As the interface between seawater and the seabed, superficial sediments on the seabed are an important part of the marine acoustic field environment and are indispensable for marine resource investigations. Studying sediments several meters to hundreds of meters below the seafloor is highly valuable and important. This study processes and analyses the water depth, topography and bottom data and obtains the shallow bottom profile and topographic map of the northern continental slope of the South China Sea (SCS). The study analyzes the influence of physical parameter (including density, porosity, and grain size) on the acoustic velocity in sediments. Single-parameter and dual-parameter models are established to further examine this influence. The results show that porosity and density have greater influences on the acoustic velocity of sediments than does grain size. Finally, the acoustic properties of several typical stations with water depths are tested to analyze the variations in the acoustic properties of the shallow sediments in the northern SCS. The results show that the influence of each parameter on the prediction of the acoustic velocity of the sediment is in the following order: porosity>density>grain size. This study analyses and reveals the reason why the seafloor sediments in the local area cause the acoustic properties to change greatly. It may be caused by changes in the sediment type, lithology along with the depth. And the other reason is the development of interlayer in the land slope of the northern SCS.

Mechanism of organic phosphorus transformation and its impact on the primary production in a deep oligotrophic plateau lake during stratification - Xiaotong Han; Fan Xun; Xianlong Zhu; Cheng Zhao; Wenlei Luo; Yanru Liu; Man Wang; Di Xu; Shiqiang Wan; Qinglong L. Wu; Peng Xing (Water Research, 2024)

Long-term use of etomidate disrupts the intestinal homeostasis and nervous system in mice - Siming Ding; Kan Li; Xing Han; Wenting Lin; Yingjun Qin; Renjuan Cao; Yuan Ren (Toxicology, 2024)

Redox mediator chlorophyll accelerates low-temperature biological denitrification with responses of extracellular polymers and changes in microbial community composition - Xiao-Yan Fan; Ya-Bao Wang; Xing-Li; Shen-Bin Cao; Xiao-Han Zhang; Wen-Nian Geng (Science of The Total Environment, 2024)

Centurial deposition records of polychlorinated biphenyls and organochlorine pesticides in sediment cores from a plateau deep-water lake of China: Significance of anthropogenic impacts, transformation signals and ecological risks revealed by full congener analysis - Xuexin Han; Lei Xu; Aixin Deng; Peng Xing; Yan Xu (Science of The Total Environment, 2024)

Deterministic assembly of grassland soil microbial communities driven by climate warming amplifies soil carbon loss - Xing Wang; Zhengchen Wang; Fang Chen; Zhenjiao Zhang; Jingbo Fang; Liheng Xing; Jia Zeng; Qi Zhang; Hanyu Liu; Weichao Liu; Chengjie Ren; Gaihe Yang; et al. (Science of The Total Environment, 2024)

Acid rain reduced soil carbon emissions and increased the temperature sensitivity of soil respiration: A comprehensive meta-analysis - Weichao Liu; Jingbo Fang; Yaoyue Liang; Xing Wang; Qi Zhang; Jinduo Wang; Mengfan He; Wenjie Wang; Jian Deng; Chengjie Ren; Wei Zhang; Xinhui Han (Science of The Total Environment, 2024)

Trophic level plays an enhanced role in shaping microbiota structure and assembly in lakes with decreased salinity on the Qinghai-Tibet and Inner Mongolia Plateaus - Xing Liu; Baozhu Pan; Xinyuan Liu; Xu Han; Penghui Zhu; Gang Li; Dianbao Li (Science of The Total Environment, 2024)

Characteristics of PM2.5 bounded carbonaceous aerosols, carbon dioxide and its stable carbon isotopes (δ13C) in rural households in northwest China: Effect of different fuel combustion - Xiuqun Liu; Zedong Wang; Jingzhi Wang; Li Xing; Jiayu Li; Zhibao Dong; Minrui Li; Yongming Han; Junji Cao (Journal of Environmental Management, 2024)

Isolation of Rhizobacteria from Crocus Sativus L. Rhizosphere and Their Effects on Host-Growth Promotion - Jing-Chao Xu; Xing-Guang Xie; Xue-Wen Bi; Jia-Hao Zhang; Zi-Hui Zhao; Khalid Rahman; Bo Zhu; Lu-Ping Qin; Ting Han (Journal of Plant Growth Regulation, 2024)

Long-term exposure to fine particulate matter constituents in relation to chronic kidney disease: evidence from a large population-based study in China - Yucen Dai; Jianzhong Yin; Sicheng Li; Jiawei Li; Xinyu Han; Quzong Deji; Ciren Pengcuo; Leilei Liu; Zhimiao Yu; Liling Chen; Linshen Xie; Bing Guo; et al. (Environmental Geochemistry and Health, 2024)

Liver Injury Induced by Exposure to Polystyrene Microplastics Alone or in Combination with Cadmium in Mice Is Mediated by Oxidative Stress and Apoptosis - Shuai Sheng; Ningxin Han; Yufeng Wei; Jinghan Wang; Wei Han; Boyu Xing; Mingwei Xing; Wen Zhang (Biological Trace Element Research, 2024)

Quasi-2D spin-Peierls transition through interstitial anionic electrons in K(NH3)2 - Chi Ding; Qing Lu; Zhaopeng Guo; Tianheng Huang; Junjie Wang; Yu Han; Dingyu Xing; Jian Sun (Science Bulletin, 2024)

Exploring the characteristics and drivers of virtual cropland trade of major agricultural products in China - Han Meng; Liwei Xing; Jiaxuan Hu; Chen Shen; Hongyu Zhang; Jianzhai Wu (Journal of Cleaner Production, 2024)

Responses of activated sludge to quorum sensing inhibitor and antibiotic compound stress: Interactions among abundant-rare genera, functional genes, and antibiotic resistance genes - Xiao-Yan Fan; Wen-Nian Geng; Xing Li; Yuan-Kun Liu; Shen-Bin Cao; Xiao-Han Zhang; Ya-Bao Wang (Journal of Environmental Chemical Engineering, 2024)

Double bismuth-based Bi2S3/Bi2MoO6 S-scheme heterojunction for ultrafast photocatalytic removal of Cr(VI) - Xu Xing; Luxin Zhang; Yue Ren; Yunfeng Li; Han Yu; Weiwei Shi (Journal of Environmental Chemical Engineering, 2024)

Study on formation of methane hydrate in rotating packed bed - Jian-Lu Zhu; Nan Li; Yu-Xing Li; Wu-Chang Wang; Guang-Chun Song; Hui Han; Yun-Fei Wang (Fuel, 2024)

Integration of genome-wide association and genomic prediction for dissecting seed protein and amino acid in foxtail millet - Xiongwei Zhao; Yanhua Cao; Litao Shao; Jie Zhang; Jian Cui; Jun Shu; Juanling Wang; Mingjing Huang; Jianhua Gao; Xingchun Wang; Xukai Li; Guofang Xing; et al. (Field Crops Research, 2024)

Rhenium(I) coordinated carbon nitride as type II immunogenic cell death inducers for enhancing photoimmunotherapy against triple-negative breast cancer - Fangmian Wei; Jinzhe Liang; Zhushuang Tan; Shunxin Tang; Han Xu; Hong Liang; Xing-Can Shen; Hui Chao (Chemical Engineering Journal, 2024)

Defect regulation of a distinctive synthetic Eu2+-doped SiAlON S-phase towards controllable spectra and thermal quenching for white-light-emitting diode - Wanying Geng; Xing Han; Zhengyue Sun; Anzheng Wang; Jinlei Zhao; Xufeng Zhou (Chemical Engineering Journal, 2024)

Microbial community evolution and individual-based model validation of biofilms in single-stage partial nitrification/anammox system - Baohong Han; Wei Xing; Zhifeng Hu; Qianqian Tian; Jingjing Zhang; Xiangyu Han; Ning Mei; Xingcheng Zhao; Hong Yao (Bioresource Technology, 2024)

Natural ventilation in vernacular architecture: A systematic review of bioclimatic ventilation design and its performance evaluation - Yongjie Pan; Wenzhou Zhong; Xing Zheng; Han Xu; Tong Zhang (Building and Environment, 2024)

Nrf2-mediated ferroptosis of spermatogenic cells involved in male reproductive toxicity induced by polystyrene nanoplastics in mice - Xufeng Fu; Hang Han; Hong Yang; Bo Xu; Wenjie Dai; Ling Liu; Tiantian He; Xing Du; Xiuying Pei (Journal of Zhejiang University-SCIENCE B, 2024)

Low-cost and high-safety montmorillonite-based solid electrolyte for lithium metal batteries - Shusen Zhou; Zhangkuo Han; Xiaofei Wang; Xin Liu; Huiying Hao; Jie Xing; Jingjing Dong; Hao Liu; Libing Liao (Applied Clay Science, 2024)

Carbon fluxes of China's coastal wetlands and impacts of reclamation and restoration - Weizhi Lu; Jingfeng Xiao; Haiqiang Gao; Qingyu Jia; Zhengjie Li; Jie Liang; Qinghui Xing; Dehua Mao; Hong Li; Xiaojing Chu; Hui Chen; Haiqiang Guo; et al. (Global Change Biology, 2024)
Coastal wetlands play an important role in regulating atmospheric carbon dioxide (CO 2 ) concentrations and contribute significantly to climate change mitigation. However, climate change, reclamation, and restoration have been causing substantial changes in coastal wetland areas and carbon exchange in China during recent decades. Here we compiled a carbon flux database consisting of 15 coastal wetland sites to assess the magnitude, patterns, and drivers of carbon fluxes and to compare fluxes among contrasting natural, disturbed, and restored wetlands. The natural coastal wetlands have the average net ecosystem exchange of CO 2 (NEE) of −577 g C m −2 year −1 , with −821 g C m −2 year −1 for mangrove forests and −430 g C m −2 year −1 for salt marshes. There are pronounced latitudinal patterns for carbon dioxide exchange of natural coastal wetlands: NEE increased whereas gross primary production (GPP) and respiration of ecosystem decreased with increasing latitude. Distinct environmental factors drive annual variations of GPP between mangroves and salt marshes; temperature was the dominant controlling factor in salt marshes, while temperature, precipitation, and solar radiation were co‐dominant in mangroves. Meanwhile, both anthropogenic reclamation and restoration had substantial effects on coastal wetland carbon fluxes, and the effect of the anthropogenic perturbation in mangroves was more extensive than that in salt marshes. Furthermore, from 1980 to 2020, anthropogenic reclamation of China's coastal wetlands caused a carbon loss of ~3720 Gg C, while the mangrove restoration project during the period of 2021–2025 may switch restored coastal wetlands from a carbon source to carbon sink with a net carbon gain of 73 Gg C. The comparison of carbon fluxes among these coastal wetlands can improve our understanding of how anthropogenic perturbation can affect the potentials of coastal blue carbon in China, which has implications for informing conservation and restoration strategies and efforts of coastal wetlands.

Species distribution modeling combined with environmental DNA analysis to explore distribution of invasive alien mosquitofish (Gambusia affinis) in China - Xu Han; Jinxiao Chen; Lang Wu; Guo Zhang; Xiaoteng Fan; Tao Yan; Long Zhu; Yongjing Guan; Linjun Zhou; Tingting Hou; Xue Xue; Xiangju Li; et al. (Environmental Science and Pollution Research, 2024)

Pathogenicity and horizontal transmission evaluation of a novel isolated African swine fever virus strain with a three-large-fragment-gene deletion - Han Gao; Dongdong Di; Qianwen Wu; Jie Li; Xing Liu; Zhiying Xu; Sijia Xu; Chengyu Wu; Lang Gong; Yankuo Sun; Guihong Zhang; Hongjun Chen; et al. (Veterinary Microbiology, 2024)

African swine fever virus maintains de novo global cellular protein synthesis and inhibits stress granules formation via dephosphorylating eIF2α - Han Gao; Xiaopeng Gao; Xing Liu; Yizhuo Luo; Jianhao Zhong; Jing Liu; Luling Yan; Heng Wang; Lang Gong; Guihong Zhang; Zezhong Zheng; Yankuo Sun (Veterinary Microbiology, 2024)

Settlement transfer mechanism of CFG piles for strengthening high-speed railway subgrades induced by twin shield tunnelling undercrossing - Beiyu Wu; Xing-Tao Lin; Dong Su; Kaihang Han; Xiangsheng Chen (Tunnelling and Underground Space Technology, 2024)

Microplastics affect mosquito from aquatic to terrestrial lifestyles and are transferred to mammals through mosquito bites - Jian-hang Li; Xiao-hui Liu; Guo-rui Liang; He-ting Gao; Si-han Guo; Xin-yu Zhou; Dan Xing; Teng Zhao; Chun-xiao Li (Science of The Total Environment, 2024)

Neurotoxic effects induced by flunitrazepam and its metabolites in zebrafish: Oxidative stress, apoptosis, and histone hypoacetylation - Yingjun Qin; Yajing Huang; Wenting Lin; Rui Huang; Kan Li; Xing Han; Yuan Ren (Science of The Total Environment, 2024)

Contrasting responses of relationship between solar-induced fluorescence and gross primary production to drought across aridity gradients - Ruonan Qiu; Ge Han; Xing Li; Jingfeng Xiao; Jiangong Liu; Songhan Wang; Siwei Li; Wei Gong (Remote Sensing of Environment, 2024)

Diffusion kinetic processes and release risks of trace metals in plateau lacustrine sediments - Xiang Gu; Xiaotong Han; Peng Xing; Di Xu; Shiqiang Wan; Qinglong L. Wu; Fengchang Wu (Journal of Hazardous Materials, 2024)

A study on visual impact assessment of the enclosing wall entourage of Chinese traditional private garden - Zhongjv Yang; Chenping Han; Tao Gu; Lin Zhang; Guanjun Li; Jingjing Zhao; Xing Huang (Environmental Impact Assessment Review, 2024)

Mechanical interlocking induced emission in two-dimensional covalent organic frameworks - Ruo-Meng Zhu; Wang-Kang Han; Yong Liu; Jia-Xing Fu; Jing-Dong Feng; Jinfang Zhang; Huan Pang; Zhi-Guo Gu (Chemical Engineering Journal, 2024)

The multifunctionality of soil aggregates is related to the complexity of aggregate microbial community during afforestation - Qi Zhang; Hanyu Liu; Yueqi Liang; Yaoyue Liang; Yongtao Zhao; Zhengchen Wang; Yuze Li; Weichao Liu; Xing Wang; Gaihe Yang; Chengjie Ren; Wei Zhang; et al. (CATENA, 2024)

Biogeochemical cycle and isotope fractionation of copper in plant–soil systems: a review - Xiaodi Zheng; Guilin Han; Zhaoliang Song; Bin Liang; Xing Yang; Changxun Yu; Dong-Xing Guan (Reviews in Environmental Science and Bio/Technology, 2024)

Three-dimensional Mg Al layered double hydroxide decorated reduced graphene oxide nanocomposite: An efficient adsorbent for the removal of methylene blue and ciprofloxacin - Xing-Wei Han; Shuai Guo; Xue Gao; Chong Lu; Sijia Wang (Applied Clay Science, 2024)

Synergistic polyploidization and long‐distance dispersal enable the global diversification of yellowcress herbs - Ting‐Shen Han; Chih‐Chieh Yu; Quan‐Jing Zheng; Seisuke Kimura; Renske E. Onstein; Yao‐Wu Xing (Global Ecology and Biogeography, 2024)
Aim Long‐distance dispersal (LDD) plays an important role in shaping the distribution of global biodiversity. Polyploidy could favour invasion and thereby facilitate LDD. However, how and to what extent polyploidy interacts with LDD remain unclear. Here, we test the putative role of polyploidy in the global dispersal of a cosmopolitan genus Rorippa . Location Global. Time Period Late Miocene to present. Major Taxa Studied Rorippa Scop., Brassicaceae. Methods We traced the biogeographical and speciation history for 17 diploids and 41 polyploids of Rorippa using variation from plastid genomes and multiple nuclear loci. The ploidy role in dispersal rate difference was demonstrated using trait‐dependent biogeographical modelling. Results LDD shaped the amphitropical disjunction of Rorippa , during which polyploids showed higher dispersal rates than those of diploids, with 5.6× increase under the best‐fitted model. Five diploids and 21 polyploids were identified as products of transoceanic speciation events. Polyploidy‐involved LDD was more common in terms of polyploidization following LDD than those preceding LDD. Main Conclusions We demonstrate that polyploidy would be not only a driver but also a responder of LDD in Rorippa , highlighting a synergistic relationship between them. Our results provide a framework to uncover the biogeographical consequences of polyploidization and the joint roles of polyploidy and LDD in shaping the distribution of biodiversity.

The dual roles of dissimilatory iron reduction in the carbon cycle: The “iron mesh” effect can increase inorganic carbon sequestration - Cheng Zhao; Fan Xun; Biao Li; Xiaotong Han; Huan Liu; Yingxun Du; Qinglong L. Wu; Peng Xing (Global Change Biology, 2024)
Dissimilatory iron reduction (DIR) can drive the release of organic carbon (OC) as carbon dioxide (CO 2 ) by mediating electron transfer between organic compounds and microbes. However, DIR is also crucial for carbon sequestration, which can affect inorganic‐carbon redistribution via iron abiotic–phase transformation. The formation conditions of modern carbonate‐bearing iron minerals (IC Fe ) and their potential as a CO 2 sink are still unclear. A natural environment with modern IC Fe , such as karst lake sediment, could be a good analog to explore the regulation of microbial iron reduction and sequential mineral formation. We find that high porosity is conducive to electron transport and dissimilatory iron‐reducing bacteria activity, which can increase the iron reduction rate. The iron‐rich environment with high calcium and OC can form a large sediment pore structure to support rapid DIR, which is conducive to the formation and growth of IC Fe . Our results further demonstrate that the minimum DIR threshold suitable for IC Fe formation is 6.65 μmol g −1 dw day −1 . DIR is the dominant pathway (average 66.93%) of organic anaerobic mineralization, and the abiotic‐phase transformation of Fe 2+ reduces CO 2 emissions by ~41.79%. Our findings indicate that as part of the carbon cycle, DIR not only drives mineralization reactions but also traps carbon, increasing the stability of carbon sinks. Considering the wide geographic distribution of DIR and IC Fe , our findings suggest that the “iron mesh” effect may become an increasingly important vector of carbon sequestration.

The different roles of fluid conduits for marine gas hydrate systems: A global review - Ying Xia; Jinxiu Yang; Wei Zhang; Wei Wei; Weifeng Han; Lanchang Xing; Jinlei Xia (International Geology Review, 2024)

Suspected sources of microplastics and nanoplastics: Contamination from experimental reagents and solvents - Yingnan Liu; Jie Han; Yanhua Wang; Aoze Li; Jian Zhao; Yu Su; Lezu Shen; Baoshan Xing (Water Research, 2024)

Simultaneous biogas upgrading and medium-chain fatty acids production using a dual membrane biofilm reactor - Kai-Kai Wu; Lei Zhao; Zi-Han Wang; Zhong-Fang Sun; Jie-Ting Wu; Chuan Chen; De-Feng Xing; Shan-Shan Yang; Ai-Jie Wang; Yi-Feng Zhang; Nan-Qi Ren (Water Research, 2024)

Middle to late Eocene charophytes from the Gaize Basin in central Tibet - Yi Xing; Sha Li; Bowen Song; Gaolei Jiang; Yi Wei; Fang Han; Kexin Zhang (Review of Palaeobotany and Palynology, 2024)

Study on the dynamic characteristics of thermal oxidation deposition of aviation kerosene under supercritical pressure - Jiahao Xing; Ruitian Yu; Huaizhi Han; Xuanyang Zou (Fuel, 2024)

Chalcones from plants cause toxicity by inhibiting human and rat 11β-hydroxysteroid dehydrogenase 2: 3D-quantitative structure-activity relationship (3D-QSAR) and in silico docking analysis - Hang Lin; Ming Su; Chao Wen; Yunbing Tang; Huitao Li; Yandan Wu; Ren-shan Ge; Xing-wang Li; Han Lin (Food and Chemical Toxicology, 2024)

An improved re-entrant honeycomb with programmable densification and multistage energy-absorbing performance - Wei Zhong Jiang; Xing Chi Teng; Xi Hai Ni; Xue Gang Zhang; Xian Cheng; Wei Jiang; Dong Han; Yi Zhang; Xin Ren (Engineering Structures, 2024)

Intermolecular π-π stacking of oligomeric naphthalene cathodes facilitate high performance aluminum ion battery - Dandan Wang; Lianming Zhao; Yongpeng Cui; Yanfu Tong; Xuejin Li; Pengyun Liu; Haoyu Hu; Jun Nan; Wei Wu; Han Xu; Zifeng Yan; Eslam Sheha; et al. (Chemical Engineering Journal, 2024)

Modulating electronic confinement and structural distortion of multiple resonance emitters enables high-performance ultrapure blue OLED - Baoxi Li; Jingli Lou; Baijun Zhang; Lu Liu; Xin He; He Xu; Xing Feng; Han Zhang; Zhiming Wang; Ben Zhong Tang (Chemical Engineering Journal, 2024)

Fabrication of robust mechanical NiCo nanocubes for lithium metal anode with superior high rate performance - Yi-Han Song; Yan-Fei Li; Jian Lin; Guo-Duo Yang; Xing-Long Wu; Jing-Ping Zhang; Hai-Zhu Sun; Liang Zhao (Chemical Engineering Journal, 2024)

Linking the soil carbon pool management index to ecoenzymatic stoichiometry and organic carbon functional groups in abandoned land under climate change - Xing Wang; Fang Chen; Jianjian Liu; Zhengchen Wang; Zhenjiao Zhang; Xiangyang Li; Qi Zhang; Weichao Liu; Hanyu Liu; Jia Zeng; Chengjie Ren; Gaihe Yang; et al. (CATENA, 2024)

Integrated biogas upgrading and medium-chain fatty acids production for more efficient resource recovery - Kai-Kai Wu; Lei Zhao; Zi-Han Wang; Zhong-Fang Sun; Chuan Chen; De-Feng Xing; Yi-Feng Zhang; Nan-Qi Ren (Bioresource Technology, 2024)

A Study on Mechanical Behavior of Intact Granite Through a Sound Simulation Using Flat-Jointed Contact - Rui Zhang; Cheng Zhao; Jinquan Xing; Jialun Niu; Qinyuan Liang; Yunshan Han (Rock Mechanics and Rock Engineering, 2024)

Investigating the Causes of a Rapid Gravity Decrease at the Luzhou Observatory - Zhongya Li; Yong Wang; Lelin Xing; Minzhang Hu; Yufei Han; Jiansheng Yu; Chi Xiao; Fan Wang; Jiapei Wang; Jian Wang; Xinlin Zhang (Pure and Applied Geophysics, 2024)

Monoclonal Antibody Targeting CGRP Relieves Cisplatin-Induced Neuropathic Pain by Attenuating Neuroinflammation - Shun Xie; Zhenfang Gao; Jiale Zhang; Cong Xing; Yanxin Dong; Lanyin Wang; Zhiding Wang; Yuxiang Li; Ge Li; Gencheng Han; Taiqian Gong (Neurotoxicity Research, 2024)

Peroxisome Proliferator-Activated Receptor-γ Coactivator-1α in the Spotlight with Multiple Sclerosis - Ya-Na Yang; Mao-Qing Zhang; Feng-Lin Yu; Bing Han; Ming-Yue Bao; Yan He; Xing Li; Yuan Zhang (Neuroscience Bulletin, 2024)

Integrating bulk-RNA sequencing and single-cell sequencing analyses to characterize adenosine-enriched tumor microenvironment landscape and develop an adenosine-related prognostic signature predicting immunotherapy in lung adenocarcinoma - Tao Han; Jing Wu; Yafeng Liu; Jiawei Zhou; Rui Miao; Jianqiang Guo; Zhi Xu; Yingru Xing; Ying Bai; Dong Hu (Functional & Integrative Genomics, 2024)

Saturation Estimation with Complex Electrical Conductivity for Hydrate-Bearing Clayey Sediments: An Experimental Study - Lanchang Xing; Shuli Zhang; Huanhuan Zhang; Chenyutong Wu; Bin Wang; Liyun Lao; Wei Wei; Weifeng Han; Zhoutuo Wei; Xinmin Ge; Shaogui Deng (Journal of Ocean University of China, 2024)

Dissolved organic carbon and dissolved oxygen determine the nitrogen removal rate constant in small water bodies of intensive agricultural region - Xing Yan; Haojie Han; Xiaohan Li; Jiong Wen; Xiangmin Rong; Yongqiu Xia; Xiaoyuan Yan (Agriculture, Ecosystems & Environment, 2024)

Reducing strategic uncertainty in transportation networks by personalized routing advice: A route-choice laboratory experiment - Xiao Han; Qiuxia Sun; Yingying Xing; Zi-You Gao; H. Michael Zhang (Travel Behaviour and Society, 2024)

Participation of WD repeat-containing protein 54 (WDR54) in rat sperm-oocyte fusion through interaction with both IZUMO1 and JUNO - Xiong Lai; Ruizhuo Liu; Mengyu Li; Yaochun Fan; Hongxia Li; Guotao Han; Ruijie Guo; Hairui Ma; Huimin Su; Wanjin Xing (Theriogenology, 2024)

Soil deterioration due to long-term grazing of desert-steppe promotes stress-tolerant ecological strategies in plants - Jiahua Zheng; Qi Wang; Shuai Yuan; Bin Zhang; Feng Zhang; Shaoyu Li; Jirong Qiao; Yunga Wu; Jiaqing Xing; Guodong Han; Jun Zhang; Mengli Zhao (Science of The Total Environment, 2024)

Variability in methylmercury exposure across migratory terrestrial bird species: Influencing factors, biomagnification and potential risks - Lingling Xing; Tong Zhang; Xuetao Han; Maowen Xie; Le Chao; Jingrui Chen; Xiaoming Yu; Jiahong Zhou; Guoxiang Yu; Jiachen Sun (Science of The Total Environment, 2024)

Integrated ultra-low PtIr catalyst coated membrane toward efficient proton exchange membrane water electrolyzers - Jiaqi Qin; Yang Lv; Guangqi Han; Huiyuan Liu; Yongpeng Li; Hongyan Zhang; Xiaoyu Zhou; Keran Xing; Tiantian Li; Chongyun Sun; Chunxiao Wang; Qiang Zhou; et al. (Chemical Engineering Journal, 2024)

Boosting promote C2 products formation in electrochemical CO2 reduction reaction via phosphorus-enhanced proton feeding - Shitao Han; Wei Xia; Shuaiqiang Jia; Jiapeng Jiao; Ting Yao; Xue Dong; Min Wang; Jianxin Zhai; Jiahao Yang; Yijun Xie; Xueqing Xing; Haihong Wu; et al. (Chemical Engineering Journal, 2024)

An effective method for fabricating crosslinked multilayer biomembranes with excellent stability and methanol resistance - Shuangling Zhong; Bin Wang; Minghui Wang; Xudan Song; Jiayu Liu; Ruida Xie; Xing Han; Xuejun Cui (Carbohydrate Polymers, 2024)

Nitrogen source affects non-aeration microalgal-bacterial biofilm growth progression and metabolic function during greywater treatment - Jiake Li; Beibei Wu; Meng Xu; Xuan Han; Yinuo Xing; Yu Zhou; Mengyao Ran; Yun Zhou (Bioresource Technology, 2024)

Targeting ferroptosis and ferritinophagy: new targets for cardiovascular diseases - Yi Luan; Yang Yang; Ying Luan; Hui Liu; Han Xing; Jinyan Pei; Hengdao Liu; Bo Qin; Kaidi Ren (Journal of Zhejiang University-SCIENCE B, 2024)

Impact of hemoglobin adducts of ethylene oxide on the prevalence and prognosis of chronic kidney disease in US adults: an analysis from NHANES 2013–2016 - Shuang Wu; Yan-min Yang; Jun Zhu; Lu-lu Wang; Wei Xu; Si-qi Lyu; Juan Wang; Xing-hui Shao; Han Zhang (Environmental Science and Pollution Research, 2023)

Forging Fenton-like system to functionalize electron/hole enrichment regions for ATZ photocatalytic degradation - Xinyu Xiao; Xing Wang; Chao Liu; Ying Han (Chemosphere, 2023)

Demethylation of ethanol organosolv lignin by Na2SO3 for enhancing antioxidant performance - Ying Han; Zihao Ma; Xing Wang; Yuanyuan Sheng; Yu Liu (Sustainable Chemistry and Pharmacy, 2023)

The mediation role of blood lipids on the path from air pollution exposure to MAFLD: A longitudinal cohort study - Xinyu Han; Bing Guo; Lele Wang; Kejun Chen; Hanwen Zhou; Shourui Huang; Huan Xu; Xianmou Pan; Jinyao Chen; Xufang Gao; Zhenghong Wang; La Yang; et al. (Science of The Total Environment, 2023)

Corrigendum to “Utilization of E-commerce for fossil fuels allocation and green recovery” [Resour. Pol. 85B (2023) 103980] - Jinghang Yang; Yuanyuan Xing; Yuanyuan Han (Resources Policy, 2023)

Flotation chemistry of scheelite and its practice: A comprehensive review - Zhao Wei; Wei Sun; Haisheng Han; Xiahui Gui; Yaowen Xing (Minerals Engineering, 2023)

Divergent patterns and drivers of leaf functional traits of Robinia pseudoacacia and Pinus tabulaeformis plantations along a precipitation gradient in the Loess plateau, China - Zhenjiao Zhang; Xing Wang; Shujuan Guo; Zhenxia Li; Mengfan He; Yunlong Zhang; Guixing Li; Xinhui Han; Gaihe Yang (Journal of Environmental Management, 2023)

Silver nanoparticles/graphene oxide arranged on polytetrafluoroethylene substrate hydrophilic modified with TiO2 to construct efficient air purification material - Chen Chen; Wenping Li; Xiaohui Liu; Junjie Yu; Shijun Xing; Jiazhi Yang; Qiaofeng Han (Journal of Environmental Chemical Engineering, 2023)

Improving antifouling functions of titanium alloys by robust slippery liquid-infused porous surfaces with tailored multiscale structures - Zeping Zhang; Yun Bai; Rizheng Han; Qiang Yu; Rui Yang; Xing Zhang (Chemical Engineering Journal, 2023)

Exogenous hydrogen supply improves in-situ biogas upgrading of sewage sludge: Performance and mechanisms - Zhong-Fang Sun; Lei Zhao; Jie-Ting Wu; Zi-Han Wang; Kai-Kai Wu; Chuan Chen; De-Feng Xing; Dong-Mei Liu; Shan-Shan Yang; Ai-jie Wang; Nan-Qi Ren (Chemical Engineering Journal, 2023)

Field simulation experiment on the relationships between hydrodynamics and soil detachment rate in formed rills - Jie Zhang; Xiaoyan Chen; Tingting Tao; Wei Han; Xing Wang; Fulin Luo; Wenhao Tan; Lingyong Kong; Tao Feng; Pingzong Zhu (CATENA, 2023)

Chemical constituents from Vitex negundo var. cannabifolia (Sieb. et Zucc.) Hand.-Mazz. (Lamiaceae) and their chemotaxonomic significance - Muhammad Aurang Zeb; Peng-Yun Yang; De-Wen Bi; Wen-Chao Tu; Xiao-Li Li; Rui-Han Zhang; Xing-Jie Zhang; Wei-Lie Xiao (Biochemical Systematics and Ecology, 2023)

A resilience assessment framework for existing underground structures under adjacent construction disturbance - Kaihang Han; Dongmei Zhang; Xiangsheng Chen; Dong Su; Jiann-Wen Woody Ju; Xing-Tao Lin; Hongzhi Cui (Tunnelling and Underground Space Technology, 2023)

Abundant and rare fungal taxa exhibit different patterns of phylogenetic niche conservatism and community assembly across a geographical and environmental gradient - Xing Wang; Zhengchen Wang; Weichao Liu; Hanyu Liu; Qi Zhang; Jia Zeng; Chengjie Ren; Gaihe Yang; Zekun Zhong; Xinhui Han (Soil Biology and Biochemistry, 2023)

Flunitrazepam induces neurotoxicity in zebrafish through microbiota-gut-brain axis - Wenting Lin; Kan Li; Yingjun Qin; Xing Han; Xiaohui Chen; Yuan Ren (Science of The Total Environment, 2023)

A tholeiitic damp parental magma for the Miyi mafic intrusion: Implications for water heterogeneity in the Emeishan large igneous province - Ying Xia; Yue Chen; An-Qing Chen; Hui-Juan Peng; Rui-Qiang Wang; Dong-Xing Han (Lithos, 2023)

Bibliometric analysis of publications on biodegradation of plastics: Explosively emerging research over 70 years - Shan-Shan Yang; Wei-Min Wu; Ji-Wei Pang; Lei He; Meng-Qi Ding; Mei-Xi Li; Yi-Lin Zhao; Han-Jun Sun; De-Feng Xing; Nan-Qi Ren; Jun Yang; Craig S. Criddle; et al. (Journal of Cleaner Production, 2023)

How low-income populations work determines carbon footprint reduction from remote work - Yongting Zhang; Haoying Han; Chao Fan; Xing Su (Journal of Cleaner Production, 2023)

A new method for pre-enrichment of gallium and lithium based on mode of occurrence in coal gangue from Antaibao surface mine, Shanxi Province, China - Shiqi Dai; Fengshuai Sun; Lei Wang; Lanhao Wang; Rui Zhang; Han Guo; Yaowen Xing; Xiahui Gui (Journal of Cleaner Production, 2023)

Natural restoration exhibits better soil bacterial network complexity and stability than artificial restoration on the Loess Plateau, China - Xing Wang; Zhengchen Wang; Zhenjiao Zhang; Yang Yang; Carolyn R. Cornell; Weichao Liu; Qi Zhang; Hanyu Liu; Jia Zeng; Chengjie Ren; Gaihe Yang; Zekun Zhong; et al. (Journal of Environmental Management, 2023)

The metabolism of membrane lipid participates in the occurrence of chilling injury in cold-stored banana fruit - Qian Li; Han Lin; He-tong Lin; Meng-shi Lin; Hui Wang; Wei Wei; Jian-ye Chen; Wang-jin Lu; Xing-feng Shao; Zhong-qi Fan (Food Research International, 2023)

Strategy of functional nucleic acids-mediated isothermal amplification for detection of foodborne microbial contaminants: A review - Jie Zhou; Teng-Yu Wang; Zhi Lan; Han-Jie Yang; Xing-Jian Ye; Rui Min; Zhao-Hui Wang; Qing Huang; Jing Cao; Yu-E Gao; Wen-Long Wang; Xiu-Lan Sun; et al. (Food Research International, 2023)

Precise classification and regional delineation of maturity groups in soybean cultivars across China - Wenwen Song; Luping Liu; Shi Sun; Tingting Wu; Haiyan Zeng; Shiyan Tian; Bincheng Sun; Wenbin Li; Lijun Liu; Shuming Wang; Han Xing; Xin’an Zhou; et al. (European Journal of Agronomy, 2023)

Low-temperature sintering of multifunctional SiC catalytic membrane for synergistic emission control of toluene and dust - Jiahao Chen; Yiqing Zeng; Yongliang Yin; Yarong Fang; Feng Han; Ze-Xian Low; Zhaoxiang Zhong; Weihong Xing (Chemical Engineering Journal, 2023)

Multifunctional MMP9-responsive silicasomes-GelMA hydrogels with bacteria-targeting capability and tissue restoration function for chronic wound infection - Yingxian Chen; Yi Xing; Junhua Han; Suhan Liu; Xin Xiang; Jianzhong Shen; Xin Du; Xiaowei Ma (Chemical Engineering Journal, 2023)

Estimating inter-satellite link Ka-band antenna phase center offsets to improve BDS-3 satellite orbit determination - Tao Geng; Kaixuan Han; Xin Xie; Xing Wang; Feng Zhang (Advances in Space Research, 2023)

Multi-scale fusion for few-shot remote sensing image classification - Xujian Qiao; Lei Xing; Anxun Han; Weifeng Liu; Baodi Liu (International Journal of Remote Sensing, 2023)

Synergetic effects of catalyst-surface dual-electric centers and microbes for efficient removal of ciprofloxacin in water - Wu Cai; Peng Zhang; Xueci Xing; Lai Lyu; Han Zhang; Chun Hu (Water Research, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Highly efficient zinc electrode prepared by electro-deposition in a salt-induced pre-phase separation region solution - Yaoyu Yin; Yaguang Peng; Meng Zhou; Pei Zhang; Yingying Cheng; Peng Chen; Xueqing Xing; Xiaoxue Ma; Qinggong Zhu; Xiaofu Sun; Qingli Qian; Xinchen Kang; et al. (Science Bulletin, 2023)

Chemical constituents from the leaves of Cinnamomum camphora and their α-glucosidase inhibitory activities - Xing Jiang; Xi-Han Zhang; Yu-Xin Li; Kai Chen; Bin Lin; Tian-Qi Lu; Min Yang; Guang-Tong Chen; Bo-Yi Fan; Wen-Li Wang (Phytochemistry Letters, 2023)

Rice roots avoid asymmetric heavy metal and salinity stress via an RBOH-ROS-auxin signaling cascade - Han-Qing Wang; Xing-Yu Zhao; Wei Xuan; Peng Wang; Fang-Jie Zhao (Molecular Plant, 2023)

Novel multiple ligand metal-group collectors assembled from benzohydroxamic acid and cupferron - Zhao Wei; Haisheng Han; Wei Sun; Xiahui Gui; Yaowen Xing (Minerals Engineering, 2023)

Incorporating a new landscape intensity indicator into landscape metrics to better understand controls of water quality and optimal width of riparian buffer zone - Haojie Han; Xing Yan; Haiwen Xie; Jie Qiu; Xianghua Li; Di Zhao; Xiaohan Li; Xiaoyuan Yan; Yongqiu Xia (Journal of Hydrology, 2023)

Host-derived peptide signals regulate Pseudomonas aeruginosa virulence stress via the ParRS and CprRS two-component systems - Ning-Lin Zhao; Zi-Qi Zhu; Han-Zhong Feng; Ying-Jie Song; Qin Huang; Xing-Yu Mou; Cheng Nong; Yong-Xing He; Rui Bao (Journal of Hazardous Materials, 2023)

A novel method for solidification/stabilization of MSWI fly ash by graphene nanoplatelets synergistic alkali-activated technology - Tianru Li; Baomin Wang; Xiong Zhang; Xiao Han; Yunqing Xing; Chengcheng Fan; Ze Liu (Journal of Environmental Chemical Engineering, 2023)

Calcium-looping coupling methane partial oxidation and dry reforming process for integrated CO2 capture and conversion: Regulable H2/CO molar ratio and excellent coke deposition-resistant - Lifei Wei; Rui Han; Shuang Xing; Yang Wang; Zhiyong Li; Qingling Liu (Chemical Engineering Journal, 2023)

Photothermal cyclic self-healing coating with long-term corrosion protection based on bifunctional graphene - Han Zhang; Wen Sun; Lida Wang; Shiheng Ma; Wenxiang Xing; Kun Liang; Guichang Liu (Chemical Engineering Journal, 2023)

The contribution of microbial necromass carbon to soil organic carbon in soil aggregates - Qi Zhang; Xiangyang Li; Jianjian Liu; Jiayi Liu; Lei Han; Xing Wang; Hanyu Liu; Miaoping Xu; Gaihe Yang; Chengjie Ren; Xinhui Han (Applied Soil Ecology, 2023)

Acclimation of electroactive biofilms under different operating conditions: comprehensive analysis from architecture, composition, and metabolic activity - Han Ma; Xing Dong; Yi Yan; Ke Shi; Hao Wang; Haoyun Lu; Jianliang Xue; Yanlu Qiao; Dongle Cheng; Qing Jiang (Environmental Science and Pollution Research, 2023)

New furofuran and tetrahydrofuran lignans from the flower buds of Magnolia biondii Pamp and their antiallergic effects - Xing Zhang; Xi-Min Wu; Lin-Hang Han; Fei Qian; Liu-Qiang Zhang; Yi-Ming Li (Natural Product Research, 2023)

Serum exosomal hsa_circRNA_0001842 is the potential biomarker for diagnosing lower limb vascular disease in type 2 diabetes mellitus - Qian-Qian Liu; Xing-Hui Liu; Hai-Ming Wang; Li-Min Xu; Xiao-Jing Zhao; Shu-Guang Han; Zuo-Hua Lu (Journal of Genetics, 2023)

Telomere length, oxidative stress and their links with growth and survival in a lizard facing climate warming - Qiong Zhang; Xing-Zhi Han; Pablo Burraco; Xin Hao; Li-Wei Teng; Zhen-Sheng Liu; Fu-Shun Zhang; Wei-Guo Du (Science of The Total Environment, 2023)

PbrWRKY70 increases pear (Pyrus bretschneideri Rehd) black spot disease tolerance by negatively regulating ethylene synthesis via PbrERF1B-2 - Caihua Xing; Qiming Chen; Qinghai Qiao; Shenao Gu; Xiangyu Cheng; Huizhen Dong; Likun Lin; Feng Zhang; Chenyang Han; Zan Zhang; Hao Yin; Kaijie Qi; et al. (Plant Science, 2023)

Hydrothermal alteration of basalts in the ultramafic-associated Tianxiu Vent Field, Carlsberg Ridge - Peng Zhou; Xiqiu Han; Yejian Wang; Xueting Wu; Tong Zong; Xing Yu; Jiqiang Liu; Honglin Li; Zhongyan Qiu (Marine Geology, 2023)

Identification of Brassica rapa BrEBF1 homologs and their characterization in cold signaling - Wangze Wu; Haobo Yang; Juan Shen; Peng Xing; Xueyan Han; Yun Dong; Guofan Wu; Sheng Zheng; Kun Gao; Ning Yang; Lina Zhang; Yujun Wu (Journal of Plant Physiology, 2023)

Self-purification of actual wastewater via microbial-synergy driving of catalyst-surface microelectronic field: A pilot-scale study - Xueci Xing; Lai Lyu; Zhen Yan; Han Zhang; Tong Li; Muen Han; Zesong Li; Fagen Zhang; Zhu Wang; Shuguang Wang; Yiguo Hong; Chun Hu (Journal of Hazardous Materials, 2023)

Low-carbon economic dispatch of Photovoltaic-Carbon capture power plant considering deep peak regulation - Xing Guo; Yanfen Liao; Gen Li; Yixiao Han; Xiaoqian Ma (Journal of Cleaner Production, 2023)

Alleviating eutrophication by reducing the abundance of Cyanophyta due to dissolved inorganic carbon fertilization: Insights from Erhai Lake, China - Chaowei Lai; Zhen Ma; Zaihua Liu; Hailong Sun; Qingchun Yu; Fan Xia; Xuejun He; Qian Bao; Yongqiang Han; Xing Liu; Haibo He (Journal of Environmental Sciences, 2023)

Strategies for sensor virtual in-situ calibration in building energy system: Sensor evaluation and data-driven based methods - Jiteng Li; Peng Wang; Xing Han; Tianyi Zhao; Sungmin Yoon (Energy and Buildings, 2023)

Distributions, influencing factors and fluxes of dissolved methane in the North Yellow Sea, near the Yalu River estuary, China - Zongcai He; Xuemei Xu; Yingying Hu; Jianbo Han; Xiaomeng Wang; Qinghui Xing; Xinyi Wang; Hong Chen (Continental Shelf Research, 2023)

Structural design of a hyperbranched chitosan-based bioplastic with excellent strength, antibacterial, and UV shielding performance - Shicun Jin; Lihong Xiong; Yuqing Yu; Jieping Xing; Jianzhang Li; Jingquan Han; Changtong Mei; Kuang Li; Huining Xiao (Chemical Engineering Journal, 2023)

Review of triazole scaffolds for treatment and diagnosis of Alzheimer's disease - Qi Li; Shulei Qi; Jinxin Liang; Yuqing Tian; Siyu He; Qinghong Liao; Shuaishuai Xing; Lingfei Han; Xuehong Chen (Chemico-Biological Interactions, 2023)

Mechanisms of Epichloë bromicola to Promote Plant Growth and Its Potential Application for Coix lacryma-jobi L. Cultivation - Xing-Guang Xie; Wei-Lan Lu; Kun-Miao Feng; Cheng-Jian Zheng; Yang Yang; Min Jia; Yi-Sang Wu; Yan-Zhang Shi; Ting Han; Lu-Ping Qin (Current Microbiology, 2023)

The East Asian wild apples, Malus baccata (L.) Borkh and Malus hupehensis (Pamp.) Rehder., are additional contributors to the genomes of cultivated European and Chinese varieties - Xilong Chen; Amandine Cornille; Na An; Libo Xing; Juanjuan Ma; Caiping Zhao; Yibin Wang; Mingyu Han; Dong Zhang (Molecular Ecology, 2023)
The domestication process in long‐lived plant perennials differs dramatically from that of annuals, with a huge amount of genetic exchange between crop and wild populations. Though apple is a major fruit crop grown worldwide, the contribution of wild apple species to the genetic makeup of the cultivated apple genome remains a topic of intense study. We used population genomics approaches to investigate the contributions of several wild apple species to European and Chinese rootstock and dessert genomes, with a focus on the extent of wild–crop gene flow. Population genetic structure inferences revealed that the East Asian wild apples, Malus baccata (L.) Borkh and M . hupehensis (Pamp.), form a single panmictic group, and that the European dessert and rootstock apples form a specific gene pool whereas the Chinese dessert and rootstock apples were a mixture of three wild gene pools, suggesting different evolutionary histories of European and Chinese apple varieties. Coalescent‐based inferences and gene flow estimates indicated that M . baccata – M . hupehensis contributed to the genome of both European and Chinese cultivated apples through wild‐to‐crop introgressions, and not as an initial contributor as previously supposed. We also confirmed the contribution through wild‐to‐crop introgressions of Malus sylvestris Mill. to the cultivated apple genome. Apple tree domestication is therefore one example in woody perennials that involved gene flow from several wild species from multiple geographical areas. This study provides an example of a complex protracted process of domestication in long‐lived plant perennials, and is a starting point for apple breeding programmes.

Association of long-term exposure to ambient PM2.5 and its constituents with gut microbiota: Evidence from a China cohort - Sicheng Li; Bing Guo; Ke Dong; Shourui Huang; Jialong Wu; Hanwen Zhou; Kunpeng Wu; Xinyu Han; Xian Liang; Xiaofang Pei; Haojiang Zuo; Hualiang Lin; et al. (Science of The Total Environment, 2023)

Utilization of E-commerce for fossil fuels allocation and green recovery - Jinghang Yang; Yuanyuan Xing; Yuanyuan Han (Resources Policy, 2023)

Effect of nano silica on solidification/stabilization of heavy metal in alkali-activated MSWI fly ash solidified body - Tianru Li; Baomin Wang; Xiong Zhang; Xiao Han; Yunqing Xing; Chengcheng Fan; Ze Liu (Process Safety and Environmental Protection, 2023)

Increase of carbon storage in the Qinghai-Tibet Plateau: Perspective from land-use change under global warming - Miaoni Gao; Runhong Xu; Jinlong Huang; Buda Su; Shan Jiang; Peijun Shi; Haifeng Yang; Yun Xing; Dongfang Wang; Han Jiang; Zbigniew W. Kundzewicz; Tong Jiang (Journal of Cleaner Production, 2023)

Using UHPLC-HRMS-based comprehensive strategy to efficiently and accurately screen and identify illegal additives in health-care foods - Meng-Han Ma; Jia-Ni Zhang; Xing-Ling Ma; Xing-Cai Wang; Feng-Lian Ma; Jia-Nan Liu; Yi Lv; Yong-Jie Yu; Yuanbin She (Food Research International, 2023)

Species identification of culinary spices with two-locus DNA barcoding - Meng-Yue Zhou; Ran-Ran Xing; Ke-Han Liu; Yi-Qiang Ge; Ying Chen (Food Control, 2023)

The association between chemical constituents of ambient fine particulate matter and obesity in adults: A large population-based cohort study - Shaokun Yang; Feng Hong; Sicheng Li; Xinyu Han; Jiawei Li; Xing Wang; Lin Chen; Xuehui Zhang; Xi Tan; Jingru Xu; Zhuoma Duoji; Zhuoga Ciren; et al. (Environmental Research, 2023)

Mucin2 regulated by Ho1/p38/IL-10 axis plays a protective role in polystyrene nanoplastics-mediated intestinal toxicity - Mengxing Cui; Qianmei He; Ziwei Wang; Yongjiang Yu; Huan Gao; Ziqi Liu; Honghao Peng; Han Wang; Xue Zhang; Daochuan Li; Liping Chen; Xiumei Xing; et al. (Environmental Pollution, 2023)

Star-like, dopant-free, corannulene-cored hole transporting materials for efficient inverted perovskite solar cells - Ming-Wei An; Bolin Li; Bin-Wen Chen; Zuo-Chang Chen; Han-Rui Tian; Lin-Long Deng; Xugang Guo; Zhou Xing (Chemical Engineering Journal, 2023)

Recovery of methane and acetate during ex-situ biogas upgrading via novel dual-membrane aerated biofilm reactor - Kai-Kai Wu; Lei Zhao; Xiao-Chuan Zheng; Zhong-Fang Sun; Zi-Han Wang; Chuan Chen; De-Feng Xing; Shan-Shan Yang; Nan-Qi Ren (Bioresource Technology, 2023)

Evaluation of Physiological Stress of Grass Carp Chronically Exposed to Enrofloxacin Based on IBR Index - Xu-Qian Cao; Xu Wang; Bin Liu; Shu-Wen He; Zhi-Han Cao; Shao-Ying Xing; Ping Li; Zhi-Hua Li (Water, Air, & Soil Pollution, 2023)

Chromosome-specific painting in Thinopyrum species using bulked oligonucleotides - Chen Chen; Yangshuo Han; He Xiao; Bingcan Zou; Dandan Wu; Lina Sha; Cairong Yang; Songqing Liu; Yiran Cheng; Yi Wang; Houyang Kang; Xing Fan; et al. (Theoretical and Applied Genetics, 2023)

Effects of triazine herbicide terbutryn on physiological responses and gene expression in Alexandrium catenella - Qikun Xing; Young Woo Kim; Ji-Sook Park; Young-Seok Han; Charles Yarish; Hyun Il Yoo; Jang K. Kim (Journal of Applied Phycology, 2023)

Resolvin D1 attenuates depressive-like behavior in LPS-challenged mice by promoting microglial autophagy - Wei Xiong; Han Wang; Hongyan Zhang; Yanmei Xing; Wenli Gao; Lengfeng Chen; Lixin Chen; Zhongliang Dai (Inflammopharmacology, 2023)

Contributions of abundant and rare bacteria to soil multifunctionality depend on aridity and elevation - Peng He; Ning Ling; Xiao-Tao Lü; Hai-Yang Zhang; Chao Wang; Ru-Zhen Wang; Cun-Zheng Wei; Jing Yao; Xiao-Bo Wang; Xing-Guo Han; Zhibiao Nan (Applied Soil Ecology, 2023)

Different nitrogen saturation thresholds for above‐, below‐, and total net primary productivity in a temperate steppe - Guo‐Jiao Yang; Carly Stevens; Zi‐Jia Zhang; Xiao‐Tao Lü; Xing‐Guo Han (Global Change Biology, 2023)
Identifying the thresholds for the positive responses of total net primary productivity (NPP) to nitrogen (N) enrichment is an essential prerequisite for predicting the benefits of N deposition on ecosystem carbon sequestration. However, the responses of below‐ground NPP (BNPP) to N enrichment are unknown in many ecosystems, which limits our ability to understand the carbon cycling under the scenario of increasing N availability. We examined the changes in above‐ground NPP (ANPP), BNPP, and NPP of a temperate meadow steppe across a wide‐ranging N addition gradient (0, 2, 5, 10, 20, and 50 g N m −2 year −1 ) during 5 years. Both ANPP and NPP increased nonlinearly with N addition rates. The N saturation threshold for ANPP ( T A ) and NPP ( T N ) was at the rate of 13.11 and 6.70 g N m −2 year −1 , respectively. BNPP decreased with increasing N addition when N addition rates ˃5 g N m −2 year −1 , resulting in much lower T N than T A . Soil N enrichment played a key role in driving the negative impacts of high N addition rates on BNPP, and consequently on the earlier occurrence of N saturation threshold for NPP. Our results highlight the negative effects of soil N enrichment on NPP in natural grasslands super‐saturated with N. Furthermore, by considering ANPP and BNPP simultaneously, our results indicate that previous findings from above‐ground might have over‐estimated the positive effects of N deposition on primary productivity.

Micro/nanoscale bone char alleviates cadmium toxicity and boosts rice growth via positively altering the rhizosphere and endophytic microbial community - Anqi Liang; Chuanxin Ma; Jiang Xiao; Yi Hao; Hao Li; Yaozu Guo; Yini Cao; Weili Jia; Lanfang Han; Guangcai Chen; Qian Tan; Jason C. White; et al. (Journal of Hazardous Materials, 2023)

Comparative study on the effects of heating rate on char gasification behaviors by thermogravimetric analyzer and high-temperature stage microscope under non-isothermal condition - Mengjie Liu; Cheng Zhang; Jin Bai; Xuetao Wang; Lili Xing; Xiaoming Li; Bin Han; Lingxue Kong; Zongqing Bai; Huaizhu Li; Wen Li (Fuel, 2023)

Adverse effects of titanium dioxide nanoparticles on beneficial gut bacteria and host health based on untargeted metabolomics analysis - Yanyan Wu; Xiaoqiong Cao; Hengjun Du; Xiaojing Guo; Yanhui Han; David Julian McClements; Eric Decker; Baoshan Xing; Hang Xiao (Environmental Research, 2023)

Effect of boron and nitrogen modulation in metal atoms anchoring on flower-like carbon superstructure for efficient ammonia electrosynthesis - Yanchao Zhao; Shuo Zhang; Cong Han; Qian Lu; Qiuju Fu; Huimin Jiang; Lingzhi Yang; Yanlong Xing; Qiuju Zheng; Jianxing Shen; Liting Yan; Xuebo Zhao (Chemical Engineering Journal, 2023)

Analysis and simulation of nitrogen loss during water erosion process on windward slope under wind-driven rain conditions - Miaoying An; Weiming Xing; Yuguo Han; Jinxing Zhou; Zhixu Qu; Chenyang Zhao; Pan Xu (CATENA, 2023)

A method for researching the eutrophication and N/P loads of plateau lakes: Lugu Lake as a case - Bing Zhao; Yuansi Hu; Haoran Yu; Sikai Chen; Tao Xing; Shanshan Guo; Han Zhang (Science of The Total Environment, 2023)

Nudifloids A-N, structurally diverse 3,4-seco-labdane diterpenoids from Callicarpa nudiflora with inflammatory inhibitory activity - Xue-Rong Zhao; Xiao-Rong Sun; Xing-Jie Zhang; Xue-Wen Wu; Bin Cheng; Dong-Xuan Ni; Jia-Bi Huang; Rui-Han Zhang; Xiao-Li Li; Wei-Lie Xiao (Phytochemistry, 2023)

Fabrication of Cu0-composited CuFe2O4 magnetic nanoparticles on diatomite support for efficient degradation of tetracycline hydrochloride by a Fenton-like system - Shuai Deng; Zhi Guo; Yi-Han Chen; Kang-Ping Cui; Zhao-Gang Ding; Bei Wang; Rohan Weerasooriya; Xing Chen (Journal of Environmental Chemical Engineering, 2023)

A study of flavor variations during the flaxseed roasting procedure by developed real-time SPME GC–MS coupled with chemometrics - Xing-Ling Ma; Xing-Cai Wang; Jia-Ni Zhang; Jia-Nan Liu; Meng-Han Ma; Feng-Lian Ma; Yi Lv; Yong-Jie Yu; Yuanbin She (Food Chemistry, 2023)

Methane Adsorption Characteristics Under In Situ Reservoir Conditions of the Wufeng–Longmaxi Shale in Southern Sichuan Basin, China: Implications for Gas Content Evaluation - Chao Qian; Xizhe Li; Qing Zhang; Yanchao Li; Weijun Shen; Hongchuan Xing; Pinghua Shu; Lingling Han; Yue Cui; Yize Huang (Natural Resources Research, 2023)

Effects of kaolin particle film coatings on the water-saving efficiency and fruit quality of Cabernet Sauvignon (Vitis vinifera L.) grape plants in the Ningxia region of China - Xiao Cao; Ying Wang; Zhi-Lei Wang; Xue-Lin Tian; Xing Han; Dong Wu; Fei Yao; Miao Hui; Hua Li; Hua Wang (Horticulture, Environment, and Biotechnology, 2023)

Endophytic fungus Trichoderma atroviride D16 increases tanshinone accumulation in Salvia miltiorrhiza plantlets by enhancing abscisic acid and salicylic acid signaling - Xing-Guang Xie; Ke-Xin Sheng; Wei-Lan Lu; Hao-Ran Wang; Khalid Rahman; Kun-Miao Feng; Ting Han (Symbiosis, 2023)

Experimental study on flow and heat transfer of supercritical carbon dioxide in zigzag channels with bending angle 30° for advanced nuclear systems - Sheng-hui Liu; Rui-long Liu; Yan-ping Huang; Xiao-liang Zhu; Liu Yang; Jia Tang; Bin Han; Tian-yang Xing; Xue-bin Zhao (Annals of Nuclear Energy, 2023)

Iron oxides act as an alternative electron acceptor for aerobic methanotrophs in anoxic lake sediments - Biao Li; Ye Tao; Zhendu Mao; Qiujin Gu; Yixuan Han; Baolan Hu; Hongwei Wang; Anxing Lai; Peng Xing; Qinglong L Wu (Water Research, 2023)

Decomposing the decoupling relationship between energy consumption and economic growth in China's agricultural sector - Jiaxuan Hu; Liang Chi; Liwei Xing; Han Meng; Mengshuai Zhu; Jing Zhang; Jianzhai Wu (Science of The Total Environment, 2023)

Fertilizer-induced N2O and NO emissions in tea gardens and the main controlling factors: A recent three-decade data synthesis - Haiyang Yu; Xing Han; Xuechen Zhang; Xiangtian Meng; Zhengfu Yue; Xinhui Liu; Ningguo Zheng; Yaying Li; Yongxiang Yu; Huaiying Yao (Science of The Total Environment, 2023)

Efficient degradation of tetracycline over vacancy-modified Cu-doped Bi2O2S via peroxymonosulfate activation and photocatalysis - Yonglei Xing; Xiaojing Jiang; Lei Han; Xiaoyong Jin; Gang Ni; Yage Peng; Xiaojing Yong; Xin Wang (Journal of Cleaner Production, 2023)

Phase Inversion-Based foam hydrogels for highly efficient Solar-Powered interfacial desalination - Chenyang Xing; Zihao Li; Shaohui Zhang; Jian Bang; Zhongjian Xie; Han Zhang; Zhengchun Peng (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Transcriptional profiles of TGF-β superfamily members in the lumbar DRGs and the effects of activins A and C on inflammatory pain in rats - Feng-Ming Zhang; Bing Wang; Han Hu; Ying-Ying Zhang; Hao-Hao Chen; Zuo-Jie Jiang; Mei-Xing Zeng; Xing-Jun Liu (Journal of Physiology and Biochemistry, 2023)

A Fluorescent Probe Based on the Hydrazone Schiff Base for the Detection of Zn2+ and its Application on Test Strips - Guo Xu; Shu-Jie Ma; Hua-Hong Zhang; Jing Jing; Xing-Han Chen; Xiao-Peng Zhang (Journal of Fluorescence, 2023)

A comparison of feature extraction capabilities of advanced UHPLC-HRMS data analysis tools in plant metabolomics - Xing-Cai Wang; Xing-Ling Ma; Jia-Nan Liu; Yang Zhang; Jia-Ni Zhang; Meng-Han Ma; Feng-Lian Ma; Yong-Jie Yu; Yuanbin She (Analytica Chimica Acta, 2023)

Biochar combined with N fertilization and straw return in wheat-maize agroecosystem: Key practices to enhance crop yields and minimize carbon and nitrogen footprints - Jinze Bai; Jiajie Song; Danyang Chen; Zhihao Zhang; Qi Yu; Guangxin Ren; Xinhui Han; Xiaojiao Wang; Chengjie Ren; Gaihe Yang; Xing Wang; Yongzhong Feng (Agriculture, Ecosystems & Environment, 2023)

Evaluating potential ecological risks of emerging toxic elements in lacustrine sediments: A case study in Lake Fuxian, China - Yixuan Han; Fan Xun; Cheng Zhao; Biao Li; Wenlei Luo; Muhua Feng; Di Xu; Peng Xing; Qinglong L. Wu (Environmental Pollution, 2023)

The role of intercellular junction proteins in the penetration resistance of Drosophila larvae to avermectin - Li-Ping Chen; Han-Qing Jiang; Liang Luo; Jun Qiu; Xue-Jie Xing; Rui-Yan Hou; Yi-Jun Wu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Silica-nickel catalyst interfaces promote highly efficient CO2 electroreduction to CO with a wide potential range - Yijun Xie; Wei Xia; Shuaiqiang Jia; Shitao Han; Ting Yao; Minghui Fang; Dawei Zhou; Xueqing Xing; Haihong Wu; Mingyuan He; Buxing Han (Chemical Engineering Journal, 2023)

Soil bacteria respond intensely to resource limitations regulated by edaphic properties during secondary succession on a semiarid abandoned farmland - Zekun Zhong; Xing Wang; Rentao Liu; Dejie Kong; Haojie Nie; Xinhui Han; Gaihe Yang; Lin Zhu (CATENA, 2023)

Molecular Analysis and Sex-specific Response of the Hepcidin Gene in Yellow Perch (Perca Flavescens) Following Lipopolysaccharide Challenge - Xing Lu; Yueh-Chiang Han; Brian S. Shepherd; Ying Xiang; Dong-Fang Deng; Bryan T. Vinyard (Probiotics and Antimicrobial Proteins, 2023)

Corticostriatal Projections Relying on GABA Levels Mediate Exercise-Induced Functional Recovery in Cerebral Ischemic Mice - Ying Xing; Anjing Zhang; Congqin Li; Jing Han; Jun wang; Lu Luo; Xuechun Chang; Zhanzhuang Tian; Yulong Bai (Molecular Neurobiology, 2023)

Mechanical deterioration effect and damage evolution characteristics of soft sandstone with different water-immersed heights under uniaxial compression - Han-Dong Liu; Shuai Liu; Hai-Ning Liu; Jia-Xing Chen; Zhi-Guo Xia; Ju-Yun Zhai; Yun-You Fu (Bulletin of Engineering Geology and the Environment, 2023)

Identification and molecular characterization of a novel cytorhabdovirus from rose plants (Rosa chinensis Jacq.) - Yujiao Wu; Mengxue Yang; Han Yang; Yuanjian Qiu; Zhiyou Xuan; Fei Xing; Mengji Cao (Archives of Virology, 2023)

Comparative transcriptome analysis reveals the molecular mechanism of heat-tolerance in Neopyropia yezoensis induced by Sargassum horneri extract - Qikun Xing; Sol Han; Ji-Sook Park; Charles Yarish; Jang K. Kim (Frontiers in Marine Science, 2023)
Introduction Heat stress is one of the main threats for the seaweed aquaculture, leading to the decay of the blades and causing serious economic losses. A newly developed biostimulant, Sargassum horneri extract (SHE), can enhance the heat-tolerance in Neopyropia yezoensis, which can be applied in the seaweed aquaculture. However, the molecular mechanism underlying this acquired heat-tolerance is still unclear. Method In this study, we examined the transcriptional regulation of N. yezoensis under heat stress after the SHE pre-treatment by performing the RNA-Seq on illumina Novaseq platform and differentially expressed gene analysis. Result and discussion Our results show that, under heat stress, the SHE pre-treatment can alleviate the suppression of genes involved in normal cell activities, such as ribosome biogenesis, photosynthesis, respiration and cell cycle. On the other hand, SHE pre-treatment can also induce some key genes involved in the heat-tolerance. We also found that the combination of SHE pre-treatment and heat stress can induce some genes related to epigenetic modification, suggesting that SHE may facilitate the formation of heat stress memory in N. yezoensis. Our study provides information for understanding the molecular mechanism of heat-tolerance in N. yezoensis and for promoting the application of seaweed-derived biostimulants in the seaweed aquaculture.

scRNA-seq analysis reveals toxicity mechanisms in shrimp hemocytes subjected to nitrite stress - QingJian Liang; BeiBei Dong; Ang Li; LiTing Wu; Yu Zhang; Tao Han; Xing Liu (Chemosphere, 2023)

Temperature effects on microbial dissolved organic matter metabolisms: Linking size fractions, fluorescent compositions, and functional groups - Gang Tang; Binrui Li; Bowei Zhang; Shiwen Hu; Shuling Chen; Tong Liu; Qianqian Wang; Han Qiao; Xing Zheng (Science of The Total Environment, 2023)

Swallowtail butterflies and hawkmoths contribute equally to the pollination of Habenaria dentata (Orchidaceae) - Shao-Lin Tan; Xing-Hui Chen; Hai-Hong Liao; Lang Huang; Han-Wen Xiao; Huo-Lin Luo; Dong-Jin Xiong; Bo-Yun Yang; Zong-Xin Ren (Flora, 2023)

Adsorption behaviour and mechanism of Avermectin-based pesticides in soil driven by H-bonds formed between the compounds and humus - Tong-fang Jing; Da-xia Zhang; Yao-zhong Zhang; Yan Jin; Xian-zheng Han; Wei Mu; Bei-xing Li; Feng Liu (Chemical Engineering Journal, 2023)

Toward high-performance dibenzo[g,p]chrysene-based conjugated polymer photocatalysts for photocatalytic hydrogen production through donor-acceptor-acceptor structure design - Peixuan Xie; Changzhi Han; Sihui Xiang; Shenglin Jin; Mantang Ge; Chong Zhang; Jia-Xing Jiang (Chemical Engineering Journal, 2023)

KMT2E Haploinsufficiency Manifests Autism-Like Behaviors and Amygdala Neuronal Development Dysfunction in Mice - Yuan-Jun Li; Chun-Yan Li; Chun-Yang Li; Dian-Xing Hu; Zhi-Bo Xv; Shu-Han Zhang; Qiang Li; Pei Zhang; Bo Tian; Xiao-Li Lan; Xiao-Qian Chen (Molecular Neurobiology, 2023)

Development of mitochondrial simple sequence repeat markers to simultaneously distinguish cytoplasmic male sterile sources in cotton - Yongqi Li; Meng Zhang; Kashif Shahzad; Yang Han; Xuexian Zhang; Liping Guo; Tingxiang Qi; Huini Tang; Hailin Wang; Xiuqin Qiao; Juanjuan Feng; Zhongxu Lin; et al. (Functional & Integrative Genomics, 2023)

Enhancing intercity transportation will improve the equitable distribution of high-quality health care in China - Han Zhang; Bing-Bing Zhou; Shuwen Liu; Guohua Hu; Xing Meng; Xiaojuan Liu; Hong Shi; Yukun Gao; Haiyan Hou; Xia Li (Applied Geography, 2023)

β‐diversity in temperate grasslands is driven by stronger environmental filtering of plant species with large genomes - Hai‐Yang Zhang; Xiao‐Tao Lü; Cun‐Zheng Wei; Jeff R. Powell; Xiao‐Bo Wang; Ding‐Liang Xing; Zhu‐Wen Xu; Huan‐Long Li; Xing‐Guo Han (Ecology, 2023)
Elucidating mechanisms underlying community assembly and biodiversity patterns is central to ecology and evolution. Genome size (GS) has long been hypothesized to potentially affect species' capacity to tolerate environmental stress and might therefore help drive community assembly. However, its role in driving β‐diversity (i.e., spatial variability in species composition) remains unclear. We measured GS for 161 plant species and community composition across 52 sites spanning a 3200‐km transect in the temperate grasslands of China. By correlating the turnover of species composition with environmental dissimilarity, we found that resource filtering (i.e., environmental dissimilarity that includes precipitation, and soil nitrogen and phosphorus concentrations) affected β‐diversity patterns of large‐GS species more than small‐GS species. By contrast, geographical distance explained more variation of β‐diversity for small‐GS than for large‐GS species. In a 10‐year experiment manipulating levels of water, nitrogen, and phosphorus, adding resources increased plant biomass in species with large GS, suggesting that large‐GS species are more sensitive to the changes in resource availability. These findings highlight the role of GS in driving community assembly and predicting species responses to global change.

Photocatalytic strategy to mitigate microplastic pollution in aquatic environments: Promising catalysts, efficiencies, mechanisms, and ecological risks - Jiehong He; Lanfang Han; Fayuan Wang; Chuanxin Ma; Yanpeng Cai; Weiwei Ma; Elvis Genbo Xu; Baoshan Xing; Zhifeng Yang (Critical Reviews in Environmental Science and Technology, 2023)

Assessing the ecotoxicity of combined exposure to triphenyltin and norfloxacin at environmental levels: A case study of immunotoxicity and metabolic regulation in carp (Cyprinus carpio) - Si-Qi Zhang; Ping Li; Shu-Wen He; Shao-Ying Xing; Zhi-Han Cao; Xue-Li Zhao; Cuici Sun; Zhi-Hua Li (Chemosphere, 2023)

Mineral residue accelerant-enhanced anaerobic digestion of cow manure: An evaluation system of comprehensive performance - Sining Yun; Tian Xing; Yi Wang; Rong Chen; Feng Han; Chen Zhang; Ming Zou (Science of The Total Environment, 2023)

Two haplotype-resolved, gap-free genome assemblies for Actinidia latifolia and Actinidia chinensis shed light on the regulatory mechanisms of vitamin C and sucrose metabolism in kiwifruit - Xue Han; Yilin Zhang; Qiong Zhang; Ni Ma; Xiaoying Liu; Wenjing Tao; Zhiying Lou; Caihong Zhong; Xing Wang Deng; Dawei Li; Hang He (Molecular Plant, 2023)

Multiscale fractures integrated equivalent porous media method for simulating flow and solute transport in fracture-matrix system - Lei Ma; Di Gao; Jiazhong Qian; Di Han; Kun Xing; Haichun Ma; Yaping Deng (Journal of Hydrology, 2023)

Nonlinear effects of internet development on chemical fertilizer application intensity: Macro evidence from China - Xi Chen; Lirong Xing; Kai Wang; Yue Zhang; Xiqiu Han (Journal of Cleaner Production, 2023)

Adsorption behaviors and mechanisms of simultaneous cadmium and fluoride removal on waste bovine bone from aqueous solution - Mengting Wang; Han Ye; Xiongkai Zheng; Siyuan Chen; Huanhuan Xing; Xueqin Tao; Zhi Dang; Guining Lu (Journal of Environmental Chemical Engineering, 2023)

Are olefin aromatization reactions structure sensitive over Al pairs and single Al in H-ZSM-5 Zeolite? - Mengjiao Xing; Yunlei Chen; Jian Cao; Yuanlong Han; Zhichao Tao; Fei Wang; Kun Hao; Ling Zhang; Wentao Zheng; Hongwei Xiang; Yong Yang; Yongwang Li; et al. (Fuel, 2023)

Nanomaterials in agricultural soils: Ecotoxicity and application - Chuanxin Ma; Lanfang Han; Heping Shang; Yi Hao; Xinxin Xu; Jason C. White; Zhenyu Wang; Baoshan Xing (Current Opinion in Environmental Science & Health, 2023)

Facile electrochemically induced vacancy modulation of NiCo2O4 cathode toward high-performance aqueous Zn-based battery - Yu Zhang; Dan Sun; Yixun Wang; Xiaoqi Liu; Hongman Sun; Tonghui Cai; Xuejin Li; Han Hu; Xiaoyun Zhang; Wei Xing; Zifeng Yan (Chemical Engineering Journal, 2023)

Piceatannol enhances Beclin-1 activity to suppress tumor progression and its combination therapy strategy with everolimus in gastric cancer - Longtao Huangfu; Xiaoyang Wang; Shanshan Tian; Junbing Chen; Xueying Wang; Biao Fan; Qian Yao; Gangjian Wang; Cong Chen; Jing Han; Xiaofang Xing; Jiafu Ji (Science China Life Sciences, 2023)

Genome-wide signatures of the geographic expansion and breeding of soybean - Ying-Hui Li; Chao Qin; Li Wang; Chengzhi Jiao; Huilong Hong; Yu Tian; Yanfei Li; Guangnan Xing; Jun Wang; Yongzhe Gu; Xingpeng Gao; Delin Li; et al. (Science China Life Sciences, 2023)

Human platelet mitochondria improve the mitochondrial and cardiac function of donor heart - Zhi Jun Lin; Soomin Kim; Hui Xing Cui; Kyuboem Han; Hong Kyu Lee; Chun-Hyung Kim; Young Cheol Kang; Yin Hua Zhang (Pflügers Archiv - European Journal of Physiology, 2023)

Botulinum toxin type A treatment of four cases of Wilson disease with lower limb dystonia: A prospective study - Zeyu Cao; Rao Rao; Tong Wu; Shangzhi Chen; Saiwei Xing; Yongsheng Han (Toxicon, 2023)

ZnO quantum dots outperform nanoscale and bulk particles for enhancing tomato (Solanum lycopersicum) growth and nutritional values - Min Sun; Chenchen Zhao; Heping Shang; Yi Hao; Lanfang Han; Kun Qian; Jason C. White; Chuanxin Ma; Baoshan Xing (Science of The Total Environment, 2023)

Geochemistry of vent fluids from the Daxi Vent Field, Carlsberg Ridge, Indian Ocean: Constraints on subseafloor processes beneath a non-transform offset - Xueting Wu; Xiqiu Han; Yejian Wang; Dieter Garbe-Schönberg; Mark Schmidt; Zhaohui Zhang; Zhongyan Qiu; Tong Zong; Peng Zhou; Xing Yu; Jiqiang Liu; Hongming Luo (Marine Geology, 2023)

Prospective pyroxenite–peridotite mixed mantle source for the northern Carlsberg Ridge - Hang Hu; Xing Yu; Xiqiu Han; Yejian Wang; Zhongyan Qiu; Tong Zong; Jiqiang Liu; Honglin Li; Xucheng Xu (Lithos, 2023)

Molting-related proteases in the brown planthopper, Nilaparvata lugens - Yu-Cheng Xie; Hou-Hong Zhang; Han-Jing Li; Xiao-Ya Zhang; Xu-Mei Luo; Ming-Xing Jiang; Chuan-Xi Zhang (Insect Biochemistry and Molecular Biology, 2023)

The association of air pollutants with hospital outpatient visits for child and adolescence psychiatry in Shenzhen, China - Dong Fang; Wang Bing; Han Yao-hui; Jing Chun-xia; Zhang Ying; Liu Xing-li; Tian Hua-wei; Xiang Ying-jun; Liao Wan-wei; Li Xiu-juan; Fan Dong-yong; Yang Wei-ting; et al. (Environmental Research, 2023)

A new strategy for mass production of single-atom catalysts for high performance of CO2 electrochemical reduction - Shitao Han; Shuaiqiang Jia; Wei Xia; Xueqing Xing; Ruijuan Qi; Haihong Wu; Mingyuan He; Buxing Han (Chemical Engineering Journal, 2023)

Salt Bridge-intermediated three phase decoupling electrolytes for high voltage electrolytic aqueous Zinc-Manganese dioxides battery - Qi Xu; Qi-Xing Xie; Tong Xue; Gao Cheng; Jian-Dong Wu; Lan Ning; Xiang-Hui Yan; You-Jun Lu; Zhong-Li Zou; Bei-Ping Wang; Feng-Lan Han (Chemical Engineering Journal, 2023)

Fabrication of alginate-based multi-crosslinked biomembranes for direct methanol fuel cell application - Bin Wang; Xing Han; Yi Wang; Lu Kang; Yudong Yang; Liying Cui; Shuangling Zhong; Xuejun Cui (Carbohydrate Polymers, 2023)

Soil erosion and its causes in high-filling body: A case study of a valley area on the Loess Plateau, China - Han Bao; Ming Tang; Heng-xing Lan; Jian-bing Peng; Han Zheng; Guan-miao Guo (Journal of Mountain Science, 2023)

Rose Bengal inhibits β-amyloid oligomers-induced tau hyperphosphorylation via acting on Akt and CDK5 kinases - Chen-Ye Mou; Yan-Fei Xie; Jia-Xin Wei; Qi-Yao Wang; Jing-Yang Le; Yong-Jie Bao; Pan-Pan Zhang; Yue-Chun Mao; Xing-Han Huang; Han-Bo Pan; C. Benjamin Naman; Lin Liu; et al. (Psychopharmacology, 2022)

Metabacillus rhizolycopersici sp. nov., Isolated from the Rhizosphere Soil of Tomato Plants - Rong Ma; Shan-Wen He; Xing Wang; Kyu Kyu Thin; Ji-Gang Han; Xiao-Xia Zhang (Current Microbiology, 2022)

Engineering geological characteristics of boulders in underground: A case study from the Yu-Wan Section of Beijing Metro Line 16 - Zhiyong Yang; Xiaokang Shao; Zhigang Zhang; Jili Feng; Hao Han; Xing Yang; Yusheng Jiang (Bulletin of Engineering Geology and the Environment, 2022)

Model study on backfill grouting in shield tunnels based on fractal theory - Nan Qin; Fei Ye; Biao He; Xing Liang; XingBo Han; EnJie Su (European Journal of Environmental and Civil Engineering, 2022)

GhMYC2 activates cytochrome P450 gene CYP71BE79 to regulate gossypol biosynthesis in cotton - Xinpei Han; Yadi Xing; Yaqian Zhu; Lei Luo; Lulu Liu; Yaohua Zhai; Wenjing Wang; Ruixing Shao; Maozhi Ren; Fuguang Li; Qinghua Yang (Planta, 2022)

Validity Analysis of the Morphological Identification of Three Highly Morphologically Similar Species Belonging to the Genus Niviventer (Rodentia: Muridae) - Yao-Yao Li; Hao-Tian Li; Jia-Wei Hao; Chen-Yi Zhang; Guan-Ze Liu; Xing-Han Lin; Xiao-Qing Sun; Guo-Chen Zang; Yu-Chun Li (Journal of Mammalian Evolution, 2022)

Composition and indication of plankton fatty acids under the influence of environmental factors in the Hongfeng Reservoir, Southwest China - Xing Wang; Qiuhua Li; Wenshen Chen; Mengshu Han; Libin Han; Anton Brancelj (Aquatic Ecology, 2022)

Inhibition of visfatin alleviates sepsis-induced intestinal damage by inhibiting Hippo signaling pathway - Zhong-Shen Kuang; Yu-Xin Leng; Ning Yang; Zheng-Qian Li; Ya-Nan Zong; Deng-Yang Han; Yue Li; Jin-Dan He; Xing-Ning Mi; Zhu-Kai Cong; Xi Zhu; Chang-Yi Wu; et al. (Inflammation Research, 2022)
Background The aim of this study is to investigate role of Visfatin, one of the pro-inflammatory adipokines, in sepsis-induced intestinal injury and to clarify the potential mechanism. Methods C57BL/6 mice underwent cecal ligation and puncture (CLP) surgery to establish sepsis model in vivo. Intestinal epithelial cells were stimulated with LPS to mimic sepsis-induced intestinal injury in vitro. FK866 (the inhibitor of Visfatin) with or without XMU-MP-1 (the inhibitor of Hippo signaling) was applied for treatment. The expression levels of Visfatin, NF-κB and Hippo signaling pathways-related proteins were detected by western blot or immunohistochemistry. The intestinal cell apoptosis and intestinal injury were investigated by TUNEL staining and H&E staining, respectively. ELISA was used to determine the production of inflammatory cytokines. Results The expression of Visfatin increased in CLP mice. FK866 reduced intestinal pathological injury, inflammatory cytokines production, and intestinal cell apoptosis in sepsis mice. Meanwhile, FK866 affected NF-κB and Hippo signaling pathways. Additionally, the effects of FK866 on inflammatory response, apoptosis, Hippo signaling and NF-κB signaling were partly abolished by XMU-MP-1, the inhibitor of Hippo signaling. In vitro experiments also revealed that FK866 exhibited a protective role against LPS-induced inflammatory response and apoptosis in intestinal cells, as well as regulating NF-κB and Hippo signaling, whereas addition of XMU-MP-1 weakened the protective effects of FK866. Conclusion In short, this study demonstrated that inhibition of Visfatin might alleviate sepsis-induced intestinal injury through Hippo signaling pathway, supporting a further research on Visfatin as a therapeutic target.

Gamma rhythms in the visual cortex: functions and mechanisms - Chuanliang Han; Robert Shapley; Dajun Xing (Cognitive Neurodynamics, 2022)
Gamma-band activity, peaking around 30–100 Hz in the local field potential's power spectrum, has been found and intensively studied in many brain regions. Although gamma is thought to play a critical role in processing neural information in the brain, its cognitive functions and neural mechanisms remain unclear or debatable. Experimental studies showed that gamma rhythms are stochastic in time and vary with visual stimuli. Recent studies further showed that multiple rhythms coexist in V1 with distinct origins in different species. While all these experimental facts are a challenge for understanding the functions of gamma in the visual cortex, there are many signs of progress in computational studies. This review summarizes and discusses studies on gamma in the visual cortex from multiple perspectives and concludes that gamma rhythms are still a mystery. Combining experimental and computational studies seems the best way forward in the future.

The key environmental factors driving the succession of phytoplankton functional groups in Hongfeng Reservoir, southwest China - Libin Han; Qiuhua Li; Wensheng Chen; Xing Wang; Shihui Zhou; Mengshu Han; Anton Brancelj (Journal of Oceanology and Limnology, 2022)

Heavy Metal Concentrations in the Surface Water of a Crater Lake in Southern China - Grace A. Abarike; Sibo Wang; Cao Xing Xing; Liu Yaoqian; Yongqian Han; Wen Bin; Zhiguang Song (Water, Air, & Soil Pollution, 2022)

Dual Drug Loaded pH-sensitive Micelles for Efficient Bacterial Infection Treatment - Yingxian Chen; Qian Zhao; Junhua Han; Xinmiao Lan; Jing Che; Meiwan Chen; Xing-Jie Liang; Xiaowei Ma (Pharmaceutical Research, 2022)

Design, synthesis of amide derivatives of scutellarin and their antileukemia and neuroprotective activities - Tong Han; Chunyu Jiang; Xing Wei; Meilin Sheng; Qin Xie; Jiqiang Zhang; Yongyi Zhang; Chenghao Jin (Medicinal Chemistry Research, 2022)

Experimental investigation of the hydraulic properties of large-scale irregular fractured rock masses in granite fault zones - Liang Guo; Xiaoyu He; Zhuhong Xiong; Han Chen; Jiao Zhu; Mingwei Liao; Hao Guo; Xiaozhao Li; Baoquan Wang; Min Zhang; Lei Xing (Hydrogeology Journal, 2022)

Effects of long-term exposure of norfloxacin on the HPG and HPT axes in juvenile common carp - Si-Qi Zhang; Xue-Li Zhao; Shu-Wen He; Shao-Ying Xing; Zhi-Han Cao; Ping Li; Zhi-Hua Li (Environmental Science and Pollution Research, 2022)

Chemical composition and phytotoxic activity of the essential oil of Artemisia sieversiana growing in Xinjiang, China - Chun-Yu Jiang; Shi-Xing Zhou; Zokir Toshmatov; Yu Mei; Guang-Zhao Jin; Cai-Xia Han; Chi Zhang; Hua Shao (Natural Product Research, 2022)

One new piperazinedione isolated from a mangrove-derived fungus Aspergillus niger JX-5 - Meng Bai; Yue Wang; Ting Liu; Yu-Xing Lian; Qi-Qi Bai; Xiao-Ping Song; Chang-Ri Han; Cai-Juan Zheng; Guang-Ying Chen (Natural Product Research, 2022)

Brivaracetam Modulates Short-Term Synaptic Activity and Low-Frequency Spontaneous Brain Activity by Delaying Synaptic Vesicle Recycling in Two Distinct Rodent Models of Epileptic Seizures - Hang Xing; Xiong Han; Sihan Xu; Zhongyu Sun; Shijun Yang (Journal of Molecular Neuroscience, 2022)

Responses of photosynthesis, antioxidant enzymes, and related gene expression to nicosulfuron stress in sweet maize (Zea mays L.) - Zhen-Xing Wu; Ning-Wei Xu; Min Yang; Xiang-Ling Li; Jin-Ling Han; Xiao-Hu Lin; Qing Yang; Gui-Hua Lv; Jian Wang (Environmental Science and Pollution Research, 2022)

Chemical constituents of Viscum coloratum (Kom.) Nakai and their cytotoxic activities - Ying-Ying Chen; Jiang-Ping Hou; Ling Huang; Afsar Khan; Fei-Fei Xing; Xiao-Han Zhang; De-Feng Han; Shi-Li Yan; Gui-Dong Cao; Qi-Yang Jiao; Dejie Liu; Xuwei Zhu; et al. (Natural Product Research, 2022)

Displacement infiltration diffusion model of power-law grout as backfill grouting of a shield tunnel - Fei Ye; Nan Qin; Xin Han; Xing Liang; Xiang Gao; Kaichen Ying (European Journal of Environmental and Civil Engineering, 2022)

Involvement of Opioid Peptides in the Analgesic Effect of Spinal Cord Stimulation in a Rat Model of Neuropathic Pain - Fu-Jun Zhai; Song-Ping Han; Tian-Jia Song; Ran Huo; Xing-Yu Lan; Rong Zhang; Ji-Sheng Han (Neuroscience Bulletin, 2022)

A novel anticancer property of Lycium barbarum polysaccharide in triggering ferroptosis of breast cancer cells - Xing Du; Jingjing Zhang; Ling Liu; Bo Xu; Hang Han; Wenjie Dai; Xiuying Pei; Xufeng Fu; Shaozhang Hou (Journal of Zhejiang University-SCIENCE B, 2022)

The genetic engineering of glycine betaine synthesis in tobacco improves the resistance of the photosynthetic apparatus to drought stress - Gui-Ping Wang; Xiao-Min Xue; Xing-hong Yang; Ru Chen; Xue-Ping Han (Plant Biotechnology Reports, 2022)

Decoupled responses of above‐ and below‐ground stability of productivity to nitrogen addition at the local and larger spatial scale - Guo‐Jiao Yang; Yann Hautier; Zi‐Jia Zhang; Xiao‐Tao Lü; Xing‐Guo Han (Global Change Biology, 2022)
Temporal stability of net primary productivity (NPP) is important for predicting the reliable provisioning of ecosystem services under global changes. Although nitrogen (N) addition is known to affect the temporal stability of aboveground net primary productivity (ANPP), it is unclear how it impacts that of belowground net primary productivity (BNPP) and NPP, and whether such effects are scale dependent. Here, using experimental N addition in a grassland, we found different responses of ANPP and BNPP stability to N addition at the local scale and that these responses propagated to the larger spatial scale. That is, N addition significantly decreased the stability of ANPP but did not affect the stability of BNPP and NPP at the two scales investigated. Additionally, spatial asynchrony of both ANPP and BNPP among communities provided greater stability at the larger scale and was not affected by N addition. Our findings challenge the traditional view that N addition would reduce ecosystem stability based on results from aboveground dynamics, thus highlighting the importance of viewing ecosystem stability from a whole system perspective.

Early changes to the extracellular space in the hippocampus under simulated microgravity conditions - Yajuan Gao; Hongbin Han; Jichen Du; Qingyuan He; Yanxing Jia; Junhao Yan; Hui Dai; Bin Cui; Jing Yang; Xunbin Wei; Liu Yang; Rui Wang; et al. (Science China Life Sciences, 2022)

Analysis of Influencing Factors of Temperature Field in Freezing Construction of Metro Connecting Passage - Ping Xu; Shuqi Han; Yu Xing (Geotechnical and Geological Engineering, 2022)

Neuroprotective effect of aldose reductase knockout in a mouse model of spinal cord injury involves NF-κB pathway - Fu-xin Han; Rui Zhang; Xin-xing Yang; Shan-bo Ma; Shi-jie Hu; Bing Li (Experimental Brain Research, 2022)

Volcanism from different eruption cycles during the Early Cretaceous in the Changling fault depression of the songliao basin, NE China, and their implications for timing of lithospheric thinning - Chaoyang Liu; Xuanlong Shan; Jian Yi; Xianjun Ren; Jiaoyan Han; Penghui Niu; Jian Xing (International Geology Review, 2022)

Effects of Suspended Particles on Exopolysaccharide Secretion of Two Microalgae in Jinjiang Estuary (Fujian, China) - Jie Liu; Xiaoyu Han; Hui Xing; Yiting Nan; Jiahui Lin; Junming He; Sijia Chen; Yanfang Wei; Peiyong Guo (Journal of Marine Science and Engineering, 2022)
The effects of suspended particles (SP) of different concentrations and sizes on the secretion of exopolysaccharide (EPS) by Chlorella pyrenoidosa (C. pyrenoidosa) and Microcystis flos-aquae (M. flos-aquae) in Jinjiang Estuary, Fujian Province, China were studied in co-cultures of microalgae and SP. The results show that the SP concentration has an “inhibit–promote–inhibit” effect on the secretion of EPS by C. pyrenoidosa, whereby there is an optimal concentration of SP corresponding to the largest amount of EPS secreted by C. pyrenoidosa. Low concentrations had no significant effect on the secretion of EPS from M. flos-aquae (p > 0.05), whereas higher concentrations had an inhibitory effect. The C. pyrenoidosa EPS content was found to be significantly decreased in response to SP of small particle sizes (0–75 and 75–120 μm) and significantly increased for SP of large particle sizes (120–150 and 150–500 μm). Small particle sizes (0–75 and 75–120 μm) were found to be beneficial to the secretion of EPS from M. flos-aquae, and the promotion of EPS secretion gradually decreased with the increase in SP particle size. However, when the particle size was too large (120–150 and 150–500 μm), SP had no significant effect on EPS secretion. This study is helpful for understanding the microalgae EPS secretion response to SP and provides a scientific basis for studying the mechanism of EPS secretion by algae and the effect of SP on eutrophication of the estuary.

The Structure of the Seasonal Benthic Diatom Community and Its Relationship With Environmental Factors in the Yellow River Delta - Xing Liu; Jichang Han; Yuhang Li; Baohua Zhu; Yun Li; Kehou Pan (Frontiers in Marine Science, 2022)
Benthic diatoms are the main primary producers and are sensitive to environmental changes in the estuarine ecosystem. Therefore, it is critical to evaluate the impact of environmental stress on the benthic diatom community in the estuarine ecosystem. In this study, the sediment samples from the five sampling sites were collected from the Yellow River Delta in the four seasons, and the abundance of benthic diatoms were determined using the high-throughput sequencing of 18S rRNA genes. The results showed that the motile guild taxa, such as Navicula , Nitzschia , and Amphora , was dominated in the benthic diatom the community throughout the sampling period. The structure of the benthic diatom community was significantly different among seasons (ANOSIM P < 0.01), especially between summer and winter. Redundancy analysis showed that water temperature and the concentrations of silicate, nitrate, ammonium, and pH value are the main driving factors shaping the seasonal assembly of the benthic diatom community. The results will improve knowledge about the benthic diatom community in the estuarine ecosystem and provide a theoretical foundation for estuary environmental management.

Utility of a pharmacogenetic-driven algorithm in guiding dual antiplatelet therapy for patients undergoing coronary drug-eluting stent implantation in China - Si-qi Lyu; Jun Zhu; Juan Wang; Shuang Wu; Han Zhang; Xing-hui Shao; Yan-min Yang (European Journal of Clinical Pharmacology, 2022)

Progressive multifocal leukoencephalopathy and peripheral neuropathy in a patient with Good’s syndrome - Qinqin Deng; Zhaofen Yan; Yujiao Yang; Jing Wang; Yixian Han; Xing Feng; Minghui Wang; Liping Zhang; Mengyang Wang (Journal of NeuroVirology, 2022)

Comparative phylogeography of Acanthocalyx (Caprifoliaceae) reveals distinct genetic structures in the Himalaya–Hengduan Mountains - Qi-Yong Mu; Chih-Chieh Yu; Yan Wang; Ting-Shen Han; Hui Wang; Wen-Na Ding; Qiu-Yue Zhang; Shook Ling Low; Quan-Jing Zheng; Chuan Peng; Zheng-Yan Hu; Yao-Wu Xing (Alpine Botany, 2022)

Comprehensive analysis of chloroplast genome of Albizia julibrissin Durazz. (Leguminosae sp.) - Jing Zhang; Huizhen Huang; Changqing Qu; Xiaoxi Meng; Fei Meng; Xiaoyan Yao; Jing Wu; Xiaohu Guo; Bangxing Han; Shihai Xing (Planta, 2022)

The decreased expression of GW2 homologous genes contributed to the increased grain width and thousand‑grain weight in wheat-Dasypyrum villosum 6VS·6DL translocation lines - Zhiyu Feng; Long Song; Wanjun Song; Zhongqi Qi; Jun Yuan; Run Li; Haiming Han; Huifang Wang; Zhaoyan Chen; Weilong Guo; Mingming Xin; Jie Liu; et al. (Theoretical and Applied Genetics, 2021)

SDF-1 secreted by mesenchymal stem cells promotes the migration of endothelial progenitor cells via CXCR4/PI3K/AKT pathway - Xiaoyi Wang; Huijiao Jiang; Lijiao Guo; Sibo Wang; Wenzhe Cheng; Longfei Wan; Zhongzhou Zhang; Lihang Xing; Qing Zhou; Xiongfeng Yang; Huanhuan Han; Xueling Chen; et al. (Journal of Molecular Histology, 2021)

Molecular identification and phylogenetic analysis of fungal pathogens isolated from diseased fish in Xinjiang, China - Yan‐Zhen Zhang; Qing‐Dian Han; Long‐Wei Fu; Yong‐Xing Wang; Zhi‐Hai Sui; Yun‐Guo Liu (Journal of Fish Biology, 2021)
The outbreaks of fungal diseases in cultured fish have been severe in recent years, which is harmful to the healthy and sustainable development of fish farming. In this study, an investigation was conducted for significant fungal infections of 12 species of fish in four regions in Xinjiang, China, to understand the distribution of local fish fungal pathogens. Twenty‐six fungal strains with pathogenicity were isolated, and the challenge experiment showed that eight strains from Changji area had high infection rate to fish eggs. Based on internal transcribed spacer sequence data and molecular analysis, the 26 strains were classified into nine different species of six fungal genera. Phylogenetic analysis showed that all strains were divided into two clades, namely Cluster 1 (contains only the genus Mucor ) and Cluster 2 (consists of five small branches), and the distribution of strains from the same region was scattered in two clusters. There is no strict host selectivity for these fungi to infect fish. Mucor sp. are the main fungal pathogen of fish in these four regions, whereas Hypophthalmichthys molitrix and Carassius auratus are two types of fish that were susceptible to pathogen. In addition, the environmental adaptability experiments showed that eight highly pathogenic strains have different adaptability to the environment, and their optimum temperature and pH were 25°C and 7.0, respectively, whereas the concentration of NaCl was negatively correlated with the growth of strains. Therefore, these results indicated that the coinfection of multiple fungal pathogens in a culture region should be considered in the future study.

Loganin ameliorates depression-like behaviors of mice via modulation of serotoninergic system - Chen-Hao Pan; Cong-Yuan Xia; Yu Yan; Yan Han; Rui Shi; Jun He; Ze-Xing Wang; Yu-Ming Wang; Wei-Ku Zhang; Jie-Kun Xu (Psychopharmacology, 2021)

The optimal soil water content models based on crop-LAI and hyperspectral data of winter wheat - Miaoying An; Weimin Xing; Yuguo Han; Qingmeng Bai; Zhigong Peng; Baozhong Zhang; Zheng Wei; Wenbiao Wu (Irrigation Science, 2021)

Maritimibacter alexandrii sp. nov., a New Member of Rhodobacteraceae Isolated from Marine Phycosphere - Xing Wang; Yun Ye; Fei-Fei Xu; Yu-Han Duan; Peng-Fei Xie; Qiao Yang; Xiao-Ling Zhang (Current Microbiology, 2021)

A proteomic analysis of Bcl-2 regulation of cell cycle arrest: insight into the mechanisms - Xing Du; Jingjing Xiao; Xufeng Fu; Bo Xu; Hang Han; Yin Wang; Xiuying Pei (Journal of Zhejiang University-SCIENCE B, 2021)

Long-term nitrogen addition further increased carbon sequestration in a boreal forest - Guancheng Liu; Guoyong Yan; Mengyu Chang; Binbin Huang; Xingyu Sun; Shijie Han; Yajuan Xing; Qinggui Wang (European Journal of Forest Research, 2021)

Methane Concentration in the Heartwood of Living Trees and Estimated Methane Emission on Stems in Upland Forests - Zhi-Ping Wang; Huan-Long Li; Hong-Hui Wu; Shi-Jie Han; Jian-Hui Huang; Xi-Mei Zhang; Xing-Guo Han (Ecosystems, 2021)

Comparison of clinical characteristics and outcomes between respiratory syncytial virus and influenza-related pneumonia in China from 2013 to 2019 - Liang Chen; Xiudi Han; YanLi Li; Chunxiao Zhang; Xiqian Xing (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Genome-wide association analysis for yield-related traits at the R6 stage in a Chinese soybean mini core collection - Xiangnan Li; Yang Zhou; Yuanpeng Bu; Xinfang Wang; Yumei Zhang; Na Guo; Jinming Zhao; Han Xing (Genes & Genomics, 2021)

Sum of High-Risk Gene Mutation (SHGM): A Novel Attempt to Assist Differential Diagnosis for Adrenocortical Carcinoma with Benign Adenoma, Based on Detection of Mutations of Nine Target Genes - Guo-Yang Zheng; Xue-Bin Zhang; Han-Zhong Li; Yu-Shi Zhang; Jian-Hua Deng; Xing-Cheng Wu (Biochemical Genetics, 2021)
There has been no research on applying gene detection to differential diagnosis of adrenocortical carcinoma (ACC). We attempted to explore a novel auxiliary method for differential diagnosis between ACC with benign adrenocortical adenoma (ACA), based on mutations of target genes in tissues. Nine genes were chosen as target genes, including TP53, CTNNB1, ARMC5, PRKAR1A, ZNRF3, RB1, APC, MEN1, and RPL22 . Exons sequencing of target genes were performed in 98 cases of tissue samples by FastTarget technology, including 41 ACC tissues, 32 ACA tissues, and 25 normal adrenal gland tissues. Significant mutations were detected and identified, and the clinical information was collected, for further comparative analysis and application to assist differential diagnosis of ACC. We identified 132 significant gene mutations and 227 significant mutation sites in 37 ACC tissues, much more than ACA and normal adrenal gland tissues. Mutation rates of 6 genes in ACC tissues were obviously higher than ACA tissues, including ZNRF3, ARMC5, TP53, APC, RB1, and PRKAR1A , regarded as high-risk genes. The sum of mutated high-risk genes detected in each sample was denominated sum of high-risk gene mutation (SHGM), and the rates of SHGM > 0 and SHGM > 1 in ACC tissues were 73.0% and 62.2%, respectively, both obviously higher than those in ACA tissues, with significant statistic differences. Especially for 8 cases of ACC with diameter 0 and SHGM > 1 were found in 6 samples (75%) and 4 samples (50%), respectively. However, no relevance was found between SHGM and clinical characteristics of ACC. We identified 6 high-risk genes in ACC tissues, with significantly higher mutation rates than ACA or normal adrenal gland tissues. The sum of mutated high-risk genes detected in ACC tissues was denominated SHGM, which was potential to assist the differential diagnosis of ACC with ACA, especially for the small-size ACC.

Loss of endothelial glucocorticoid receptor promotes angiogenesis via upregulation of Wnt/β-catenin pathway - Bing Liu; Han Zhou; Tiening Zhang; Xixiang Gao; Bo Tao; Hao Xing; Zhenwu Zhuang; Alan Dardik; Themis R. Kyriakides; Julie E. Goodwin (Angiogenesis, 2021)
Objective The glucocorticoid receptor (GR) is a member of the nuclear receptor family that controls key biological processes in the cardiovascular system and has recently been shown to modulate Wnt signaling in endothelial cells. Wnt/β-catenin signaling has been demonstrated to be crucial in the process of angiogenesis. In the current study, we studied whether GR could regulate angiogenesis via the Wnt/β-catenin pathway. Approach and Resultsa Key components of the Wnt/β-catenin pathway were evaluated using quantitative PCR and Western blot in the presence or absence of GR. Enhanced angiogenesis was found in GR deficiency in vitro and confirmed with cell viability assays, proliferation assays and tube formation assays. Consistent with these in vitro findings, endothelial cell-specific GR loss GR in vivo promoted angiogenesis in both a hind limb ischemia model and sponge implantation assay. Results were further verified in a novel mouse model lacking endothelial LRP5/6, a key receptor in canonical Wnt signaling, and showed substantially suppressed angiogenesis using these same in vitro and in vivo assays. To further investigate the mechanism of GR regulation of Wnt signaling, autophagy flux was investigated in endothelial cells by visualizing auto phagolysosomes as well as by assessing P62 degradation and LC3B conversion. Results indicated that potentiated autophagy flux participated in GR-Wnt regulation. Conclusions Lack of endothelial GR triggers autophagy flux, leads to activation of Wnt/β-catenin signaling and promotes angiogenesis. There may also be a synergistic interaction between autophagy and Wnt/β-catenin signaling.

Distinctive distributions of halophilic Archaea across hypersaline environments within the Qaidam Basin of China - Derui Zhu; Guoping Shen; Zhibo Wang; Rui Han; Qifu Long; Xiang Gao; Jiangwa Xing; Yongzhen Li; Rong Wang (Archives of Microbiology, 2021)

Intraspecific recurrent selection in V. vinifera: an effective method for breeding of high quality, disease-, cold-, and drought -resistant grapes - Zhi-Lei Wang; Ting-Ting Xue; Fei-Fei Gao; Liang Zhang; Xing Han; Ying Wang; Miao Hui; Dong Wu; Hua Li; Hua Wang (Euphytica, 2021)

Application of DNA barcoding and metabarcoding for species identification in salmon products - Nan Wang; Ran-Ran Xing; Meng-Yue Zhou; Rui-Xue Sun; Jian-Xun Han; Jiu-Kai Zhang; Wen-Jie Zheng; Ying Chen (Food Additives & Contaminants: Part A, 2021)

A reciprocal egg-swap experiment reveals sources of variation in developmental success among populations of a desert lizard - Xin Hao; Chen-Xu Wang; Xing-Zhi Han; Yang Wang; Qiong Zhang; Fu-Shun Zhang; Bao-Jun Sun; Wei-Guo Du (Oecologia, 2021)

The circular RNA circSlc7a11 promotes bone cancer pain pathogenesis in rats by modulating LLC-WRC 256 cell proliferation and apoptosis - Han-Wen Chen; Xiao-Xia Zhang; Zhu-Ding Peng; Zu-Min Xing; Yi-Wen Zhang; Ya-Lan Li (Molecular and Cellular Biochemistry, 2021)
Treatment of bone cancer pain (BCP) caused by bone metastasis in advanced cancers remains a challenge in clinical oncology, and the underlying mechanisms of BCP are poorly understood. This study aimed to investigate the pathogenic roles of circular RNAs (circRNAs) in regulating cancer cell proliferation and BCP development. Eight differentially expressed circRNAs in the rat spinal cord were validated by agarose gel electrophoresis and Sanger sequencing. Expression of circRNAs and mRNAs was detected by quantitative RT-PCR. MTS assay and flow cytometry were performed to analyze cell proliferation and apoptosis, respectively. Differentially expressed mRNA profiles were characterized by deep RNA sequencing, hierarchical clustering, and functional categorization. The interactions among circRNAs, microRNAs (miRNAs), and mRNAs were predicted using TargetScan. Additionally, western blot was performed to determine the protein levels of Pax8, Isg15, and Cxcl10. Multiple circRNAs were differentially expressed in the spinal cords of BCP model rats; of these, circSlc7a11 showed the greatest increase in expression. The overexpression of circSlc7a11 significantly promoted cell proliferation and repressed apoptosis of LLC-WRC 256 and UMR-106 cells, whereas circSlc7a11 silencing produced the opposite effects. Altered expression of circSlc7a11 also induced substantial changes in the mRNA expression profiles of LLC-WRC 256 cells; these changes were linked to multiple apoptotic processes and signaling pathways, such as the chemokine signaling pathway, and formed a complex circRNA/miRNA/mRNA network. Additionally, Pax8, Isg15, and Cxc110 protein level in LLC-WRC 256 cells was consistent with the mRNA results. The circRNA circSlc7a11 regulates rat BCP development by modulating LLC-WRC 256 cell proliferation and apoptosis through multiple-signaling mechanisms.

Nitrogen Enrichment Reduces Nitrogen and Phosphorus Resorption Through Changes to Species Resorption and Plant Community Composition - Xiao-Tao Lü; Shuang-Li Hou; Sasha Reed; Jiang-Xia Yin; Yan-Yu Hu; Hai-Wei Wei; Zhi-Wei Zhang; Guo-Jiao Yang; Zhuo-Yi Liu; Xing-Guo Han (Ecosystems, 2021)

EmhR is an indole‐sensing transcriptional regulator responsible for the indole‐induced antibiotic tolerance in Pseudomonas fluorescens - Jian‐Ting Han; Di‐Yin Li; Meng‐Yuan Zhang; Xiao‐Quan Yu; Xiang‐Xue Jia; Hang Xu; Xu Yan; Wen‐Juan Jia; Shaomin Niu; Megan L. Kempher; Xuanyu Tao; Yong‐Xing He (Environmental Microbiology, 2021)
Summary Indole is well known as an interspecies signalling molecule to modulate bacterial physiology; however, it is not clear how the indole signal is perceived and responded to by plant growth promoting rhizobacteria (PGPR) in the rhizosphere. Here, we demonstrated that indole enhanced the antibiotic tolerance of Pseudomonas fluorescens 2P24, a PGPR well known for its biocontrol capacity. Proteomic analysis revealed that indole influenced the expression of multiple genes including the emhABC operon encoding a major multidrug efflux pump. The expression of emhABC was regulated by a TetR‐family transcription factor EmhR, which was demonstrated to be an indole‐responsive regulator. Molecular dynamics simulation showed that indole allosterically affected the distance between the two DNA‐recognizing helices within the EmhR dimer, leading to diminished EmhR–DNA interaction. It was further revealed the EmhR ortholog in Pseudomonas syringae was also responsible for indole‐induced antibiotic tolerance, suggesting this EmhR‐dependent, indole‐induced antibiotic tolerance is likely to be conserved among Pseudomonas species. Taken together, our results elucidated the molecular mechanism of indole‐induced antibiotic tolerance in Pseudomonas species and had important implications on how rhizobacteria sense and respond to indole in the rhizosphere.

At3g53630 encodes a GUN1-interacting protein under norflurazon treatment - Xing-Qi Huang; Lin-Juan Wang; Meng-Juan Kong; Na Huang; Xin-Ya Liu; Han-Yu Liang; Jia-Xin Zhang; Shan Lu (Protoplasma, 2021)

Unraveling Physiological and Metabolomic Responses Involved in Phlox subulata L. Tolerance to Drought Stress - Yan Xiong; Yanting Qu; Hui Han; Fei Chen; Li Li; Huanwei Tang; Daidi Che; Xing Zhang (Plant Molecular Biology Reporter, 2021)

The cellulose synthase (CesA) gene family in four Gossypium species: phylogenetics, sequence variation and gene expression in relation to fiber quality in Upland cotton - Sujun Zhang; Zhenxing Jiang; Jie Chen; Zongfu Han; Jina Chi; Xihua Li; Jiwen Yu; Chaozhu Xing; Mingzhou Song; Jianyong Wu; Feng Liu; Xiangyun Zhang; et al. (Molecular Genetics and Genomics, 2021)

2,3,5,6-Tetramethylpyrazine protects retinal photoreceptors against endoplasmic reticulum stress by modulating ATF4-mediated inhibition of PRP aggregation - Hao Huang; Xiaobo Zhu; Hao Cheng; Xielan Kuang; Chongde Long; Xizhi Deng; Yuxiu Zou; Han Zhang; Yue Xing; Xiangtian Ling; Renchun Wang; Han Tang; et al. (Journal of Molecular Medicine, 2021)

Polybrominated diphenyl ethers in soils from Tianjin, North China: distribution, health risk, and temporal trends - Yu Han; Jiali Cheng; Lei He; Minna Zhang; Shan Ren; Jiazheng Sun; Xiangyang Xing; Zhenwu Tang (Environmental Geochemistry and Health, 2021)

Effects of degradation succession of alpine wetland on soil organic carbon and total nitrogen in the Yellow River source zone, west China - Chun-ying Lin; Xi-lai Li; Jing Zhang; Hua-fang Sun; Juan Zhang; Hui-bang Han; Qi-hua Wang; Cheng-biao Ma; Cheng-yi Li; Yu-xing Zhang; Xue-qian Ma (Journal of Mountain Science, 2021)

Rhizobium rhizolycopersici sp. nov., Isolated from the Rhizosphere Soil of Tomato Plants in China - Kyu Kyu Thin; Shan-Wen He; Xing Wang; Yao Wang; Ma Rong; Ji-Gang Han; Xiaoxia Zhang (Current Microbiology, 2021)

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

A chemical structure-based approach for estimating the added levels of flavourings to foods for the purpose of assessing consumer intake - Maria Bastaki; Michel Aubanel; Heidi Bialk; Christopher Choi; Jan Demyttenaere; Malick Maodo Diop; Sylvain Etter; Xing Han; Mihoko Koyanagi; Gerhard Krammer; Jürgen Schnabel; Cody L. Wilson; et al. (Food Additives & Contaminants: Part A, 2021)

Circulating sortilin levels are associated with inflammation in patients with moyamoya disease - Wenxiu Han; Yi Qiao; Hailiang Zhang; Chunmei Geng; Xing Zhu; Dehua Liao; Yujin Guo; Mengqi Yang; Dan Chen; Pei Jiang (Metabolic Brain Disease, 2021)

LncRNA RHPN1-AS1 accelerates proliferation, migration, and invasion via regulating miR-485-5p/BSG axis in hepatocellular carcinoma - Wei Zhang; Lei Han; Peng Xing; Bailiang Liu; Zhongqi Sun; Wenping Zhou; Jiahong Dong (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

SNP of AHSA2 gene in three cattle breeds using snapshot technology - Shu-Zhu Cheng; E. Guang-Xin; Cheng-Li Liu; Wang-Dui Basang; Yan-Bin Zhu; Ri-Su Na; Yan-Guo Han; Yan Zeng; Xiao Wang; Wei-Wei Ni; Bai-Gao Yang; Xing-Hai Duan; et al. (Journal of Genetics, 2020)

Study of the geostatistical grid maths operation method of quantifying water movement in soil layers of a cotton field * - Liyuan Liu; Fangfang Xing; Yabing Li; Yingchun Han; Zhanbiao Wang; Xiaoyu Zhi; Guoping Wang; Lu Feng; Beifang Yang; Yaping Lei; Zhengyi Fan; Wenli Du (Irrigation and Drainage, 2020)
The precise quantification of water movement in different field soil layers is important for variable‐rate irrigation and fertilization. To this end, a field experiment based on a geostatistical approach was conducted in southern Anyang, Henan, China, to examine soil water movement in a cotton field with drip irrigation by measuring the soil water content (SWC) data on a regular 100 × 80 cm grid. The result shows that the temporal and spatial variation of soil moisture decreased with the increase of soil depth at different points, and apparent spatial heterogeneity was observed under different soil conditions through a semivariogram analysis. The variation of soil moisture at different soil profiles was affected by the cotton plants and drip lines in non‐irrigation and irrigation periods respectively. The level of the change at 20 cm was more than 70 cm in the horizontal direction in the two periods, however the degree of change at 40 cm in the irrigation period was more than 70 cm in the vertical direction, while contrary results were shown in the non‐irrigation period. Moreover, the results indicated that the trapezoidal rule could be applied to quantify the volume of water movement precisely.

Fingerprint identification of white clover cultivars based on SSR molecular markers - Sainan Ma; Chongyang Han; Jie Zhou; Ruchang Hu; Xing Jiang; Feifei Wu; Ke Tian; Gang Nie; Xinquan Zhang (Molecular Biology Reports, 2020)

Climate factors during key periods affect the comprehensive crop losses due to drought in Southern China - Qiang Zhang; Lanying Han; Jian Zeng; Xing Wang; Jingjing Lin (Climate Dynamics, 2020)

Bias Correction and Ensemble Projections of Temperature Changes over Ten Subregions in CORDEX East Asia - Chenwei Shen; Qingyun Duan; Chiyuan Miao; Chang Xing; Xuewei Fan; Yi Wu; Jingya Han (Advances in Atmospheric Sciences, 2020)

Internalization of the TAT-PBX1 fusion protein significantly enhances the proliferation of human hair follicle-derived mesenchymal stem cells and delays their senescence - Bo Wang; Feilin Liu; Zinan Liu; Xing Han; Aobo Lian; Yuying Zhang; Kuiyang Zuo; Yuan Wang; Mingsheng Liu; Fei Zou; Yixu Jiang; Minghua Jin; et al. (Biotechnology Letters, 2020)

An evaluation of the core bacterial communities associated with hypersaline environments in the Qaidam Basin, China - Derui Zhu; Rui Han; Qifu Long; Xiang Gao; Jiangwa Xing; Guoping Shen; Yongzhen Li; Rong Wang (Archives of Microbiology, 2020)

Frequency extension and robust full-waveform inversion based on nth power operation - Pan Zhang; Liguo Han; Rui Gao; Fengjiao Zhang; Zhenzhen Xing (Acta Geophysica, 2020)

Dominant complementary interaction between OsC1 and two tightly linked genes, Rb1 and Rb2, controls the purple leaf sheath in rice - Wei Hu; Tianhao Zhou; Zhongmin Han; Cong Tan; Yongzhong Xing (Theoretical and Applied Genetics, 2020)

Bacterial and Archaeal Communities within an Ultraoligotrophic, High-altitude Lake in the Pre-Himalayas of the Qinghai-Tibet Plateau - Rong Wang; Rui Han; Qifu Long; Xiang Gao; Jiangwa Xing; Guoping Shen; Derui Zhu (Indian Journal of Microbiology, 2020)

CDOM in the source regions of the Yangtze and Yellow Rivers, China: optical properties, possible sources, and their relationships with environmental variables - Dianbao Li; Baozhu Pan; Xing Zheng; Xiaoming Jiang; Gengnan Zhao; Xu Han (Environmental Science and Pollution Research, 2020)

Laboratory investigation of the mode-I fracture of sandstone caused by a combination of freeze-thaw cycles and chemical solutions - Tielin Han; Xianfeng Wang; Zhihui Li; Dawang Li; Feng Xing; Ningxu Han (Bulletin of Engineering Geology and the Environment, 2020)

Effects of different treatments on genes related to polysaccharide content in Dendrobium huoshanense - Jun Dai; Xing-bang Han; Nai-fu Chen; Cun-wu Chen; Nai-dong Chen; Xiang-wen Song; Xue-ping Jiang; Yu-juan Wang (Brazilian Journal of Botany, 2020)

Streptomyces soli sp. nov., isolated from birch forest soil - Jialing Xing; Xu Jiang; Delong Kong; Yiqing Zhou; Miaomiao Li; Xiaoyan Han; Qingyun Ma; Hao Tan; Zhiyong Ruan (Archives of Microbiology, 2020)

Identification and evaluation of tobacco cytoplasmic male sterile line Nta(gla)S K326 generated from asymmetric protoplast fusion of Nicotiana glauca and N. tabacum followed by backcrossing with N. tabacum K326 - Xue-Jun Chen; Zhi-Jun Tong; Bing-Guang Xiao; Yong-Ping Li; Fang-Chan Jiao; Yong Li; Tao Pang; Dun-Huang Fang; Xing-Fu Wu; Yi-Han Zhang; He Xie; Ge Bai; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Responses of Primary Afferent Fibers to Acupuncture-Like Peripheral Stimulation at Different Frequencies: Characterization by Single-Unit Recording in Rats - Ran Huo; Song-Ping Han; Feng-Yu Liu; Xiao-Jing Shou; Ling-Yu Liu; Tian-Jia Song; Fu-Jun Zhai; Rong Zhang; Guo-Gang Xing; Ji-Sheng Han (Neuroscience Bulletin, 2020)

Ochratoxin A in human blood plasma samples from apparently healthy volunteers in Nanjing, China - Kai Fan; Xi Cheng; Wenbo Guo; Xing Liu; Zhiqi Zhang; Qi Yao; Dongxie Nie; Bing Yao; Zheng Han (Mycotoxin Research, 2020)

Improving the prediction of western North Pacific summer precipitation using a Bayesian dynamic linear model - Wen Xing; Weiqing Han; Lei Zhang (Climate Dynamics, 2020)

Impact of early neuraminidase inhibitor treatment on clinical outcomes in patients with influenza B-related pneumonia: a multicenter cohort study - Liang Chen; Xiudi Han; YanLi Li; Chunxiao Zhang; Xiqian Xing (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

C:N:P stoichiometries explain soil organic carbon accumulation during afforestation - Zekun Zhong; Xinyi Zhang; Xing Wang; Yinyue Dai; Zhengxing Chen; Xinhui Han; Gaihe Yang; Chengjie Ren; Xiaojiao Wang (Nutrient Cycling in Agroecosystems, 2020)

Pictalignans D-F, three new neolignan derivatives from Selaginella picta - Fei Cheng; Zhen-Xing Zou; Ping-Sheng Xu; Shui-Han Zhang; Yan Zhang; Cai-Ping Yao; Kang-Ping Xu; Gui-Shan Tan (Natural Product Research, 2020)

Primary percutaneous coronary intervention in a COVID-19 patient with ST-segment elevation myocardial infarction after lung transplantation: a case report - Tian-ming Xuan; Xing-xiang Wang; Xiang-yuan Pu; Wei-li Han; Xiao-gang Guo (Journal of Zhejiang University-SCIENCE B, 2020)

Targeting Two Antigens Associated with B-ALL with CD19-CD123 Compound Car T Cell Therapy - Lulu E. Yan; Hongyu Zhang; Masayuki Wada; Liu Fang; Jia Feng; Wenli Zhang; Qi Chen; Yuanzhen Cao; Kevin G. Pinz; Kevin H. Chen; Jessica C. Petrov; Xi Chen; et al. (Stem Cell Reviews and Reports, 2020)

The effect of temperature fluctuation on the microbial diversity and community structure of rural household biogas digesters at Qinghai Plateau - Rui Han; Derui Zhu; Jiangwa Xing; Quanhui Li; Yi Li; Laisheng Chen (Archives of Microbiology, 2020)

Soil bacteria and fungi respond differently to plant diversity and plant family composition during the secondary succession of abandoned farmland on the Loess Plateau, China - Zekun Zhong; Xinyi Zhang; Xing Wang; Shuyue Fu; Shaojun Wu; Xuqiao Lu; Chengjie Ren; Xinhui Han; Gaihe Yang (Plant and Soil, 2020)

Mechanism of phosphorus mobility in sediments with larval (Propsilocerus akamusi) bioturbation - Wenming Yan; Musong Chen; Ling Liu; Tingfeng Wu; Yi Zhang; Han Wang; Xigang Xing; Kongming Fan (Environmental Science and Pollution Research, 2020)

The NADPH oxidase in Volvariella volvacea and its differential expression in response to mycelial ageing and mechanical injury - Jun-Jie Yan; Zong-Jun Tong; Yuan-Yuan Liu; Zi-Yan Lin; Ying Long; Xing Han; Wei-Nan Xu; Qian-Hui Huang; Yong-Xin Tao; Bao-Gui Xie (Brazilian Journal of Microbiology, 2020)

Effect of slope gradient on the subsurface water flow velocity of sand layer profile - Zhen Han; Xiao-yan Chen; Yu-han Huang; Bang-lin Luo; Hang Xing; Yong-chao Huang (Journal of Mountain Science, 2020)

Microbial methane production is affected by secondary metabolites in the heartwood of living trees in upland forests - Huan-Long Li; Xi-Mei Zhang; Feng-Dan Deng; Xing-Guo Han; Chun-Wang Xiao; Shi-Jie Han; Zhi-Ping Wang (Trees, 2020)

Bin-based genome-wide association analyses improve power and resolution in QTL mapping and identify favorable alleles from multiple parents in a four-way MAGIC rice population - Zhongmin Han; Gang Hu; Hua Liu; Famao Liang; Lin Yang; Hu Zhao; Qinghua Zhang; Zhixin Li; Qifa Zhang; Yongzhong Xing (Theoretical and Applied Genetics, 2020)

A genome-wide analysis of pentatricopeptide repeat (PPR) protein-encoding genes in four Gossypium species with an emphasis on their expression in floral buds, ovules, and fibers in upland cotton - Zongfu Han; Yuxiang Qin; Xihua Li; Jiwen Yu; Ruzhong Li; Chaozhu Xing; Mingzhou Song; Jianyong Wu; Jinfa Zhang (Molecular Genetics and Genomics, 2020)

Fractional crystallization processes of magma beneath the Carlsberg Ridge (57°–65°E) - Tong Zong; Xiqiu Han; Jiqiang Liu; Yejian Wang; Zhongyan Qiu; Xing Yu (Journal of Oceanology and Limnology, 2020)

Effects of Exogenous GA3 and DPC Treatments on Levels of Endogenous Hormone and Expression of Key Gibberellin Biosynthesis Pathway Genes During Stem Elongation in Sugarcane - Li-Hang Qiu; Rong-Fa Chen; Han-Min Luo; Ye-Geng Fan; Xing Huang; Jun-Xian Liu; Fa-Qian Xiong; Hui-Wen Zhou; Chong-Kun Gan; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2019)

Changes of plant N:P stoichiometry across a 3000-km aridity transect in grasslands of northern China - Xiao-Guang Wang; Xiao-Tao Lü; Feike A. Dijkstra; Hai-Yang Zhang; Xiao-Bo Wang; Wuyunna; Zheng-Wen Wang; Jiao Feng; Xing-Guo Han (Plant and Soil, 2019)

Dynamics of dissolved greenhouse gas response to seasonal water mixing in subtropical reservoirs - Zhenglun Yang; Changyuan Tang; Xing Li; Han Zhang; Yangyang Cai (Environmental Monitoring and Assessment, 2019)

Geospatial relation captioning for high-spatial-resolution images by using an attention-based neural network - Jie Chen; Yarong Han; Li Wan; Xing Zhou; Min Deng (International Journal of Remote Sensing, 2019)

Influence of Vitamin D Status and Mechanical Loading on the Morphometric and Mechanical Properties of the Mouse Tibia - Yong-Tao Lu; Zhen-Tao Cui; Han-Xing Zhu; Ru-Kun Ma; Cheng-Wei Wu (Journal of Medical and Biological Engineering, 2019)

Isochromanes from Aspergillus fumigatus , an endophytic fungus from Cordyceps sinensis - Xiao-Hua Li; Xue-Hua Han; Ling-Ling Qin; Jun-Lin He; Zhi-Xing Cao; Yu-Cheng Gu; Da-Le Guo; Yun Deng (Natural Product Research, 2019)

Identification of a lytic Pseudomonas aeruginosa phage depolymerase and its anti-biofilm effect and bactericidal contribution to serum - Liyuan Mi; Yannan Liu; Can Wang; Tongtong He; Shan Gao; Shaozhen Xing; Yong Huang; Hang Fan; Xianglilan Zhang; Wengong Yu; Zhiqiang Mi; Yigang Tong; et al. (Virus Genes, 2019)

The Tibetan Plateau Surface-Atmosphere Coupling System and Its Weather and Climate Effects: The Third Tibetan Plateau Atmospheric Science Experiment - Ping Zhao; Yueqing Li; Xueliang Guo; Xiangde Xu; Yimin Liu; Shihao Tang; Wenming Xiao; Chunxiang Shi; Yaoming Ma; Xing Yu; Huizhi Liu; La Jia; et al. (Journal of Meteorological Research, 2019)

Correction to: Mowing mitigates the negative impacts of N addition on plant species diversity - Guo-Jiao Yang; Xiao-Tao Lü; Carly J. Stevens; Guang-Ming Zhang; Hong-Yi Wang; Zheng-Wen Wang; Zi-Jia Zhang; Zhuo-Yi Liu; Xing-Guo Han (Oecologia, 2019)

The antitoxin MqsA homologue in Pseudomonas fluorescens 2P24 has a rewired regulatory circuit through evolution - Yong Wang; Si‐Ping Zhang; Meng‐Yuan Zhang; Megan L. Kempher; Ding‐Ding Guo; Jian‐Ting Han; Xuanyu Tao; Yi Wu; Li‐Qun Zhang; Yong‐Xing He (Environmental Microbiology, 2019)
Summary The mqsRA operon encodes a toxin–antitoxin pair that was characterized to participate in biofilm and persister cell formation in Escherichia coli . Notably, the antitoxin MqsA possesses a C‐terminal DNA‐binding domain that recognizes the [5’‐AACCT(N) 2‐4 AGGTT‐3′] motif and acts as a transcriptional regulator controlling multiple genes including the general stress response regulator RpoS. However, it is unknown how the transcriptional circuits of MqsA homologues have changed in bacteria over evolutionary time. Here, we found mqsA in Pseudomonas fluorescens ( PfmqsA ) is acquired through horizontal gene transfer and binds to a slightly different motif [5′‐TACCCT(N) 3 AGGGTA‐3′], which exists upstream of the PfmqsRA operon. Interestingly, an adjacent GntR‐type transcriptional regulator, which was termed AgtR, is under negative control of PfMqsA. It was further demonstrated that PfMqsA reduces production of biofilm components through AgtR, which directly regulates the pga and fap operons involved in the synthesis of extracellular polymeric substances. Moreover, through quantitative proteomics analysis, we showed AgtR is a highly pleiotropic regulator that influences up to 252 genes related to diverse processes including chemotaxis, oxidative phosphorylation and carbon and nitrogen metabolism. Taken together, our findings suggest the rewired regulatory circuit of PfMqsA influences diverse physiological aspects of P. fluorescens 2P24 via the newly characterized AgtR.

Vertical profile of organic and elemental carbon in sediments of Songkhla Lake, Thailand - Siwatt Pongpiachan; Danai Tipmanee; Chomsri Choochuay; Mattanawadee Hattayanone; Woranuch Deelaman; Natthapong Iadtem; Suratta Bunsomboonsakul; Jittree Palakun; Saran Poshyachinda; Apichart Leckngam; Pitipong Somboonpon; Thirasak Panyaphirawat; et al. (Limnology, 2019)

Mitochondrial superoxide anions induced by exogenous oxidative stress determine tumor cell fate: an individual cell-based study - Hui Pan; Bao-hui Wang; Zhou-bin Li; Xing-guo Gong; Yong Qin; Yan Jiang; Wei-li Han (Journal of Zhejiang University-SCIENCE B, 2019)

Treatment with MQA, a Derivative of Caffeoylquinic Acid, Provides Neuroprotective Effects against Cerebral Ischemia Through Suppression of the p38 Pathway and Oxidative Stress in Rats - Long Chen; Dan-ni Liu; Yu Wang; Xue-ying Liu; Shuai Han; Ke Zhang; Guo-yu Li; Xing Tian; Hang-yu Wang; Jin-hui Wang (Journal of Molecular Neuroscience, 2019)

l-Carnitine inhibits the senescence-associated secretory phenotype of aging adipose tissue by JNK/p53 pathway - Lian-wei Yang; Ming Song; Yu-lin Li; Ya-peng Liu; Chun Liu; Lu Han; Zhi-hao Wang; Wei Zhang; Yan-qiu Xing; Ming Zhong (Biogerontology, 2019)

An experimental study on metal precipitation driven by fluid mixing: implications for genesis of carbonate-hosted lead–zinc ore deposits - Yan Zhang; Runsheng Han; Xing Ding; Junjie He; Yurong Wang (Acta Geochimica, 2019)

Mowing mitigates the negative impacts of N addition on plant species diversity - Guo-Jiao Yang; Xiao-Tao Lü; Carly J. Stevens; Guang-Ming Zhang; Hong-Yi Wang; Zheng-Wen Wang; Zi-Jia Zhang; Zhuo-Yi Liu; Xing-Guo Han (Oecologia, 2019)

Two new secondary metabolites from a mangrove-derived fungus Cladosporium sp. JJM22 - Jia-Ting Wu; Cai-Juan Zheng; Bin Zhang; Xue-Ming Zhou; Qi Zhou; Guang-Ying Chen; Zhuo-Er Zeng; Jin-Long Xie; Chang-Ri Han; Ji-Xing Lyu (Natural Product Research, 2019)

Transcription profiles reveal the regulatory mechanisms of spur bud changes and flower induction in response to shoot bending in apple (Malus domestica Borkh.) - Libo Xing; Dong Zhang; Siyan Qi; Xilong Chen; Na An; Youmei Li; Caiping Zhao; Mingyu Han; Juan Zhao (Plant Molecular Biology, 2019)

Evaluation of a Potential Clinical Significant Drug-Drug Interaction between Digoxin and Bupropion in Cynomolgus Monkeys - Yang Shen; Yang Yu; Wei Lai; Shuai Li; Zixuan Xu; Jiejing Jin; Xia Yan; Han Xing; Xijing Chen; Aizhen Xiong; Chunhua Xia; Jiake He; et al. (Pharmaceutical Research, 2019)

Conditional and unconditional QTL analyses of seed hardness in vegetable soybean (Glycine max L. Merr.) - Yuanpeng Bu; Xing Zhang; Congcong Wang; Jingjie Guo; Xiaoli Zhang; Xiangnan Li; Qiang Yan; Jinming Zhao; Han Xing (Euphytica, 2018)

Histamine Excites Striatal Dopamine D1 and D2 Receptor-Expressing Neurons via Postsynaptic H1 and H2 Receptors - Qian-Xing Zhuang; Han-Ting Xu; Xu-Juan Lu; Bin Li; Wing-Ho Yung; Jian-Jun Wang; Jing-Ning Zhu (Molecular Neurobiology, 2018)

Genome-wide SNP-based association mapping of resistance to Phytophthora sojae in soybean (Glycine max (L.) Merr.) - Jingping Niu; Na Guo; Zhang Zhang; Zili Wang; Jianli Huang; Jinming Zhao; Fangguo Chang; Haitang Wang; Tuanjie Zhao; Han Xing (Euphytica, 2018)

Overexpression of Chalcone Isomerase (CHI) Increases Resistance Against Phytophthora sojae in Soybean - Yang Zhou; Jian-li Huang; Xiao-li Zhang; Long-ming Zhu; Xin-fang Wang; Na Guo; Jin-ming Zhao; Han Xing (Journal of Plant Biology, 2018)

Genome-Wide Association Studies of Soybean Seed Hardness in the Chinese Mini Core Collection - Xing Zhang; Jinming Zhao; Yuanpeng Bu; Dong Xue; Zhangxiong Liu; Xiangnan Li; Jing Huang; Na Guo; Haitang Wang; Han Xing; Lijuan Qiu (Plant Molecular Biology Reporter, 2018)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

Phenolic acid production is more effectively enhanced than tanshinone production by methyl jasmonate in Salvia miltiorrhiza hairy roots - Bingcong Xing; Dongfeng Yang; Lin Liu; Ruilian Han; Yanfang Sun; Zongsuo Liang (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Foliar nutrient resorption differs between arbuscular mycorrhizal and ectomycorrhizal trees at local and global scales - Hai‐Yang Zhang; Xiao‐Tao Lü; Henrik Hartmann; Adrienne Keller; Xing‐Guo Han; Susan Trumbore; Richard P. Phillips (Global Ecology and Biogeography, 2018)
Aim Trees associating with ectomycorrhizal (ECM) fungi typically occur in infertile soils and use nutrients more conservatively than arbuscular mycorrhizal (AM) trees. We hypothesized that ECM trees would have greater nutrient resorption (i.e., proportion of nutrients resorbed during leaf senescence) than AM trees. Location Global. Methods We synthesized nitrogen (N) and phosphorus (P) resorption data from 378 species from sub/tropical, temperate and boreal forests, including 43 studies where ECM and AM trees co‐occurred, and conducted a meta‐analysis. Additionally, we quantified N resorption in 45 plots varying in ECM‐AM tree abundances in the temperate deciduous forests of southern Indiana, USA. Results Overall, resorption patterns were driven primarily by mycorrhizal type, climate zone, and to a lesser degree, leaf habit. In the boreal forest, P resorption was 76% greater for ECM than AM trees ( p p p = .08). Besides, deciduous ECM trees resorbed more N (10%) and P (15%) than deciduous AM trees, while evergreen ECM and AM trees did not differ. In the deciduous forests of Indiana, where ECM and AM trees co‐occurred, the relative abundance of ECM trees in a plot was positively correlated to plot‐scale N resorption ( R 2 = .25, p = .001), indicating greater nutrient conservatism with increasing ECM‐dominance. Main conclusions Our results indicate that mycorrhizal association – in addition to other factors – is correlated with the degree to which trees recycle nutrients, with the strongest effects occurring for N resorption by temperate deciduous trees.

Alteration of SlYABBY2b gene expression impairs tomato ovary locule number and endogenous gibberellin content - Hui Li; Mei-hua Sun; Ming-fang Qi; Jiao Xing; Tao Xu; Han-ting Liu; Tian-lai Li (Journal of Zhejiang University-SCIENCE B, 2018)

Umbilical Cord Mesenchymal Stem Cells Conditioned Medium Promotes Aβ25-35 phagocytosis by Modulating Autophagy and Aβ-Degrading Enzymes in BV2 Cells - Zhihao Xu; Wenbin Nan; Xiaoyue Zhang; Yuliang Sun; Jichao Yang; Kecheng Lu; Yalin Liu; Yaoxin Gao; Fen Yang; Wenchao Mao; Xuekun Xing; Jiang Du; et al. (Journal of Molecular Neuroscience, 2018)

Phenotypic plasticity may help lizards cope with increasingly variable temperatures - Liang Ma; Bao-jun Sun; Peng Cao; Xing-han Li; Wei-guo Du (Oecologia, 2018)

PGL3 is required for chlorophyll synthesis and impacts leaf senescence in rice - Jing Ye; Yao-long Yang; Xing-hua Wei; Xiao-jun Niu; Shan Wang; Qun Xu; Xiao-ping Yuan; Han-yong Yu; Yi-ping Wang; Yue Feng; Shu Wang (Journal of Zhejiang University-SCIENCE B, 2018)

Diagnostic value of computed tomography (CT) histogram analysis in thyroid benign solitary coarse calcification nodules - Le-xing Zhang; Jing-jing Xiang; Pei-ying Wei; Jin-wang Ding; Ding-cun Luo; Zhi-yi Peng; Zhi-jiang Han (Journal of Zhejiang University-SCIENCE B, 2018)

Complete canine spinal cord transection model: a large animal model for the translational research of spinal cord regeneration - Sufang Han; Xing Li; Zhifeng Xiao; Jianwu Dai (Science China Life Sciences, 2018)

Human placenta-derived mesenchymal stem cells loaded on linear ordered collagen scaffold improves functional recovery after completely transected spinal cord injury in canine - Sufang Han; Zhifeng Xiao; Xing Li; Huan Zhao; Bin Wang; Zhixue Qiu; Zhi Li; Xin Mei; Bai Xu; Caixia Fan; Bing Chen; Jin Han; et al. (Science China Life Sciences, 2018)

First identification of porcine parvovirus 7 in China - Xiulin Xing; Han Zhou; Ling Tong; Yao Chen; Yankuo Sun; Heng Wang; Guihong Zhang (Archives of Virology, 2018)

Consistent responses of litter stoichiometry to N addition across different biological organization levels in a semi-arid grassland - Shuang-Li Hou; Jiang-Xia Yin; Jun-Jie Yang; Hai-Wei Wei; Guo-Jiao Yang; Yan-Yu Hu; Xing-Guo Han; Xiao-Tao Lü (Plant and Soil, 2017)

Down-regulation of Noggin and miR-138 coordinately promote osteogenesis of mesenchymal stem cells - Xing-Kun Sun; Jin Zhou; Lei Zhang; Tian Ma; Yu-Han Wang; Yan-Mei Yang; Yan-Ting Tang; Hong Li; Li-Jun Wang (Journal of Molecular Histology, 2017)

Isolation and characterization of 44 SNP markers in Pseudogyrincheilus procheilus - Ting Liu; Shikai Li; Wei Wang; Bize Han; Xing Yang (Conservation Genetics Resources, 2017)

Simulated nitrogen deposition significantly suppresses the decomposition of forest litter in a natural evergreen broad-leaved forest in the Rainy Area of Western China - Shi-xing Zhou; Cong-de Huang; Bo-han Han; Yong-xiang Xiao; Jian-dong Tang; Yuan-bin Xiang; Chao Luo (Plant and Soil, 2017)

Effect of submerged macrophytes on metal and metalloid concentrations in sediments and water of the Yunnan Plateau lakes in China - Wei Xing; Guoliang Bai; Haoping Wu; Han Liu; Guihua Liu (Journal of Soils and Sediments, 2017)

Two new Anti-TMV active chalconoid analogues from the root of Phyllanthus emblica - He Yan; Li Rong Han; Xing Zhang; Jun Tao Feng (Natural Product Research, 2017)

A MDR transporter contributes to the different extracellular production of sesquiterpene pyridine alkaloids between adventitious root and hairy root liquid cultures of Tripterygium wilfordii Hook.f. - Guo-peng Miao; Juan Han; Ji-feng Zhang; Chuan-shu Zhu; Xing Zhang (Plant Molecular Biology, 2017)

Phylogenetic analysis of IDD gene family and characterization of its expression in response to flower induction in Malus - Sheng Fan; Dong Zhang; Libo Xing; Siyan Qi; Lisha Du; Haiqin Wu; Hongxia Shao; Youmei Li; Juanjuan Ma; Mingyu Han (Molecular Genetics and Genomics, 2017)

Controllable synthesis Fe3O4@POHABA core-shell nanostructure as high-performance recyclable bifunctional magnetic antimicrobial agent - Zhijia Zhang; Defeng Xing; Xin Zhao; Xiaojun Han (Environmental Science and Pollution Research, 2017)

Distribution, sources, and risk assessment of polychlorinated biphenyls in surface waters and sediments of rivers in Shanghai, China - Xueping Wang; Jingchao Han; Chunjuan Bi; Xing Huang; Jinpu Jia; Zhenlou Chen (Frontiers of Earth Science, 2017)

A Volumetric and Functional Connectivity MRI Study of Brain Arginine-Vasopressin Pathways in Autistic Children - Xiao-Jing Shou; Xin-Jie Xu; Xiang-Zhu Zeng; Ying Liu; Hui-Shu Yuan; Yan Xing; Mei-Xiang Jia; Qing-Yun Wei; Song-Ping Han; Rong Zhang; Ji-Sheng Han (Neuroscience Bulletin, 2017)

A novel model to assess soil productivity in the dry-hot valleys of China - Xing-wu Duan; Xu Han; Jin-ming Hu; De-tai Feng; Li Rong (Journal of Mountain Science, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Joint 3D traveltime calculation based on fast marching method and wavefront construction - Hui Sun; Jian-Guo Sun; Zhang-Qing Sun; Fu-Xing Han; Zhi-Qiang Liu; Ming-Chen Liu; Zheng-Hui Gao; Xiu-Lin Shi (Applied Geophysics, 2017)

QTLs for heading date and plant height under multiple environments in rice - Zhongmin Han; Wei Hu; Cong Tan; Yongzhong Xing (Genetica, 2017)

Molecular signal networks and regulating mechanisms of the unfolded protein response - Jing Gong; Xing-zhi Wang; Tao Wang; Jiao-jiao Chen; Xiao-yuan Xie; Hui Hu; Fang Yu; Hui-lin Liu; Xing-yan Jiang; Han-dong Fan (Journal of Zhejiang University-SCIENCE B, 2017)

Correlation between status of epidermal growth factor receptor mutation and distant metastases of lung adenocarcinoma upon initial diagnosis based on 1063 patients in China - Hongwei Li; Jianzhong Cao; Xiaqin Zhang; Xing Song; Weili Wang; Sufang Jia; Zhengran Li; Haixia Jia; Xing Cao; Wei Zhou; Jianhong Lian; Songye Han; et al. (Clinical & Experimental Metastasis, 2017)

Trace element stoichiometry of submerged macrophytes in Yangtze floodplain lakes and Yunnan plateau lakes (China) - Wei Xing; Haoping Wu; Beibei Hao; Han Liu; Guihua Liu (Aquatic Sciences, 2017)

Different responses of soybean cyst nematode resistance between two RIL populations derived from Peking × 7605 under two ecological sites - YONGCHUN LI; NA GUO; JINMING ZHAO; BIN ZHOU; RAN XU; HUI DING; WEIGUO ZHAO; JUNYI GAI; HAN XING (Journal of Genetics, 2016)

Normal moveout for long offset in isotropic media using the Padé approximation - Han-Jie Song; Jin-Hai Zhang; Zhen-Xing Yao (Applied Geophysics, 2016)

Nitrogen deposition promotes phosphorus uptake of plants in a semi-arid temperate grassland - Min Long; Hong-Hui Wu; Melinda D. Smith; Kimberly J. La Pierre; Xiao-Tao Lü; Hai-Yang Zhang; Xing-Guo Han; Qiang Yu (Plant and Soil, 2016)

Alterations to biological soil crusts with alpine meadow retrogressive succession affect seeds germination of three plant species - Yi-kang Li; Jing-zheng Ouyang; Li Lin; Xing-liang Xu; Fa-wei Zhang; Yan-gong Du; Shu-li Liu; Guang-min Cao; Fa Han (Journal of Mountain Science, 2016)

Nucleotide Diversity and Molecular Evolution of the ALK Gene in Cultivated Rice and its Wild Relatives - Ying Zhou; Hongyu Zheng; Guochao Wei; Hui Zhou; Yanni Han; Xufeng Bai; Yongzhong Xing; Yuepeng Han (Plant Molecular Biology Reporter, 2016)

Over-expression of GmHAL3 modulates salt stresses tolerance in transgenic arabidopsis - Na Guo; Ming-xia Wang; Chen-chen Xue; Dong Xue; Jin-yan Xu; Hai-tang Wang; Jun-yi Gai; Han Xing; Jin-ming Zhao (Journal of Plant Biology, 2016)

Detrital zircon geochronology of Devonian quartzite from tectonic mélange in the Mianlue Suture Zone, Central China: provenance and tectonic implications - Xing-Zhong Ji; Li-Qiang Yang; M. Santosh; Nan Li; Chuang Zhang; Zhi-Chao Zhang; Ri Han; Zai-Chun Li; Chun-Jun Wu (International Geology Review, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Early Abscisic Acid Accumulation Regulates Ascorbate and Glutathione Metabolism in Soybean Leaves Under Progressive Water Stress - Xinghua Xing; Qin Zhou; Han Xing; Haidong Jiang; Shaohua Wang (Journal of Plant Growth Regulation, 2016)

Description of Sphingomonas mohensis sp. nov., Isolated from Sediment - Lu Han; Yue-Wen Teng; Qing-Qing Feng; Ren-Gang Zhang; Xing-Min Zhao; Jie Lv; Bing Xie (Current Microbiology, 2016)

3D modeling of geological anomalies based on segmentation of multiattribute fusion - Zhi-Ning Liu; Cheng-Yun Song; Zhi-Yong Li; Han-Peng Cai; Xing-Miao Yao; Guang-Min Hu (Applied Geophysics, 2016)

3D finite-difference modeling algorithm and anomaly features of ZTEM - Tao Wang; Han-Dong Tan; Zhi-Qiang Li; Kun-Peng Wang; Zhi-Ming Hu; Xing-Dong Zhang (Applied Geophysics, 2016)

Common Aging Signature in the Peripheral Blood of Vascular Dementia and Alzheimer’s Disease - Hongbo Luo; Guangchun Han; Jiajia Wang; Fan Zeng; Yuanming Li; Shaoju Shao; Fuhai Song; Zhouxian Bai; Xing Peng; Yan-Jiang Wang; Xiangqun Shi; Hongxing Lei (Molecular Neurobiology, 2016)

One-year clinical study of NeuroRegen scaffold implantation following scar resection in complete chronic spinal cord injury patients - Zhifeng Xiao; Fengwu Tang; Jiaguang Tang; Huilin Yang; Yannan Zhao; Bing Chen; Sufang Han; Nuo Wang; Xing Li; Shixiang Cheng; Guang Han; Changyu Zhao; et al. (Science China Life Sciences, 2016)

Loci and candidate gene identification for resistance to Phytophthora sojae via association analysis in soybean [Glycine max (L.) Merr.] - Lihong Li; Na Guo; Jingping Niu; Zili Wang; Xiaoxia Cui; Jutao Sun; Tuanjie Zhao; Han Xing (Molecular Genetics and Genomics, 2016)

Toxic effects of HT-2 toxin on mouse oocytes and its possible mechanisms - Cheng-Cheng Zhu; Yue Zhang; Xing Duan; Jun Han; Shao-Chen Sun (Archives of Toxicology, 2016)

Impacts of leguminous shrub encroachment on neighboring grasses include transfer of fixed nitrogen - Hai-Yang Zhang; Qiang Yu; Xiao-Tao Lü; Susan E. Trumbore; Jun-Jie Yang; Xing-Guo Han (Oecologia, 2016)

Triadimefon Induced C and N Metabolism and Root Ultra-Structural Changes for Drought Stress Protection in Soybean at Flowering Stage - Qin Zhou; Yuanyuan Wu; Zheng Chonglan; Xinghua Xing; Lixin Liu; Haidong Jiang; Han Xing (Journal of Plant Growth Regulation, 2016)

Nutrient resorption helps drive intra-specific coupling of foliar nitrogen and phosphorus under nutrient-enriched conditions - Xiao-Tao Lü; Sasha C. Reed; Qiang Yu; Xing-Guo Han (Plant and Soil, 2016)

AlzBase: an Integrative Database for Gene Dysregulation in Alzheimer’s Disease - Zhouxian Bai; Guangchun Han; Bin Xie; Jiajia Wang; Fuhai Song; Xing Peng; Hongxing Lei (Molecular Neurobiology, 2016)

Myeloid-Specific Blockade of Notch Signaling by RBP-J Knockout Attenuates Spinal Cord Injury Accompanied by Compromised Inflammation Response in Mice - Bei-Yu Chen; Min-Hua Zheng; Yan Chen; Yan-Ling Du; Xiao-Long Sun; Xing Zhang; Li Duan; Fang Gao; Liang Liang; Hong-Yan Qin; Zhuo-Jing Luo; Hua Han (Molecular Neurobiology, 2015)

Impact of short-term climate variation and hydrology change on thermal structure and water quality of a canyon-shaped, stratified reservoir - Wei-Xing Ma; Ting-Lin Huang; Xuan Li; Hai-Han Zhang; Tuo Ju (Environmental Science and Pollution Research, 2015)

Streptomyces kanasensis sp. nov., an Antiviral Glycoprotein Producing Actinomycete Isolated from Forest Soil Around Kanas Lake of China - Lirong Han; Guoqiang Zhang; Guopeng Miao; Xing Zhang; Juntao Feng (Current Microbiology, 2015)

Response difference of transgenic and conventional rice (Oryza sativa) to nanoparticles (γFe2O3) - Xin Gui; Yingqing Deng; Yukui Rui; Binbin Gao; Wenhe Luo; Shili Chen; Le Van Nhan; Xuguang Li; Shutong Liu; Yaning Han; Liming Liu; Baoshan Xing (Environmental Science and Pollution Research, 2015)

Silicon improves salt tolerance by increasing root water uptake in Cucumis sativus L. - Yong-Xing Zhu; Xuan-Bin Xu; Yan-Hong Hu; Wei-Hua Han; Jun-Liang Yin; Huan-Li Li; Hai-Jun Gong (Plant Cell Reports, 2015)

Effects of light intensity on the susceptibility of Nicotiana tabacum to cucumber mosaic virus - Li-Juan Chen; Han Ren; Xing-Guang Deng; Ya-Nan Li; Wen-Qiong Cha; Hong-Hui Lin; De-Hui Xi (Journal of General Plant Pathology, 2015)

Early Cretaceous arc magmatism and high-sulphidation epithermal porphyry Cu–Au mineralization in Yanbian area, Northeast China: the Duhuangling example - Peng Chai; Jing-Gui Sun; Shu-Wen Xing; Lan-Jing Men; Ji-Long Han (International Geology Review, 2015)

Effects of delayed motherhood on hippocampal gene expression in offspring rats - Ping Duan; Bo Li; Caifang Li; Xuefei Han; Yan Xu; Ying Xing; Wenhai Yan (Molecular and Cellular Biochemistry, 2015)

Potent CDC25B and PTP1B phosphatase inhibitors: 2′,4′,6′-trihydroxylchalcone derivatives - Shui-Lian Zhao; Zhou Peng; Xing-Hua Zhen; Hong-Guo Jin; Yan Han; You-Le Qu; Li-Ping Guan (Medicinal Chemistry Research, 2015)

Drug susceptibility and molecular epidemiology of Escherichia coli in bloodstream infections in Shanghai, China, 2011–2013 - Sheng-Yuan Zhao; Yan-Chun Wang; Shu-Zhen Xiao; Xiao-Fei Jiang; Xiao-Kui Guo; Yu-Xing Ni; Li-Zhong Han (Infectious Diseases, 2015)

Transglutaminase-2 is Involved in Cell Apoptosis of Osteosarcoma Cell Line U2OS Under Hypoxia Condition - Wei Wang; Xiao Li; Xiang-zhen Han; Fan-bin Meng; Zhen-xing Wang; Yong-qing Zhai; Dong-sheng Zhou (Cell Biochemistry and Biophysics, 2015)

Association mapping of salinity and alkalinity tolerance in improved japonica rice (Oryza sativa L. subsp. japonica Kato) germplasm - Di Cui; Chang-ying Xu; Chun-gang Yang; Qi-xing Zhang; Jun-guo Zhang; Xiao-ding Ma; Yong-li Qiao; Gui-lan Cao; San-yuan Zhang; Long-zhi Han (Genetic Resources and Crop Evolution, 2015)

Effects of Plant Stress Signal Molecules on the Production of Wilforgine in an Endophytic Actinomycete Isolated from Tripterygium wilfordii Hook.f. - Guo-peng Miao; Chuan-shu Zhu; Jun-tao Feng; Li-rong Han; Xing Zhang (Current Microbiology, 2015)

Erratum to: Evolutionary fate of SVA2 elements in primate genomes - Yongsik Kwak; Yun-ji Kim; Jinchuan Xing; Kyudong Han (Genes & Genomics, 2015)

Contrasting responses in leaf nutrient-use strategies of two dominant grass species along a 30-yr temperate steppe grazing exclusion chronosequence - Xiao-Tao Lü; Grégoire T. Freschet; Elena Kazakou; Zheng-Wen Wang; Li-Shi Zhou; Xing-Guo Han (Plant and Soil, 2015)

Evolutionary fate of SVA2 elements in primate genomes - Yonsik Kwak; Yun-ji Kim; Jinchuan Xing; Kyudong Han (Genes & Genomics, 2015)

Understanding of the molecular evolution of deafness-associated pathogenic mutations of connexin 26 - Xin-Huan Han; Yi Fan; Qin-Jun Wei; Guang-Qian Xing; Xin Cao (Genetica, 2014)

Evaluation of Flow Velocity in Unilateral Middle Cerebral Artery Stenosis by Transcranial Doppler - Lin Wang; Yingqi Xing; Yang Li; Ke Han; Jiafeng Chen (Cell Biochemistry and Biophysics, 2014)

Hierarchical responses of plant stoichiometry to nitrogen deposition and mowing in a temperate steppe - Xu Han; Seeta A. Sistla; Yun-Hai Zhang; Xiao-Tao Lü; Xing-Guo Han (Plant and Soil, 2014)

GmSGT1 is differently required for soybean Rps genes-mediated and basal resistance to Phytophthora sojae - Qiang Yan; Xiaoxia Cui; Liming Su; Na Xu; Na Guo; Han Xing; Daolong Dou (Plant Cell Reports, 2014)

Computational identification of novel microRNAs and targets in Glycine max - Na Guo; Wenwu Ye; Qiang Yan; Jing Huang; Yuren Wu; Danyu Shen; Junyi Gai; Daolong Dou; Han Xing (Molecular Biology Reports, 2014)

Association mapping for partial resistance to Phytophthora sojae in soybean (Glycine max (L.) Merr.) - JUTAO SUN; NA GUO; JUN LEI; LIHONG LI; GUANJUN HU; HAN XING (Journal of Genetics, 2014)

Multiwave velocity analysis based on Gaussian beam prestack depth migration - Jian-Guang Han; Yun Wang; Ning Han; Zhan-Tao Xing; Jun Lu (Applied Geophysics, 2014)

Genetic analysis and fine mapping of RpsJS, a novel resistance gene to Phytophthora sojae in soybean [Glycine max (L.) Merr.] - Jutao Sun; Lihong Li; Jinming Zhao; Jing Huang; Qiang Yan; Han Xing; Na Guo (Theoretical and Applied Genetics, 2014)

Halobellus litoreus sp. nov., a Halophilic Archaeon Isolated from a Chinese Marine Solar Saltern - Mei-Lin Zhao; Xing-Xing Qiu; Wen-Jiao Zhang; Dong Han; Heng-Lin Cui; Zheng-Rong Li (Current Microbiology, 2014)

Natural antisense transcripts of UL123 packaged in human cytomegalovirus virions - Cui-Qing Yang; Ling-Feng Miao; Xing Pan; Cong-Cong Wu; Simon Rayner; Edward S. Mocarski; Han-Qing Ye; Min-Hua Luo (Archives of Virology, 2014)

Preparation and Characterization of Microcapsules Containing Squalene - Lulu Han; Liangwu Bi; Zhendong Zhao; Guilin Gao; Yali Xing (BioEnergy Research, 2013)

Haloplanus salinus sp. nov., an extremely halophilic archaeon from a Chinese marine solar saltern - Xing–Xing Qiu; Mei-Lin Zhao; Dong Han; Wen-Jiao Zhang; Heng-Lin Cui (Archives of Microbiology, 2013)

Investigation of individual heterozygosity correlated to growth traits in Tongshan Black-boned goat - Yan Guo Han; Gui Qiong Liu; Xun Ping Jiang; Guo Ming Liang; Chun Bo He; Dang Wei Wang; Yan Wu; Xing Long Xiang; Jie Hu; Yu Qin Peng (Molecular Biology Reports, 2013)

Identification and characterization of Pestalotiopsis spp. causing twig blight disease of bayberry (Myrica rubra Sieb. & Zucc) in China - Hai-Ying Ren; Gang Li; Xing-Jiang Qi; Li Fang; Han-Rong Wang; Ji-Guang Wei; Shaobin Zhong (European Journal of Plant Pathology, 2013)

Halorubrum rubrum sp. nov., an extremely halophilic archaeon from a Chinese salt lake - Xing-Xing Qiu; Mei-Lin Zhao; Dong Han; Wen-Jiao Zhang; Heng-Lin Cui (Antonie van Leeuwenhoek, 2013)

Impact of matrix metalloproteinase-8 gene variations on the risk of thoracic aortic dissection in a Chinese Han population - Xiao-Zeng Wang; Xiao-Mo Du; Quan-Min Jing; Xing-Xing Li; Ruo-Xi Gu; Jiao Wang; Ya-Ling Han (Molecular Biology Reports, 2013)

Halobellus rarus sp. nov., a halophilic archaeon from an inland salt lake of China - Wen-Jiao Zhang; Dong Han; Xing-Xing Qiu; Mei-Lin Zhao; Yun-Zhuang Mou; Heng-Lin Cui; Zheng-Rong Li (Antonie van Leeuwenhoek, 2013)

Convergent responses of nitrogen and phosphorus resorption to nitrogen inputs in a semiarid grassland - Xiao‐Tao Lü; Sasha Reed; Qiang Yu; Nian‐Peng He; Zheng‐Wen Wang; Xing‐Guo Han (Global Change Biology, 2013)
Human activities have significantly altered nitrogen (N) availability in most terrestrial ecosystems, with consequences for community composition and ecosystem functioning. Although studies of how changes in N availability affect biodiversity and community composition are relatively common, much less remains known about the effects of N inputs on the coupled biogeochemical cycling of N and phosphorus (P), and still fewer data exist regarding how increased N inputs affect the internal cycling of these two elements in plants. Nutrient resorption is an important driver of plant nutrient economies and of the quality of litter plants produce. Accordingly, resorption patterns have marked ecological implications for plant population and community fitness, as well as for ecosystem nutrient cycling. In a semiarid grassland in northern China, we studied the effects of a wide range of N inputs on foliar nutrient resorption of two dominant grasses, Leymus chinensis and Stipa grandis . After 4 years of treatments, N and P availability in soil and N and P concentrations in green and senesced grass leaves increased with increasing rates of N addition. Foliar N and P resorption significantly decreased along the N addition gradient, implying a resorption‐mediated, positive plant–soil feedback induced by N inputs. Furthermore, N : P resorption ratios were negatively correlated with the rates of N addition, indicating the sensitivity of plant N and P stoichiometry to N inputs. Taken together, the results demonstrate that N additions accelerate ecosystem uptake and turnover of both N and P in the temperate steppe and that N and P cycles are coupled in dynamic ways. The convergence of N and P resorption in response to N inputs emphasizes the importance of nutrient resorption as a pathway by which plants and ecosystems adjust in the face of increasing N availability.

AhR expression is increased in hepatocellular carcinoma - Ziyu Liu; Xing’an Wu; Fanglin Zhang; Lurong Han; Guoqiang Bao; Xianli He; Zhikai Xu (Journal of Molecular Histology, 2013)

Functional analysis of BT4 of Arabidopsis thaliana in resistance against Botrytis cinerea - Cong-Cong Hao; Jiao Jia; Zhan Chen; Ji-Hong Xing; Qiao-Yun Weng; Feng-Ru Wang; Jin-Gao Dong; Jian-Min Han (Australasian Plant Pathology, 2013)

Simultaneous removal of nitrate and pentachlorophenol from simulated groundwater using a biodenitrification reactor packed with corncob - Xuming Wang; Lijun Xing; Tianlei Qiu; Meilin Han (Environmental Science and Pollution Research, 2013)

Disruption of the transcription factor RBP-J results in osteopenia attributable to attenuated osteoclast differentiation - Jing Ma; Ya-Li Liu; Yi-Yang Hu; Ya-Ning Wei; Xing-Cheng Zhao; Guang-Ying Dong; Hong-Yan Qin; Yin Ding; Hua Han (Molecular Biology Reports, 2013)

Quantitative evaluation of Candia antarctica lipase B displayed on the cell surface of a Pichia pastoris based on an FS anchor system - Xing-xiang Liang; Bei-bei Wang; Yu-fei Sun; Ying Lin; Shuang-yan Han; Sui-ping Zheng; Tang-bing Cui (Biotechnology Letters, 2013)

Geology and ages of porphyry and medium- to high-sulphidation epithermal gold deposits of the continental margin of Northeast China - Shi-Jiong Han; Jing-Gui Sun; Ling-An Bai; Shu-Wen Xing; Peng Chai; Yong Zhang; Fan Yang; Lan-Jing Men; Yi-Xin Li (International Geology Review, 2013)

A comparative proteomics analysis of soybean leaves under biotic and abiotic treatments - Jinming Zhao; Yumei Zhang; Xiaochun Bian; Jun Lei; Jutao Sun; Na Guo; Junyi Gai; Han Xing (Molecular Biology Reports, 2013)

Mutations in AP22.65 accelerate flowering in Arabidopsis thaliana - Ji Hong Xing; Feng Ru Wang; Jiao Jia; Jing Zhang; Li Li; Zhan Chen; Qiao Yun Weng; Ping Yang; Ye Zhang; Bin Zhao; He Long Si; Jin Gao Dong; et al. (Journal of Plant Biology, 2013)

Aggregate cell suspension cultures of Tripterygium wilfordii Hook. f. for triptolide, wilforgine, and wilforine production - Guo-peng Miao; Chuan-shu Zhu; Jun-tao Feng; Juan Han; Xiao-Wei Song; Xing Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Relation between nitrous oxide production in wetland and groundwater: a case study in the headwater wetland - Xing Li; Changyuan Tang; Zhiwei Han; Yingjie Cao; Chipeng Zhang (Paddy and Water Environment, 2013)

Compromised cerebrovascular modulation in chronic anxiety: evidence from cerebral blood flow velocity measured by transcranial Doppler sonography - Hong-Liang Zhang; Zhen-Ni Guo; Ge Yang; Le Yang; Ke Han; Jiang Wu; Yingqi Xing; Yi Yang (Neuroscience Bulletin, 2012)

Downregulation of galectin-3 by EGF mediates the apoptosis of HepG2 cells - Zhenzhen Hu; Xiuqin Jiang; Ying Xu; Nan Lu; Weizhi Wang; Jie Luo; Han Zou; Datong Zheng; Xing Feng (Molecular and Cellular Biochemistry, 2012)

The influence of sea water velocity variation on seismic traveltimes, ray paths, and amplitude - Fu-Xing Han; Jian-Guo Sun; Kun Wang (Applied Geophysics, 2012)

Time-dependent expression and distribution of Egr-1 during skeletal muscle wound healing in rats - Yan-Yan Fan; Guang-Hua Ye; Ke-Zhi Lin; Lin-Sheng Yu; Shu-Zhen Wu; Miao-Wu Dong; Jun-Ge Han; Xiang-Ping Feng; Xing-Biao Li (Journal of Molecular Histology, 2012)

Meta-analysis of MCP-1 promoter −2518 A/G polymorphism and SLE susceptibility - Ting Liu; Jin-Xia Zhai; Han-Yong Wang; Xing-Hua Wang; Li-Wei Zou; Wen-jing Fan; Dong-Qing Ye (Molecular Biology Reports, 2012)

Partial Purification and Characterization of Fibrinolytic Enzymes from Yellow Mealworm - Ming Xing Huang; Yun Ye; Ya Xiong Chen; Ya Li Han (International Journal of Peptide Research and Therapeutics, 2012)

Formaldehyde up-regulates TRPV1 through MAPK and PI3K signaling pathways in a rat model of bone cancer pain - Ying Han; Yan Li; Xing Xiao; Jia Liu; Xiang-Ling Meng; Feng-Yu Liu; Guo-Gang Xing; You Wan (Neuroscience Bulletin, 2012)

Characterization of Prototheca zopfii Associated with Outbreak of Bovine Clinical Mastitis in Herd of Beijing, China - Jian Gao; Han-qi Zhang; Jian-zhong He; Yang-hua He; Shu-mei Li; Rong-guang Hou; Qiao-xing Wu; Yang Gao; Bo Han (Mycopathologia, 2012)

Effect of neuronal induction on NSE, Tau, and Oct4 promoter methylation in bone marrow mesenchymal stem cells - Ping Duan; Ying Zhang; Xuefei Han; Junling Liu; Wenhai Yan; Ying Xing (In Vitro Cellular & Developmental Biology - Animal, 2012)

Nitrogen and water availability interact to affect leaf stoichiometry in a semi-arid grassland - Xiao-Tao Lü; De-Liang Kong; Qing-Min Pan; Matthew E. Simmons; Xing-Guo Han (Oecologia, 2012)

Differential expression of AdipoR1, IGFBP3, PPARγ and correlative genes during porcine preadipocyte differentiation - Hai-Feng Liu; Ming-Xing Gui; Han Dong; Xun Wang; Xue-Wei Li (In Vitro Cellular & Developmental Biology - Animal, 2012)

Taxol-induced alteration of intracellular amino-acid profile related to human cervical carcinoma HeLa cell death - Xiao-Fei Han; Yan-Qiu Liu; Long-Xing Wang; Qian-Xu Yang; Hong-Bin Xiao (Biotechnology Letters, 2012)

CTLA-4 exon 1 +49 polymorphism alone and in a haplotype with −318 promoter polymorphism may confer susceptibility to chronic HBV infection in Chinese Han patients - Shaoqiong Duan; Guoyu Zhang; Qunying Han; Zhu Li; Zhengwen Liu; Jinghong Chen; Yi Lv; Na Li; Yawen Wang; Man Li; Sai Lou; Mingbo Yang; et al. (Molecular Biology Reports, 2011)

Genomic Differences Between Actinobacillus pleuropneumoniae Serotypes 5b and 3 and their Distribution and Transcription Among 15 Serotypes - Feng Yang; Fang Xie; Yuwen Jiang; Suqing Li; Yanping Xing; Yu Wang; Xin Feng; Wenyu Han; Liancheng Lei (Current Microbiology, 2011)

Identification and expression analysis of two growth hormone receptors in zanzibar tilapia (Oreochromis hornorum) - Feng-Ying Gao; Mai-Xin Lu; Xing Ye; Zhang-Han Huang; Huan Wang; Hua-Ping Zhu; Li-Ping Yang (Fish Physiology and Biochemistry, 2011)

A tyrosine decarboxylase catalyzes the initial reaction of the salidroside biosynthesis pathway in Rhodiola sachalinensis - Ji-Xing Zhang; Lan-Qing Ma; Han-Song Yu; Hong Zhang; Hao-Tian Wang; Yun-Fei Qin; Guang-Lu Shi; You-Nian Wang (Plant Cell Reports, 2011)

The investigation of the interaction between ribavirin and bovine serum albumin by spectroscopic methods - Xing-Jia Guo; Ai-Jun Hao; Xiao-Wei Han; Ping-Li Kang; Yu-Chun Jiang; Xiang-Jun Zhang (Molecular Biology Reports, 2011)

Expression of a novel gene FAM43B repressing cell proliferation is regulated by DNA methylation in hepatocellular carcinoma cell lines - Xiao Xu; Rui-Fang Liu; Bing-Bing Wan; Wen-Ming Xing; Jian Huang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2011)

Profile of Organochlorine Pesticides in Soil Cores from Some Hotspot Areas of Beijing, China - Hang-Xin Cheng; Xing-Hong Li; Ya-Ping Wang; Chuan-Dong Zhao; Ying-Han Liu; Hong-Han Chen; Xiao-Bai Xu (Bulletin of Environmental Contamination and Toxicology, 2011)

Isolation and expression analysis of LEA genes in peanut (Arachis hypogaea L.) - Lei Su; Chuan-Zhi Zhao; Yu-Ping Bi; Shu-Bo Wan; Han Xia; Xing-Jun Wang (Journal of Biosciences, 2011)

Malignant transformation of 293 cells induced by ectopic expression of human Nanog - Yan-Li Lin; Zheng-Bin Han; Fu-Yin Xiong; Li-Yuan Tian; Xiao-Jie Wu; Shi-Wei Xue; Yan-Rong Zhou; Ji-Xian Deng; Hong-Xing Chen (Molecular and Cellular Biochemistry, 2011)

c-Src in paraventricular nucleus modulates sympathetic activity and cardiac sympathetic afferent reflex in renovascular hypertensive rats - Ying Han; Ning Yuan; Shu-Juan Zhang; Juan Gao; Zhen Shi; Ye-Bo Zhou; Xing-Ya Gao; Guo-Qing Zhu (Pflügers Archiv - European Journal of Physiology, 2011)

Expression patterns of imprinted gene Inpp5f-v3 during mouse brain development - Chen Yan; He Hongjuan; Xing Yanjiang; Han Zhengbin; Li Kai; Zhang Fengwei; Hou Jing; Wu Qiong (Journal of Molecular Histology, 2011)

The effects of biomass removal and N additions on microbial N transformations and biomass at different vegetation types in an old-field ecosystem in northern China - Changhui Wang; Klaus Butterbach-Bahl; Yi Han; Qibing Wang; Lihua Zhang; Xingguo Han; Xuerong Xing (Plant and Soil, 2011)

Feedback of grazing on gross rates of N mineralization and inorganic N partitioning in steppe soils of Inner Mongolia - Honghui Wu; Michael Dannenmann; Nicole Fanselow; Benjamin Wolf; Zhisheng Yao; Xing Wu; Nicolas Brüggemann; Xunhua Zheng; Xingguo Han; Klaus Dittert; Klaus Butterbach-Bahl (Plant and Soil, 2011)

Molecular cloning and characterization of Izumo1 gene from sheep and cashmere goat reveal alternative splicing - Wan-Jin Xing; Bao-Da Han; Qi Wu; Li Zhao; Xiao-Hong Bao; Shorgan Bou (Molecular Biology Reports, 2011)

Determination of optimal carbon source and pH value for sclerotial formation of Polyporus umbellatus under artificial conditions - Yong-Mei Xing; Juan Chen; Ya-Li Lv; Han-Qiao Liang; Shun-Xing Guo (Mycological Progress, 2011)

Carbon and nitrogen storage in plant and soil as related to nitrogen and water amendment in a temperate steppe of northern China - Fu-Mei Lü; Xiao-Tao Lü; Wei Liu; Xu Han; Guang-Ming Zhang; De-Liang Kong; Xing-Guo Han (Biology and Fertility of Soils, 2011)

A survey of soybean germplasm for resistance to Phytophthora sojae - Xiao-Ling Wu; Jin-Ming Zhao; Shi Sun; Feng Yang; Yuan-Chao Wang; Jun-Yi Gai; Han Xing (Euphytica, 2010)

Nitrogen fertilization and fire act independently on foliar stoichiometry in a temperate steppe - Qiang Cui; Xiao-Tao Lü; Qi-Bing Wang; Xing-Guo Han (Plant and Soil, 2010)

Lipid Peroxidation and Changes of Trace Elements in Mice Treated with Paradichlorobenzene - Wang Suhua; Lu Rongzhu; Yin Changqing; Xing Guangwei; Han Fangan; Jing Junjie; Xu Wenrong; Michael Aschner (Biological Trace Element Research, 2010)

Endemic Seed Plant Species from Hainan Island: A Checklist - Javier Francisco-Ortega; Fa-Guo Wang; Zhong-Sheng Wang; Fu-Wu Xing; Hong Liu; Han Xu; Wei-Xiang Xu; Yi-Bo Luo; Xi-Qiang Song; Stephan Gale; David E. Boufford; Mike Maunder; et al. (The Botanical Review, 2010)

Seed Plant Endemism on Hainan Island: A Framework for Conservation Actions - Javier Francisco-Ortega; Zhong-Sheng Wang; Fa-Guo Wang; Fu-Wu Xing; Hong Liu; Han Xu; Wei-Xiang Xu; Yi-Bo Luo; Xi-Qiang Song; Stephan Gale; David E. Boufford; Mike Maunder; et al. (The Botanical Review, 2010)

cDNA sequence and tissues expression analysis of lipoprotein lipase from common carp (Cyprinus carpio Var. Jian) - Han-liang Cheng; Si-ping Sun; Yong-xing Peng; Xiao-yun Shi; Xin Shen; Xue-ping Meng; Zhi-guo Dong (Molecular Biology Reports, 2010)

Phenotypic and Genetic Characteristics of Macrolide and Lincosamide Resistant Ureaplasma urealyticum Isolated in Guangzhou, China - Chun Lu; Ting lu Ye; Guo xing Zhu; Pei ying Feng; Han Ma; Rong biao Lu; Wei Lai (Current Microbiology, 2010)

A new cytotoxic iridoid from Callicarpa nudiflora - Wen-Li Mei; Zhuang Han; Hai-Bin Cui; You-Xing Zhao; Yuan-Yuan Deng; Hao-Fu Dai (Natural Product Research, 2010)

Interactive effects of soil nitrogen and water availability on leaf mass loss in a temperate steppe - Xiao-Tao Lü; Cun-Zheng Wei; Qiang Cui; Yun-Hai Zhang; Xing-Guo Han (Plant and Soil, 2010)

Induction or inhibition of cytochrome P450 2E1 modifies the acute toxicity of acrylonitrile in rats: biochemical evidence - Wang Suhua; Lu Rongzhu; Xu Wenrong; Xing Guangwei; Zhao Xiaowu; Wang Shizhong; Zhang Ye; Han Fangan; Michael Aschner (Archives of Toxicology, 2010)

Angiotensin-(1–7) and angiotension II in the rostral ventrolateral medulla modulate the cardiac sympathetic afferent reflex and sympathetic activity in rats - Li-Min Zhou; Zhen Shi; Juan Gao; Ying Han; Ning Yuan; Xing-Ya Gao; Guo-Qing Zhu (Pflügers Archiv - European Journal of Physiology, 2010)

Isolation and Characterization of Putative Acetyl-CoA Carboxylases in Arachis hypogaea L. - Meng-Jun Li; Han Xia; Chuan-Zhi Zhao; Ai-Qin Li; Chang-Sheng Li; Yu-Ping Bi; Shu-Bo Wan; Xing-Jun Wang (Plant Molecular Biology Reporter, 2010)

Nutrient resorption responses to water and nitrogen amendment in semi-arid grassland of Inner Mongolia, China - Xiao-Tao Lü; Xing-Guo Han (Plant and Soil, 2010)

Dissipation and Residues of Chlormequat in Wheat and Soil - Xing-li Guo; Chun-hong Jia; Er-cheng Zhao; Yan-jun Xu; Li-jun Han; Shu-ren Jiang (Bulletin of Environmental Contamination and Toxicology, 2010)

A single-nucleotide polymorphism of the TNFAIP3 gene is associated with systemic lupus erythematosus in Chinese Han population - Li-Qiong Cai; Zai-Xing Wang; Wen-Sheng Lu; Jian-Wen Han; Liang-Dan Sun; Wen-Hui Du; Shu-Mei Zhang; Xian-Bo Zuo; Xue-Jun Zhang; Sen Yang (Molecular Biology Reports, 2010)

Receptor mediation and nociceptin inhibition of bradykinin-induced plasma extravasation in the knee joint of the rat - Kumi Moriyama; Jia Liu; Yeon Jang; Yun Jeong Chae; Yan Wang; James Mitchell; Stefan Grond; Xiaokang Han; Yilei Xing; Guo-xi Xie; Pamela Pierce Palmer (Inflammation Research, 2009)

Hydrogeochemical Indicators of Groundwater Flow Systems in the Yangwu River Alluvial Fan, Xinzhou Basin, Shanxi, China - Dongmei Han; Xing Liang; Menggui Jin; Matthew J. Currell; Ying Han; Xianfang Song (Environmental Management, 2009)

Zinc, Copper, Iron, and Selenium Levels in Brain and Liver of Mice Exposed to Acrylonitrile - Lu Rongzhu; Wang Suhua; Xing Guangwei; Ren Chunlan; Han Fangan; Jing Junjie; Michael Aschner (Biological Trace Element Research, 2009)

Cloning and sequence analysis of putative type II fatty acid synthase genes from Arachis hypogaea L. - Meng-Jun Li; Ai-Qin Li; Han Xia; Chuan-Zhi Zhao; Chang-Sheng Li; Shu-Bo Wan; Yu-Ping Bi; Xing-Jun Wang (Journal of Biosciences, 2009)

QTL analysis of kernel shape and weight using recombinant inbred lines in wheat - Xian-Yin Sun; Ke Wu; Yan Zhao; Fan-Mei Kong; Guan-Zhu Han; Hong-Ming Jiang; Xing-Jiao Huang; Rui-Jun Li; Hong-Gang Wang; Si-Shen Li (Euphytica, 2009)

Heat shock proteins and p53 play a critical role in K+ channel-mediated tumor cell proliferation and apoptosis - Xiaobing Han; Fang Wang; Weixing Yao; Hui Xing; Danhui Weng; Xiaohong Song; Gang Chen; Ling Xi; Tao Zhu; Jianfeng Zhou; Gang Xu; Shixuan Wang; et al. (Apoptosis, 2007)

Plant–microbe association for rhizoremediation of chloronitroaromatic pollutants with Comamonas sp. strain CNB‐1 - Lei Liu; Cheng‐Ying Jiang; Xing‐Yu Liu; Jian‐Feng Wu; Ji‐Gang Han; Shuang‐Jiang Liu (Environmental Microbiology, 2007)
Summary Comamonas sp. strain CNB‐1, isolated from activated sludge and having a strong ability to degrade 4‐chloronitrobenzene (4CNB), was applied for rhizoremediation of 4CNB‐polluted soil through association with alfalfa. Confocal laser scanning microscopy revealed that strain CNB‐1 successfully colonized alfalfa roots. Determination of strain CNB‐1 populations by cultivation method and by quantitative competitive PCR technique targeting the chloronitrobenzene nitroreductase gene showed that the population of strain CNB‐1 in the rhizosphere was about 10–100 times higher than that in the bulk soil. Gnotobiotic and outdoor experiments showed that pollutant 4CNB was completely removed within 1 or 2 days after 4CNB application into soil, and that its phytotoxicity to alfalfa was eliminated by inoculation of strain CNB‐1. Results from PCR‐denaturing gradient gel electrophoresis and analysis of 16S rRNA gene libraries revealed that the indigenous soil microbial community mainly consisted of alphaproteobacteria, betaproteobacteria, gammaproteobacteria, the CFB bacteria ( Cytophaga‐Flavabacterium‐Bacteriodes ), and Acidobacteria . This microbial community was not significantly influenced by inoculation of strain CNB‐1. Thus, this study has developed a Comamonas ‐alfalfa system for rhizoremediation of 4CNB.

Oogenesis in summer females of the rice water weevil, Lissorhoptrus oryzophilus Kuschel (Coleoptera: Curculionidae), in southern Zhejiang, China - Sheng-wei Shi; Ming-xing Jiang; Han-wu Shang; Hui-ping Lv; Jia-an Cheng (Journal of Zhejiang University-SCIENCE B, 2007)

Nitrogen response efficiency increased monotonically with decreasing soil resource availability: a case study from a semiarid grassland in northern China - Zhi-You Yuan; Ling-Hao Li; Xing-Guo Han; Shi-Ping Chen; Zheng-Wen Wang; Quan-Sheng Chen; Wen-Ming Bai (Oecologia, 2006)

Identification and characterization of piggyBac-like elements in the genome of domesticated silkworm, Bombyx mori - Han-Fu Xu; Qing-You Xia; Chun Liu; Ting-Cai Cheng; Ping Zhao; Jun Duan; Xing-Fu Zha; Shi-Ping Liu (Molecular Genetics and Genomics, 2006)

Salicylic Acid Enhances Jaceosidin and Syringin Production in Cell Cultures of Saussurea medusa - Zhen-Zhen Yu; Chun-Xiang Fu; Ying-Shan Han; Yong-Xing Li; De-Xiu Zhao (Biotechnology Letters, 2006)

GS3, a major QTL for grain length and weight and minor QTL for grain width and thickness in rice, encodes a putative transmembrane protein - Chuchuan Fan; Yongzhong Xing; Hailiang Mao; Tingting Lu; Bin Han; Caiguo Xu; Xianghua Li; Qifa Zhang (Theoretical and Applied Genetics, 2006)

Effects of Cycle Time on Properties of Aerobic Granules in Sequencing Batch Airlift Reactors - Fang Wang; Feng-lin Yang; Xing-wen Zhang; Yi-hui Liu; Han-min Zhang; Jun Zhou (World Journal of Microbiology and Biotechnology, 2005)

A Population-Based Morphologically Structured Model for Hyphal Growth and Product Formation in Streptomycin Fermentation - Gang Liu; Miao Xing and; Qingguo Han (World Journal of Microbiology and Biotechnology, 2005)

Foliar Nitrogen Dynamics and Nitrogen Resorption of a Sandy Shrub Salix gordejevii in Northern China - Zhi-You Yuan; Ling-Hao Li; Xing-Guo Han; Jian-Hui Huang; Shi-Qiang Wan (Plant and Soil, 2005)

A Pilot Study of Transcription Unit Analysis in Rice Using Oligonucleotide Tiling-path Microarray - Viktor Stolc; Lei Li; Xiangfeng Wang; Xueyong Li; Ning Su; Waraporn Tongprasit; Bin Han; Yongbiao Xue; Jiayang Li; Michael Snyder; Mark Gerstein; Jun Wang; et al. (Plant Molecular Biology, 2005)

Soil characteristics and nitrogen resorption in Stipa krylovii native to northern China - Zhi-You Yuan; Ling-Hao Li; Xing-Guo Han; Jian-Hui Huang; Gao-Ming Jiang; Shi-Qiang Wan (Plant and Soil, 2005)

Screening and characterization of astaxanthin-hyperproducing mutants of Haematococcus pluvialis - Yong Chen; Defa Li; Wenqing Lu; Jianjun Xing; Bodi Hui; Yashan Han (Biotechnology Letters, 2003)

Phenotypic polymorphism of CYP2A6 activity in a Chinese population - Ping Xu; Song-Lin Huang; Rong-Hua Zhu; Xing-Mei Han; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2002)

Phylogeny of Saururaceae based on mitochondrial matR gene sequence data - Shao-Wu Meng; Zhi-Duan Chen; De-Zhu Li; Han-Xing Liang (Journal of Plant Research, 2002)